Single and combined toxicity of the harmful dinoflagellates Alexandrium minutum and Protoceratium reticulatum in the copepod Nitokra spinipes - Wenxin Liu; Ilias Semmouri; Luca Deroma; Colin R. Janssen; Jana Asselman (Marine Pollution Bulletin, 2026)

Herbicolin A, an antifungal lipopeptide produced by Pantoea agglomerans APC 4211 is a promising biocontrol agent against food spoilage fungi - Eleni Kamilari; Paula M. O'Connor; Jerry Reen; Promi Das; Aiswariya Deliephan; Daragh Hill; Oxana Fursenko; Jonathan Weise; Ay Sha Naomi Moore; Colin Hill; Catherine Stanton; Paul R. Ross (International Journal of Food Microbiology, 2026)

Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Application of QPS- and GRAS-status microorganisms and bacteriocins for sustainable food preservation - Eleni Kamilari; Catherine Stanton; Colin Hill; R. Paul Ross (International Journal of Food Microbiology, 2026)

Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

Fish Assemblage Shift Following Abrupt Seagrass Loss in a Southwest Florida Tidal Creek - Kelly S. Chase; Philip W. Stevens; David A. Blewett; Courtney R. Saari; Colin P. Shea; Jeffrey E. Hill; Quenton M. Tuckett (Estuaries and Coasts, 2026)
Phase shifts can occur in ecosystems because of external stressors. Such transitions from one state (e.g., clear water, seagrass) to another (e.g., phytoplankton blooms, bare substrate) continue to be documented worldwide. In estuaries, stressors related to urban and suburban development are often implicated in phase shifts, including altered hydrology and eutrophication. Tidal creeks may be especially prone to phase shifts as their position in the landscape exposes them to the brunt of coastal development. In 2017, a precipitous seagrass decline occurred in a tidal creek downstream of coastal development in the Charlotte Harbor estuary, Florida (USA). Fisheries independent monitoring data (July 2014 to June 2022) from 21.3 m seines were used to investigate changes in fish assemblages. Multivariate analyses identified a fish assemblage shift that coincided with seagrass loss and increasing algal blooms. Reductions in seagrass-associated species (e.g., Rainwater Killifish Lucania parva ) were offset by increases in generalist and planktivorous taxa (e.g., Bay Anchovy Anchoa mitchilli ). Such changes did not occur in neighboring creeks downstream of more natural habitat. The present study is indicative of a potential phase shift. Tidal creeks serve as ‘sentinels’ for ecosystem change. Furthermore, similar patterns of seagrass loss and algal blooms are taking place in the open estuary; thus, the fish assemblage shift identified in the tidal creek may signal similar, widespread changes. Identifying shifts in biotic assemblages and predominant drivers can help guide resource planning to strengthen ecosystem resilience and recovery within Charlotte Harbor and other Florida estuaries.

Anticipating winners and losers in a warming southern North Sea: improved climate forcing in an ecosystem-based model - Dries Lorré; Sara Vandamme; Renee Kelem; Steven Pint; Johanna J. Heymans; Colin R. Janssen; Jana Asselman (Ocean & Coastal Management, 2026)

Linking urban expansion to multi-contaminant pollution in karst aquifer cenotes - D. Alvarado-Zambrano; M.Y. Ayala-Campos; S.A. Reyes-Colin; S. Vasco-Viteri; R. Pérez-Ceballos; R. Rojo; J.S. Armstrong-Altrin; B.Y. Pérez-Alvarado; L. Abrell; D. Barrientes; M.G. Moulatlet; M.V. Capparelli (Environmental Research, 2026)

The Matador Bug and Several Related Leaf-footed Bugs (Hemiptera: Coreidae) Accumulate Cyanogens From their Host Plants - Colin R. Morrison; Brian E. Sedio; Lawrence E. Gilbert; Justin C. Havird; Ummat Somjee (Journal of Chemical Ecology, 2026)

Heterospecific social behavior in primates: insights into the evolutionary roots of pet-keeping - Cyril C. Grueter; Fany Roncin; K. Anne-Isola Nekaris; Jill Pruetz; Richard McFarland; Sabit Hasan; Malgorzata Arlet; Timothy M. Eppley; Susan M. Cheyne; Vincent Nijman; Eckhard W. Heymann; Pascal R. Marty; et al. (Primates, 2026)
Primate interspecific interactions with both other primates and non-primate species range from predator–prey dynamics to affiliative behaviors such as grooming, play, and carrying. While many primates participate in interspecific associations or commensal relationships, to our knowledge interspecific social interactions have never been systematically synthesized. Here, we present the first comprehensive review of such interactions, compiling 427 cases from the literature, media sources, and a global survey of primatologists. These involved 88 primate species and 127 non-primate species (including mammals, birds, reptiles, amphibians, malacostracans, and insects) across wild (n = 311) and captive (n = 111) contexts. The most frequent interactions occurred within or between primate families (e.g., Cercopithecidae–Cercopithecidae, Cebidae–Atelidae), though affiliative behaviors were also directed toward distantly related taxa such as dogs and birds. Play (n = 139) and grooming (n = 136) were most common. Juveniles and infants predominantly engaged in play, while adult females were more likely to groom. Adult males were less affiliative overall. Contrary to expectations, affiliative behaviors were not more often directed toward immature than adult heterospecifics. Primates were the initiators in most interactions. These findings offer new insights into the diversity and contexts of heterospecific sociality in primates and suggest that some behavioral tendencies relevant to later forms of human–animal companionship – such as caregiving, tolerance, and exploratory play – may be more widespread among primates than previously recognized.

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Insights from three decades of IUCN Red List assessments catalyzing shark, ray, and chimaera conservation - Brittany Finucci; Cassandra L. Rigby; Nicholas K. Dulvy; Rachel D. Cavanagh; Sarah Fowler; Lucy R. Harrison; Julia M. Lawson; Riley Pollom; Colin A. Simpfendorfer; Rachel H. L. Walls; Rima W. Jabado (Conservation Biology, 2026)
The International Union for Conservation of Nature (IUCN) Red List of Threatened Species is a critical measure of global aquatic and terrestrial biodiversity status. It is also the basis for the Red List Index, which tracks extinction risk over time. Sharks, rays, and chimaeras (Chondrichthyes) have now been comprehensively assessed twice (1996–2011 and 2012–2021) with hindcast assessments from 1970 onward, yielding an unprecedented extinction risk trajectory for an aquatic vertebrate class. The three‐decade success of the IUCN Species Survival Commission (SSC) Shark Specialist Group (SSG) in providing updated and evidence‐based assessments stems from sustained and coordinated activities by SSG members. We examined how a community of dedicated experts organized to fill gaps in key information to inform Red List assessments. From this evaluation, we identified six key lessons related to membership, taxonomic changes, implementation of the precautionary approach, information prioritization, assessment standardization, and policy efforts. However, existing challenges, including resource constraints and assessment discrepancies at different spatial scales, need to be addressed to ensure Red List assessments stay on pace with advances in conservation. With the second global assessment of chondrichthyans completed, it is appropriate to reflect on the evolution of the SSG and its achievements over three decades to highlight new tools and approaches to red listing and to identify priorities for the immediate future that are also applicable to other aquatic taxa with limited data, slow life histories, and exposure to high levels of fishing.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Detecting Antarctic flying seabird breeding occupancy with satellite remote sensing: opportunities and limitations - Heather J. Lynch; Mathew R. Schwaller; Louise Emmerson; Kate Blackwell; Colin Southwell (Polar Biology, 2026)

Novel Haemoproteus parasite lineage in Hooded Vultures (Necrosyrtes monachus) forms a distinct clade in Accipitriformes and highlights primer selection challenges in understudied avian hosts - Misa Shimizu; Oliver J. L. Fox; Jez Blackburn; Michael Colley; Colin Cross; Wendy James; John Jarju; Emmanuel Jatta; Naffie Sarr; Roger Walsh; Stephanie Key; Claudio Navarrete; et al. (Acta Parasitologica, 2026)

The Integration of Fire Ecology and Freshwater Ecosystems in North America: Knowledge Gaps and Research Needs - Morgan L. Piczak; Ava J. A. Sergio; Caliyena R. Brown; Waverley S. Birch; Rebecca L. Flitcroft; Meg A. Krawchuk; Colin P. R. McCarter; Jonathan W. Moore; Brendan P. Murphy; Brooke E. Penaluna; Prabha A. Rupasinghe; Victoria Steblaj; et al. (Global Change Biology, 2026)
Wildfires, unplanned fires that start and spread under the influence of weather and fuel composition, are increasing in frequency, duration, and severity across North America. While wildfires are one component of wildland fire, a broader natural process in many ecosystems, their changing behavior poses growing ecological and management challenges. Although wildfire is widely recognized as an important disturbance, empirical research quantifying its impacts on freshwater ecosystems remains limited and fragmented. As a result, our understanding of how wildfire affects imperiled freshwater systems remains underdeveloped. The objective of this review was to synthesize the existing empirical literature and identify key knowledge gaps to guide future research on wildfire–freshwater interactions across both biotic and abiotic components. At the biological scale, uncertainties remain around species‐ and community‐level responses (e.g., direct and indirect effects on biota). Freshwater habitat dimensions should also be the focus of further research, including alterations to physical structure (e.g., vegetation) and physicochemical conditions (e.g., temperature). From a management perspective, critical questions relate to fire‐informed restoration (e.g., specialized techniques, role of managed burns) and strategies for enhancing ecosystem resilience (e.g., identifying relevant indicators, links to watershed health). Understanding how land‐use change (e.g., forestry) and climate change interact to influence wildfire regimes and generate cumulative effects across landscapes is also essential in this new wildfire reality. To advance research and practice, we recommend comprehensive monitoring, standardization of methods and indicators, recognition of the role of cultural and prescribed burns, meaningful knowledge co‐production, and bridging the gap between scientific knowledge and management action.

Investigating wildfire smoke-related emergency department visits and syndromic surveillance in New Mexico 2019–2022 - Olivia Sablan; Bonne Ford; Colin B. Hawkinson; Leiqiu Hu; Jihoon Jung; Chelsea Eastman Langer; Courtney Maichak; Kamal Jyoti Maji; Stephanie Moraga-McHaley; Joseph O’Dell; Christopher K. Uejio; Melissa VanSickle; et al. (Air Quality, Atmosphere & Health, 2026)

Last Interglacial (MIS 5e) and Holocene sea surface temperature and environmental reconstructions from Yorke Peninsula, southern Australia - Tsun-You Pan; Allan R. Chivas; Colin V. Murray-Wallace; David J. Wheeler; Robert P. Bourman (Marine Geology, 2026)

Rationale and Study Protocol for the Academy of Nutrition and Dietetics’ Breastfeeding Registry Study - Allison C. Gaubert; Julie M. Long; Lindsay Woodcock; Casey R. Colin; Lauri Wright; Hanadi Hamadi; Constantina Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2026)

The risk of uncontrolled large-membrane reflectors in near-Earth orbit - Robert A.D. Gordon; Colin R. McInnes (Advances in Space Research, 2026)

Solar sail cooperative constellation control in displaced asteroid orbits - Zitong Lin; Matteo Ceriotti; Colin R. McInnes (Advances in Space Research, 2026)

Solar sail trajectory cost estimation with transfer learning - Edward Tomanek-Volynets; Matteo Ceriotti; Colin R. McInnes (Advances in Space Research, 2026)

Small jellyfish, large consequences: The overlooked predatory role of hydromedusae in subtropical estuarine ecosystems - Guilherme M. von Montfort; Kelly R. Sutherland; Sean Colin; John H. Costello; Renato M. Nagata (Limnology and Oceanography, 2026)
Hydromedusae are often overlooked in pelagic trophic ecology compared to large scyphozoans. We investigated the diet, prey selectivity, ingestion rates, digestion times, and predation impacts of the native Liriope tetraphylla and non‐indigenous species Cnidostoma fallax and Moerisia inkermanica in a subtropical estuary of the southwestern Atlantic. While all three species predominantly consumed copepods, L. tetraphylla exhibited the broadest diet and highest number of preys in gut content (up to 13). Digestion time for L. tetraphylla decreased significantly with increasing temperature, from 94 min at 18°C to 64 min at 28°C, with Q 10 values showing that digestion rates roughly double with a 10°C increase. Cnidostoma fallax exhibited longer digestion times (180 min at 23°C). Daily ingestion rations ranged from 16 to 212 copepods day −1 for L. tetraphylla , 7–15 for C. fallax , and up to 48 for M. inkermanica . Predation impact (PI), the proportion of a prey stock consumed by L. tetraphylla population, averaged 38.1% and peaked at 103.5%, while C. fallax and M. inkermanica had lower impacts (~ 5%). Carbon intake analyses revealed that L. tetraphylla consumed daily up to 280 times its own carbon weight, far exceeding the non‐indigenous species. These results highlight the critical role of hydromedusae in estuarine food webs, challenging the prevailing view that only large gelatinous predators exert top‐down control. We demonstrate that small hydrozoans can be key agents shaping prey community structure and carbon flow in subtropical estuarine ecosystems.

Assessing the integration of social marketing principles in ivory demand management interventions in China and Southeast Asia - Molly R. C. Brown; Victoria K. Wells; Colin M. Beale (Conservation Biology, 2026)
Consumer demand for ivory perpetuates the unsustainable and illegal killing of African elephants and other wildlife species. Interventions that aim to change consumer behavior are increasingly recognized as a crucial element of demand management. However, poor design and implementation have limited their effectiveness. We evaluated how ivory demand‐management interventions in China and neighboring Southeast Asian countries align with best practices from the behavioral field of social marketing. Through a literature review, we identified 55 interventions conducted from 2008 to 2022. We used 2 social marketing frameworks to assess each intervention's capacity to influence behavior. We conducted semistructured interviews with 5 intervention practitioners to provide contextual grounding for our review findings. From 2018 to 2022, social marketing principles were more frequently applied and interventions were of a higher quality ( n = 26) than interventions conducted from 2008 to 2017, reflecting a growing adoption of consumer‐insight‐driven strategies. Since 2018, 7 interventions applied no social marketing principles, and 9 interventions, to varying degrees, included monitoring and evaluation. Although 13 interventions contained some theoretical considerations, these were often vague and superficial. Despite identifying a shift from experiential practices to evidence‐based approaches over time, the shift was largely restricted to communications‐based social and behavior change approaches. This left the wide range of social marketing approaches underused. Ivory demand management must improve the breadth and depth of social marketing used to contribute to long‐term elephant conservation. We suggest all consumer approaches tackling demand for wildlife meaningfully consider integrating behavioral theories in intervention design, undertake primary or secondary research to enable evidence‐led decision‐making, conduct systematic monitoring for evidence‐based learning and adaptation, and use impact and process evaluation methods to understand the mechanisms and magnitude of behavioral change following interventions.

Deep Convective Activity in Tropical Cyclones and its Impact on Cirrus Clouds: Using Lightning as a Proxy - Joydeb Saha; Ashish Routray; Colin Price; Kieran M. R. Hunt; K. B. R. R. Hari Prasad; Anirban Guha (Pure and Applied Geophysics, 2026)

Comparative assessment of nutrient cycling and larval whiteleg shrimp () performance in batch and recirculating hatchery systems - Ilias Semmouri; Flor Nachtergale; Vincent Vermeylen; Jana Asselman; Annelies M. Declercq; Colin R. Janssen (Aquacultural Engineering, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Does fishery management for groupers (Teleostei: Epinephelidae) protect them effectively? Context from the IUCN's Red list of threatened species - Sean T. Fennessy; Christi Linardich; Kevin Rhodes; Joao P. Barreiros; David Pollard; Eloy Sosa-Cordero; Felicia Coleman; Alfonso Aguilar-Perera; Christopher R. Malinowski; Thierry Brulé; Pedro Afonso; Kayan Ma; et al. (Ocean & Coastal Management, 2026)

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Simulation of polycyclic aromatic compounds in the Athabasca River Basin: integrated models and insights - Qianyang Wang; Maricor J. Arlos; Jinqiang Wang; Mark McMaster; Erin Ussery; Colin A. Cooke; Brandon R. Hill; Nancy Glozier; Keegan A. Hicks (Water Research, 2026)

Influence of global climate modes on wildfire occurrence in the contiguous United States under recent and future climates - Theodore R. Keeping; Theodore G. Shepherd; I. Colin Prentice; Karin van der Wiel; Sandy P. Harrison (Climate Dynamics, 2026)
Predictable modes of climate variability, such as the El Niño Southern Oscillation (ENSO), have a major influence on regional weather patterns, an important control on wildfire occurrence. Although these global climate modes have been associated with historical variability in wildfire occurrence in the United States and are used to forecast seasonal wildfire risk, precise information about the spatial pattern and magnitude of their influence is lacking and the satellite record of wildfires is too short to address these issues. Here we use wildfire occurrence model with a large ensemble of 1600 simulated years from EC-Earth3 in a recent climate (2000–2009) and a future climate corresponding to + 2 °C global warming, to characterise the impact of specific climate modes on wildfire occurrence in the contiguous US. We show that ENSO, the Indian Ocean Dipole (IOD), and the 1-year lagged Tropical North Atlantic (TNA+1) have the greatest effect on annual fire occurrence—strongly contributed by the effect of these modes on hot, dry conditions in the Great Plains and precipitation in the southwestern US. El Niño is not significantly associated with wildfire occurrence in the northwestern US, contrary to expectation, but is associated with a later (earlier) wildfire season peak in the southwestern (southeastern) US. Under future warming, the AMO and PNA become a significant influence over most of the US, and the magnitude of impact of ENSO and TNA+1 increase strongly.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Recycling of ash particles during highly explosive eruptions: multiple glass populations in the 1.8 ka Taupō tephra - Simon J. Barker; Stephen B. Piva; Colin J. N. Wilson; David J. Lowe; Bruce L. A. Charlier; Alan R. Orpin (Bulletin of Volcanology, 2025)

Combined exposure of poly(lactic-co-glycolic acid) microplastics and global warming affects the population dynamics of a coastal copepod - Zhiyue Niu; Jana Asselman; Colin R. Janssen; Charlotte P. Linley; Karel De Schamphelaere; Gert Everaert; Ana I. Catarino (Marine Pollution Bulletin, 2025)

Regional pressure response to large-scale carbon storage in the bunter sandstone formation, Silverpit Basin (Southern North Sea, UK) - Mattia De Luca; Eric J. Mackay; Timothy R. Good; Vittorio Scisciani; Colin MacBeth; Stefano Patruno; Joseph Sutcliffe (International Journal of Greenhouse Gas Control, 2025)

The Effect of High Temperatures on the Growth and Biochemical Composition of Cultivated Palmaria Palmata (Rhodophyta) - Ilias Semmouri; Sophie Vanhercke; Andreia S. Ferreira; Jessica Knoop; Olivier De Clerck; Cláudia Nunes; Manuel A. Coimbra; Leonardo M. de Souza Mesquita; Sónia P. M. Ventura; Colin R. Janssen; Jana Asselman (Marine Biotechnology, 2025)

The effect of light, aeration and temperature on the growth and phenolic content of cultivated Ecklonia cava gametophytes (Phaeophyceae) and their antioxidant properties - Ilias Semmouri; Hojun Lee; Samira Alahyaribeik; Juan Miguel Baldominos Botas; Phara Claeys; Taejun Han; Colin R. Janssen; Mahta Mirzaei; Jana Asselman; Jihae Park (Journal of Applied Phycology, 2025)

Symbiodiniaceae shifts over the last decade on the hottest coral reefs on Earth - Anna Fiesinger; Rachel Alderdice; Luigi Colin; Hannah Manns; Gabriela Perna; Kathryn H. Stankiewicz; Jacob J. Valenzuela; Line K. Bay; Daniel J. Barshis; Nitin S. Baliga; Iliana B. Baums; John A. Burt; et al. (Coral Reefs, 2025)
Corals in the Persian/Arabian Gulf (PAG) are resilient to various stressors, whose levels exceed those of coral reefs globally. These corals thereby offer insight into mechanisms underlying thermal resilience, e.g., regarding the role of endosymbiotic microalgae in the family Symbiodiniaceae. Previous studies have identified the thermotolerant species Cladocopium thermophilum as broadly associated with corals in the southern PAG. However, algal-host specificity at the within-species level and the temporal stability of these associations are not well understood. Here we sampled two dominant stony corals ( Porites harrisoni , n = 119 and Platygyra daedalea , n = 79) at three sites in the southern PAG and the neighboring Gulf of Oman (GO) to explore algal symbiont assemblage and specificity, whereby a prior dataset provided the opportunity to assess symbiont community stability in P. daedalea across a decadal time frame. Using high-throughput ITS2 marker gene sequencing and the SymPortal framework, we identified distinct, largely non-overlapping ITS2 type profiles of C. thermophilum as the dominant symbiotic partners in P. harrisoni and P. daedalea in the southern PAG, highlighting high host fidelity at the subspecies level. Despite this, we observed notable changes in C. thermophilum genotype diversity and an overall decrease over the course of a decade. By comparison, algal symbiont diversity in the neighboring GO corals increased, with formerly prevalent ITS2 type profiles being replaced by novel genotypes. Decadal data on P. daedalea suggest a shift in algal symbiont assemblage signified by the decline of formerly dominant algal type profiles and the emergence of novel genotypes. It is currently unknown whether the respective coral colonies associated with novel algae or became rare or extinct themselves. Understanding long-term algal population dynamics is critical to forecast how algal lineage loss or, alternatively, an increase in algal diversity will impact coral resilience and survival.

Spatial atlasing of N-glycosylation in healthy control and clear cell renal cell carcinoma tissues linked with immune checkpoint inhibition response by MALDI mass spectrometry imaging - Caroline Kittrell; Lyndsay E.A. Young; Colin McDowell; Grace Grimsley; Anand S. Mehta; Peggi M. Angel; Jessica Schmitz; Nikolaos Vasileiadis; Christopher Darr; Viktor Grünwald; Philipp Ivanyi; Jan Hinrich Bräsen; et al. (Analytica Chimica Acta, 2025)

Floridoside originating from red algae (Rhodophyta): Review on the occurrence, extraction and potential applications for human health and aquaculture - Ilias Semmouri; Robbe Paepen; Colin R. Janssen; Jana Asselman (Algal Research, 2025)

Environmental Microbial Cues Alter Embryonic Development and Stress Responses in Vertebrates: Insights From the Zebrafish ( Danio rerio ) Model - Emily M. Green; Akila Harishchandra; Colin R. Lickwar; Yeon Ji Kim; John F. Rawls; Richard T. Di Giulio; Nishad Jayasundara (Molecular Ecology, 2025)
Host‐microbiome interactions shape key physiological processes, including bioenergetics, neurodevelopment and xenobiotic metabolism, and strongly influence the ecological fitness of the host. However, our understanding of host‐microbiome interactions is primarily derived from post‐embryonic free‐living life stages, when the organism is in direct contact with microbes. Whether environmental microbial communities influence embryogenesis—particularly in oviparous organisms where embryos are encased in a protective chorion—remains unknown. Using zebrafish ( Danio rerio ) embryos reared germ‐free or conventionalized with a defined microbial community at 6 and 24 h post‐fertilisation, we demonstrate that environmental microbiota influence embryonic development prior to hatching, altering transcriptomic, proteomic and metabolomic pathways linked to energy metabolism, neurodevelopment and xenobiotic responses, including cytochrome P4501A ( cyp1a ) activation. Furthermore, embryos exposed to benzo(a)pyrene, a CYP1A‐activator, exhibited microbiome‐dependent changes in embryonic mitochondrial function and larval behaviour, revealing persistent developmental effects. These findings challenge the long‐held assumption that embryonic development is insulated from microbial influence. Instead, our results reveal that host–microbe interactions begin earlier than previously recognised, with implications for developmental plasticity, xenobiotic stress responses and environmental sensitivity likely affecting the ecological fitness of the host. Our results advance understanding of molecular adaptation to microbial environments and provide a foundation for investigating how microbiota shape the developmental origins of host resilience and vulnerability in microbially‐dynamic natural habitats.

Comments on a recently proposed alternative definition for postbiotics - Gabriel Vinderola; Seppo Salminen; Maria Carmen Collado; Akihito Endo; Colin Hill; Sarah Lebeer; Daniel Merenstein; Eamonn M.M. Quigley; Raanan Shamir; Jonathan R. Swann; Hania Szajewska; Daniel J. Tancredi; et al. (Trends in Food Science & Technology, 2025)

Earlier onset of phytoplankton bloom in the Southern Bight of the North Sea in response to climate variability - Zixia Liu; Ilias Semmouri; Yunmeng Li; Maarten De Rijcke; Emmanuel Van Acker; Colin R. Janssen; Jana Asselman (Marine Environmental Research, 2025)

Widespread pseudo-perennial water ice patches at high northern latitudes on Mars - Colin M. Dundas; Michael T. Mellon; Aditya R. Khuller; Vidhya Ganesh Rangarajan (Icarus, 2025)

Role of viral coinfection in post-pandemic invasive Group A streptococcal infections in adults, a nation-wide cohort study (iGASWISS) - S. Musumeci; A. MacPhail; M. Weisser Rohacek; A. Erba; D. Goldenberger; C. Lang; E. Colin-Benoit; S. L. Leib; P. Sendi; C. Chuard; V. Erard; C. Fournier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Objective During the winter season of 2022–2023, numerous countries experienced a surge in invasive Streptococcus pyogenes (iGAS) infections. The role of viral coinfections in the post-COVID surge has not been elucidated. We report nation-wide data describing clinical presentation, microbiological characteristics, and associations with viral infection in adults during this period. Methods A multicenter retrospective cohort study was conducted across 10 hospitals in Switzerland, including adults (> 16 years old) with iGAS infection from November 2022 to February 2023. Descriptive analysis was performed. A multivariable logistic regression model was fitted to assess the impact of viral coinfection. In addition, genetic analysis was performed in available isolates. Results A total of 194 patients were included, with a median age of 50 years (interquartile range [IQR]: 37–69). 17/194 (8.8%) were immunosuppressed and 40/194 (20.6%) exhibited concomitant viral infections, predominantly Influenza A (21/40, 53%). Illness severity was high: 65/194 (33.5%) of cases necessitated admission to an intensive care unit (ICU), and the 30-day mortality was 4% ( n = 8). Among the available strains for genetic analysis ( n = 48), heterogeneity was found although ST28- emm 1 isolates (also known as M1UK) was predominant (22/48). Conclusion The post-COVID iGAS surge in Switzerland was associated with high levels of morbidity and mortality in immunocompetent adults. M1UK was predominant within the iGAS strains circulating in Switzerland during the study period and viral coinfection was a predictor for ICU admission and mortality.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

The Need for and Challenges of Nutrition and Dietetics Registry Studies Part II: A Primer for the Design and Implementation of Registry Studies in the Academy of Nutrition and Dietetics Health Informatics Infrastructure - Lindsay Woodcock; Casey R. Colin; Erin Lamers-Johnson; Constantina Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2025)

Inverse vulcanized sulfur polymers: A greener and cost-effective alternative to conventional polymers - A cradle-to-gate life cycle analysis - Vinicius Diniz; Abdirahman Mohamud; Fardin Teen Rahman; Hibah Tariq Rana; Nimota Anjolaade Ogunwoolu; Colin R. Crick (Journal of Cleaner Production, 2025)

Assessing Plastic Pollution in Kenyan Mangroves: Distribution, Sources, and Social Impact in Gazi Bay - Elissa P. B. Pelsmaekers; Colin R. Janssen; Stefano Cannicci; Cosmas Nzaka Munga; Farid Dahdouh-Guebas (Estuaries and Coasts, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

The effect of bromoform supplementation in Angus cows during late gestation on offspring’s growth performance and maternal greenhouse gas emissions using two devices - Matilda G. Dent; Alice H. Brownrigg; Bruno R. Costa Alves; Kellie M. Wenham; Stephen J. Lee; Wayne S. Pitchford; Nigel W. Tomkins; Colin L. Trengove; Mariana Caetano (Livestock Science, 2025)

Transcriptome Profiling of Trabecular Meshwork Progenitor Cells - Xiaochen Fan; Stephanie Kennedy; Emine K Bilir; Brian Lane; Olivia A Kingston; Xu Chen; Victoria R Kearns; Colin E Willoughby; Carl M Sheridan (Stem Cell Reviews and Reports, 2025)
The loss and dysfunction of trabecular meshwork (TM) cells are implicated in aging and primary open-angle glaucoma. TM progenitor cells (TMPCs) contribute to the population and function of the TM, but their identity is not well elucidated. This study aimed to identify the expression profile of differentially expressed genes (DEGs) in human TM cell cultures, TM-derived spheres, and their differentiated progeny. Primary normal human TM cells (PTM) from three donors were cultured, de-differentiated into spheres, and re-differentiated into TM cells (DTM). RNA-Seq was performed using Illumina NGS, and bioinformatics analysis was conducted with Tuxedo, Bowtie2, Tophat, Cufflinks, and Ingenuity Pathway Analysis (IPA). DEGs were validated via Nanostring, RT-qPCR (in five independent donors), immunocytochemistry, and western blotting. RNA-seq identified significant DEGs in PTM, TM progenitor cells (TMPCs), and DTM cells. Gene expression in TMPCs differed significantly from PTM and DTM cells. Nanostring and RT-qPCR confirmed 70 DEGs upregulated in TMPCs ( P < 0.05). Immunocytochemistry highlighted distinct markers in TMPCs (SOX2, NOTCH1, ANKG, MGP) versus PTM and DTM cells (TAGLN, TEM7, SPARC). Western blotting further analyzed MGP, TAGLN, and SPARC proteins, revealing significant upregulation of MGP in TMPCs and downregulation of TAGLN and SPARC in spheres compared to PTM cells. Pathway analysis revealed activation of cell cycle checkpoint regulation, SUMOylation, and STAT3 pathways in TMPCs, with HGF, MMP9, KDR, IGF1, and FOS as key node genes in TMPC development. RNA-Seq identified novel expression profile of potential TM markers and activated pathways in TMPCs, providing insights into TMPC behaviours in physiological and pathological conditions. Graphical Abstract

Contribution of combined stressors on density and gene expression dynamics of the copepod Temora longicornis in the North Sea - Ilias Semmouri; Karel A. C. De Schamphelaere; Filip Van Nieuwerburgh; Dieter Deforce; Colin R. Janssen; Jana Asselman (Molecular Ecology, 2025)
The impact of multiple environmental and anthropogenic stressors on the marine environment remains poorly understood. Therefore, we studied the contribution of environmental variables to the densities and gene expression of the dominant zooplankton species in the Belgian part of the North Sea, the calanoid copepod Temora longicornis . We observed a reduced density of copepods, which were also smaller in size, in samples taken from nearshore locations when compared to those obtained from offshore stations. To assess the factors influencing the population dynamics of this species, we applied generalised additive models. These models allowed us to quantify the relative contribution of temperature, nutrient levels, salinity, turbidity, concentrations of photosynthetic pigments, as well as chemical pollutants such as polychlorinated biphenyls and polycyclic aromatic hydrocarbons (PAHs), on copepod density. Temperature and Secchi depth, a proxy for turbidity, were the most important environmental variables predicting the densities of T. longicornis , followed by summed PAH and chlorophyll concentrations. Analysing gene expression in field‐collected adults, we observed significant variation in metabolic and stress‐response genes. Temperature correlated significantly with genes involved in proteolytic activities, and encoding heat shock proteins. Yet, concentrations of anthropogenic chemicals did not induce significant differences in the gene expression of genes involved in the copepod's fatty acid metabolism or well‐known stress‐related genes, such as glutathione transferases or cytochrome P450. Our study highlights the potential of gene expression biomonitoring and underscores the significance of a changing environment in future studies.

Exposure and health risks of benzene from combustion by gas stoves: A modelling approach in U.S. homes - Anchal Garg; Yannai Kashtan; Metta Nicholson; Colin J. Finnegan; Eric D. Lebel; Drew R. Michanowicz; Seth B.C. Shonkoff; Kari C. Nadeau; Robert B. Jackson (Journal of Hazardous Materials, 2025)

Real-Time detection of sewer water levels and blockages using UHF-RFID sensors - Sundra R. Tatiparthi; Yashika G. De Costa; David Wyllie; Ray Y. Zhong; Shihu Hu; Zhiguo Yuan; Colin N. Whittaker; Wei-Qin Zhuang (Water Research, 2025)

Quantitative approach for assessing risks and benefits to the supply of ecosystem services in response to human activities - Dries Lorré; Sara Vandamme; Ulrike Braeckman; Colin R. Janssen; Jana Asselman (Science of The Total Environment, 2025)

Temperature and salinity affect growth and toxin content of cyanobacterium Microcystis aeruginosa (PCC 7806) in estuarine environments - Wenxin Liu; Ilias Semmouri; Suzanne Bulckaert; Colin R. Janssen; Jana Asselman (Harmful Algae, 2025)

10Be reproducibility in the Santa Monica Mountains, California, USA: A longitudinal study in a scorched and soaked landscape - Eric W. Portenga; Kirk F. Townsend; Lee B. Corbett; Paul R. Bierman; Marc W. Caffee; Collin Bogoski; Colin O'Neill; Samantha Skora (Geomorphology, 2025)

Cellular and tissue-level responses of mussels (Mytilus edulis) to aged polyethylene terephthalate (PET) micro- and nanoplastic particles - Jenevieve Hara; Gethrie B. Oraño; Maaike Vercauteren; Kayawe Valentine Mubiana; Colin R. Janssen; Ronny Blust; Jana Asselman; Raewyn M. Town (Aquatic Toxicology, 2025)

Climate change threatens the sustainability of current timber harvesting practices across a latitudinal gradient in Siberia - Eric J. Gustafson; Melissa S. Lucash; Anatoly Z. Shvidenko; Brian R. Sturtevant; Dmitry Schepaschenko; Colin Mast; Neil Williams (European Journal of Forest Research, 2025)

Urban imperviousness and carotid intima-medial thickness: Evidence from the Coronary Artery Risk Development in Young Adults (CARDIA) study - Dandan Zhao; Jie Yao; Yuanfei Li; David R. Jacobs; Tao Gao; Linda H. Nie; Colin O. Wu; Umit Tokac; Shuang Li; Hui Zhao; Donald Lloyd-Jones; Lifang Hou; et al. (Science of The Total Environment, 2025)

Integration of genetic, taxonomic, and functional dimensions of biodiversity yields conservation insights - Carla L. Atkinson; Irene Sánchez González; Jamie R. Bucholz; Garrett W. Hopper; Ryan C. Garrick; Colin R. Jackson; Jeffrey D. Lozier (Biological Conservation, 2025)

Determinants of riverine migration success by Atlantic salmon ( Salmo salar ) smolts from rivers across the UK and Ireland - Jessica R. Rodger; Jemma Guthrie; Hannele M. Honkanen; Angus J. Lothian; Jessie Lilly; Marcus Walters; Richie Miller; Lorraine Hawkins; Al Reeve; Jamie Ribbens; Jim Henderson; Debbie Parke; et al. (Journal of Fish Biology, 2025)
There is some evidence that the river migration success of Atlantic salmon smolts, on their first migration to sea, varies both spatially and temporally. However, we have only a poor understanding of what may be driving this variation. In this study, we used acoustic telemetry to quantify the spatial and temporal variations in river migration success in Atlantic salmon smolts on their first migration to sea. In total 4120 Atlantic salmon smolts migrating through 22 rivers in Scotland, England, Ireland, and Northern Ireland over multiple years were included in the study. Individuals were defined as successful migrants if detected leaving the river to enter marine waters. The results show significant temporal (up to 4 years) and spatial (river) variations in migration success, with overall between‐river migration success varying from 3.4% to 97.0% and between years from 3.4% and 61.0%. Temporal variation in migration success was river specific, with some rivers being more temporally stable (exhibiting little variation between years) than others. Across all rivers and years, individual migration success was predicted positively by body condition and negatively by tag burden. The rate of migration success for a population (migration success standardized to a common river distance [proportion km −1 ]) was predicted by a number of environmental factors. The proportion of river catchment that comprised wetland and woodland positively predicted migration success, whereas the proportion of grassland and peatland in a catchment negatively predicted the rate of migration success. Although the mechanisms through which these effects may be operating were not directly examined in this study, we discuss some potential routes through which they may occur.

Performance and detection range of acoustic receivers in mangrove habitats - Shiori Kanno; Michelle R. Heupel; Kristin Hoel; Audrey Schlaff; Aliya Siddiqi; Colin A. Simpfendorfer (Journal of Fish Biology, 2025)
Acoustic telemetry has been used to monitor the movement of aquatic animals in a broad range of aquatic environments. Despite their importance, mangrove habitats are understudied for the spatial ecology of elasmobranchs, with acoustic telemetry rarely used inside mangrove habitats. One reason for this may be a general assumption that acoustic signals would not be able to be detected by receivers in such shallow, structurally complex, environments. This study tested whether acoustic receivers can be used inside mangrove habitats to track the movement of sharks and rays. Thirty‐eight receivers were deployed in a mangrove system in Pioneer Bay, Orpheus Island, Great Barrier Reef, including inside mangroves, mangrove edges, and adjacent reef flat areas. The detection range and receiver performance metrics, such as code detection efficiency, rejection coefficient, and noise quotient, were examined and tested among habitats. The results highlighted that the signal from transmitters was successfully detected inside mangrove habitats as well as on the adjacent reef flat. The range to detect at least 50% of transmissions was up to 20 m inside mangroves and up to 120 m outside mangroves. The performance metrics of acoustic receivers inside the mangrove habitat were characterized by low background noise, low rejection rates, and reasonably high code detection efficiency. Furthermore, this study tested the application of this method on juvenile blacktip reef shark Carcharhinus melanopterus and mangrove whipray Urogymnus granulatus , and demonstrated that it can be used to successfully track animals inside mangrove habitat. This novel method could reveal further information on how sharks and rays use mangrove habitats.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Nuance in the Narrative of a Brown Poison Frog: Environmental Alkaloids and Specialized Foraging in a Presumed Toxin-Free and Diet-Generalized Species - Jeffrey L. Coleman; Steven Y. Wang; Paul E. Marek; Colin R. Morrison; Brian E. Sedio; David C. Cannatella (Journal of Chemical Ecology, 2025)

Can trees and their associated organisms still benefit arable crops in the presence of pesticide use? - Colin R. Tosh; Jo Smith (Agricultural Systems, 2025)

A circumpolar review of the breeding distribution and habitat use of the snow petrel (Pagodroma nivea), the world’s most southerly breeding vertebrate - Josie Francis; Ewan Wakefield; Stewart S. R. Jamieson; Richard A. Phillips; Dominic A. Hodgson; Colin Southwell; Louise Emmerson; Peter Fretwell; Michael J. Bentley; Erin L. McClymont (Polar Biology, 2025)
Knowledge of the spatial distribution of many polar seabird species is incomplete due to the remoteness of their breeding locations. Here, we compiled a new database of published and unpublished records of all known snow petrel Pagodroma nivea breeding sites. We quantified local environmental conditions at sites by appending indices of climate and substrate, and regional-scale conditions by appending 30 year mean (1992–2021) sea-ice conditions within accessible foraging areas. Breeding snow petrels are reported at 456 sites across Antarctica and subantarctic islands. Although many counts are old or have large margins of error, population estimates available for 222 known sites totalled a minimum of ~ 77400 breeding pairs. However with so many missing data, the true breeding population will be much higher. Most sites are close to the coast (median = 1.15 km) and research stations (median = 26 km). Median distance to the November sea-ice edge (breeding season sea-ice maximum) is 430 km. Locally, most nests occur in cavities in high-grade metamorphic rocks. Minimum air temperatures occur at inland sites, and maxima at their northern breeding limit. Breeding location and cavity selection is likely determined by availability of suitable breeding substrate within sustainable distance of suitable foraging habitat. Within this range, nest sites may then be selected based on local conditions such as cavity size and aspect. Our database will allow formal analyses of habitat selection and provides a baseline against which to monitor future snow petrel distribution changes in response to climate change.

Cytochromes P460 and c′-β: exploiting a novel fold for multiple functions - Hannah R. Adams; Sotaro Fujii; Hans E. Pfalzgraf; Peter Smyth; Colin R. Andrew; Michael A. Hough (JBIC Journal of Biological Inorganic Chemistry, 2025)
Two related classes of ligand-binding heme c -containing proteins with a high degree of structural homology have been identified and characterized over recent decades: cytochromes P460 (cyts P460), defined by an unusual heme-lysine cross-link, and cytochromes c ′-β (cyts c ′-β), containing a canonical c -heme without the lysine cross-link. The shared protein fold of the cyt P460-cyt c ′-β superfamily can accommodate a variety of heme environments with entirely different reactivities. On the one hand, cyts P460 with polar distal pockets have been shown to oxidize NH 2 OH to NO and/or N 2 O via proton-coupled electron transfer. On the other hand, cyts c ′-β with hydrophobic distal pockets have a proposed gas binding function similar to the unrelated, but more extensively characterized, alpha helical cytochromes c ′. Recent studies have also identified ‘halfway house’ proteins (cyts P460 with non-polar heme pockets and cyts c ′-β with polar distal heme pockets) with functions yet to be resolved. Here, we review the structural, spectroscopic and enzymatic properties of the cyt P460-cyt c ′-β superfamily with a view to understanding the structural determinants of their different functional properties. Graphical abstract

Improving potential strategies for biological activities of phlorotannins derived from seaweeds - Xinyu Duan; Osman Tuncay Agar; Colin J. Barrow; Frank R. Dunshea; Hafiz A. R. Suleria (Critical Reviews in Food Science and Nutrition, 2025)

Quaternary rivers, tufas and mires of southern England: Description of Geological Conservation Review sites - Rebecca M. Briant; Colin A. Whiteman; B. Andrew Haggart; David R. Bridgland; Ella Egberts; Michael J. Grant; Marcus Hatch; Peter G. Knowles; Danielle C. Schreve; Philip S. Toms; Francis F. Wenban-Smith; Mark J. White (Proceedings of the Geologists' Association, 2025)

A Comprehensive Survey of 2024 Funding for Radiation Oncology Visiting Medical Student Electives - Drew T. Bergman; Colin J. McNamara; Alexys C. Gayne; Charles R. Jr. Thomas; Nirav S. Kapadia (Journal of Cancer Education, 2025)

Complex landscape, instream and anthropogenic environmental features drive genetic and morphological structuring amongst brown trout (Salmo trutta) populations in a dendritic river system - Jessica R. Rodger; Hannele M. Honkanen; Caroline R. Bradley; Patrick Boylan; Paulo A. Prodöhl; Colin E. Adams (Evolutionary Ecology, 2025)
Untangling the patterns and proximate drivers of intraspecific genetic and phenotypic structuring informs our understanding of the evolutionary processes shaping diversity. This study investigated morphological and genetic structuring of brown trout ( Salmo trutta L.) populations across varying spatial scales in a single, complex, dendritic river catchment and examined the potential natural and anthropogenic environmental features driving this structuring. Morphometric and hierarchical genetic structuring analyses of fish from 22 sampling sites in the River Foyle catchment, Ireland (~ 4500km 2 ) identified 19 morphologically distinct groups and 15 genetically distinct populations, separated by river distances ranging from 0.4 km to 188 km. Isolation by Distance was the main factor shaping both genetic and morphological divergence, indicating that strong philopatry is one of the major drivers of the observed population structuring in this system. However, both natural and anthropogenic environmental variables also explained pairwise genetic and morphological differences between sampling sites. Thus, the pairwise differences in the area of woodland in the upstream catchment, water phosphorus concentration, biological oxygen demand, catchment slope, urban area in upstream catchment, altitude, site specific percentage of canopy cover and dissolved oxygen concentration in the river channel were correlated with genetic divergence. The pairwise differences in the concentration of suspended solids, the extent of bankside overhang, the composition of bedrock, boulder and cobble substrates, watercourse width, catchment slope and site altitude were correlated with between-site morphological differences. We hypothesise that local differential selection pressures comprising both natural environmental variation and variation resulting from anthropogenic effects, in combination with strong philopatry and random genetic processes drive the clearly defined genetic and phenotypic patterns described here.

Muscle microvascular oxygen delivery limitations during the contraction phase of intermittent maximal effort contractions - Kylie N. Sears; Tony R. Montgomery; Colin W. Kipper; Petra Kis; Taylor K. Dinyer-McNeely; Shane M. Hammer (European Journal of Applied Physiology, 2025)

The effect of downstream translocation on Atlantic salmon Salmo salar smolt outmigration success - Ruaidhri Forrester; Hannele M. Honkanen; Jessie Lilly; Amy Green; Jessica R. Rodger; Brian A. Shields; Philip Ramsden; J. Peter Koene; Melanie Fletcher; Colin W. Bean; Colin E. Adams (Journal of Fish Biology, 2025)
Trap and transport, the capture and subsequent translocation of fish during the freshwater phase of their migration, is becoming more common as a management intervention. Although the technique can be successful, it is costly and can have unintended effects on the fish being transported. This study investigates whether trap and transport can be used to increase the migration success of Atlantic salmon, Salmo salar , smolts in naturally flowing rivers. Seaward‐migrating S. salar ( n = 294) from two UK rivers were tracked using acoustic telemetric techniques. Outmigration success and timing were compared between non‐transported (released at the original in‐river capture site) and transported (released ca. 23 km downstream of the capture site) individuals. Downstream translocation increased the proportion of fish that successfully migrated to marine waters, and there was no indication that transport reduced post‐release survival. The post‐release migration speed of transported fish was slower than expected but this was likely a function of their advanced migration timing rather than an inhibition of their capacity to migrate. These results suggest that trap and transport can increase the outmigration success of S. salar smolts, but the earlier river exit dates of transported fish could negatively affect their survival at sea.

Lake shape and the characteristics of migration behavior modify Atlantic salmon smolt migration success through lakes - Matthew Newton; Joseph McCallum; Hannele M. Honkanen; Alastair Stephen; Jessie M. Lilly; Danielle L. Orrell; Amy Green; Louise Chavarie; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2025)
Migration is a high‐risk behavior. For the Atlantic salmon, Salmo salar , migrating from its river nursery area to marine feeding grounds, the magnitude of risk varies with habitat type. Passage through lakes, in particular, is associated with low rates of migration success. Downstream migrating salmon smolts are rheotactic when migrating in rivers, but lakes typically provide poorer directional currents for migrating salmon. In this study we tested if, in the absence of clear navigational cues in lakes, Atlantic salmon smolts switch to a random search strategy to find the outflowing river. We constructed random search simulations to test if lake basin shape has an effect on migration success. We also compared simulated migration characteristics with migrations of salmon smolts through five real lakes for which there are telemetry data for migrating salmon. Correlated random walk simulations showed that a random search strategy could be successful for all lake shapes tested but was more successful in curved (round and elliptical) than rectangular basin shapes. Rectangular basins with the migration start and stop points at the ends of the lake had a higher success than those where these points were perpendicular to the axis of the lake. In general, a random walk model predicted the migration success rate of fish tracked through real lakes. However, for two lakes the simulated migration success exceeded that of actual success, suggesting that fish passing through these lakes were not adopting a random search strategy. We speculate that this is the result of either conflicting navigational cues which inhibit smolts from finding the lake outlet or that they temporarily suspend migration (e.g., to feed). Modelling predicted that for small lakes, directional swimming in short steps (ca. 100 m) followed by turns with very low variation from the direction of travel resulted in the highest migration success. For larger lakes, longer step lengths but also with low turn variation (simulated turning angle drawn from distributions of standard deviation 2 ° and 5 ° around a mean of 0 ° ) resulted in the highest migration success. We conclude that navigation in downstream migrating salmon smolts switches from rheotaxis in rivers to a random search tactic in lakes except where residual flow cues in some lakes prevent this, at times resulting in suboptimal navigation outcomes.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Faecal contamination determines bacterial assemblages over natural environmental parameters within intermittently opened and closed lagoons (ICOLLs) during high rainfall - Nathan L.R. Williams; Nachshon Siboni; Jaimie Potts; Peter Scanes; Colin Johnson; Melanie James; Vanessa McCann; Nine Le Reun; William L King; Justin R. Seymour (Water Research, 2025)

Health risks associated with the consumption of sea turtles: A review of chelonitoxism incidents and the presumed responsible phycotoxins - Ilias Semmouri; Colin R. Janssen; Jana Asselman (Science of The Total Environment, 2024)

Characterizing Juvenile Common Snook and Tarpon Habitat to Guide Conservation and Restoration of Coastal Wetlands - Philip W. Stevens; David A. Blewett; Corey R. Anderson; Courtney R. Saari; Colin P. Shea; Casey A. Craig; Kara R. Radabaugh (Wetlands, 2024)
To conserve or restore juvenile fish habitat, resource managers, restoration practitioners, and engineers need fine-scale information to understand what conditions they need to preserve or what specifications are needed to create new habitat. The objective of this study was to develop statistical models using a dataset of 18 coastal ponds in Southwest Florida, USA, to predict the abundance of juvenile common snook Centropomus undecimalis (hereafter snook) and presence of juvenile tarpon Megalops atlanticus , both of which are flagship species used for conservation and restoration of subtropical and tropical wetlands. Model predictors included water conditions and characteristics of vegetation, sediment, and geographic position. Modeling results indicated that juvenile snook used coastal ponds that were directly connected to tidal creeks. In contrast, juvenile tarpon were more likely to be present in coastal ponds that were separated from tidal creeks by dense mangrove forest (e.g., elevation > 0.48 m above Mean Low Water) characterized by highly organic sediment and low dissolved oxygen, to which tarpon are well adapted. Overlap between snook abundance and tarpon presence was greatest where connections between ponds and the nearest tidal creek were at a relatively low elevation (e.g., -0.12 m relative to Mean Low Water). Although these findings are most applicable to management and conservation of populations in areas along the Gulf coast of Florida (i.e., in areas of similar tidal range and coastal geomorphology), incorporating more detailed habitat surveys to better capture landscape context, geomorphology, and connectivity into fish sampling designs should be broadly applicable to estuarine fish ecology.

Emigration of Juvenile Tarpon Megalops atlanticus from Ephemerally Connected Coastal Ponds - Matthew S. Bunting; Philip W. Stevens; David A. Blewett; Quenton M. Tuckett; Jeffrey E. Hill; Gregg R. Poulakis; Colin P. Shea; Courtney R. Saari (Estuaries and Coasts, 2024)
Worldwide, coastal wetlands are threatened by disrupted hydrology, urbanization, and sea-level rise. In southwest Florida, coastal wetlands include tidal creeks and coastal ponds, which are the primary habitats used by juvenile Tarpon, Megalops atlanticus , an important sport fish. Coastal ponds can occur near uplands and are ephemerally connected to the open estuary, creating conditions of variable dissolved oxygen and salinity. Juveniles can tolerate wide-ranging abiotic conditions, but little is known about how they egress from their remote nursery habitats, which often requires them to cross > 1 km of mangrove forest to reach the open estuary. The objective of this study was to (1) compare Tarpon body condition among ponds close to the open estuary versus those ponds farther away on the Cape Haze peninsula of Charlotte Harbor, Florida, and (2) using acoustic telemetry determine what factors contribute to Tarpon emigration from the ponds to open estuarine waters. We tested the hypothesis that distinct groups of Tarpon occur in isolated ponds, leading to variation in fish length and body condition, and that opportunities for emigration from these ponds hinge on high water events. No pond stood out as having Tarpon of low body condition. Factors contributing to increased probabilities of Tarpon emigration were low barometric pressure, high-water level, and Tarpon body length. Tarpon emigrated from ponds near tidal creeks during summer king tides, while tropical cyclone conditions were needed to allow for movement from ponds farther in the landscape. The juvenile Tarpon were later detected at the mouths of large rivers 30 km up-estuary. The characterizations of water levels and event criteria needed for successful Tarpon nurseries should aid in habitat conservation and the creation of Tarpon nursery habitat in restoration designs.

Environmental Change Drivers Reduce Sapling Layer Diversity in Sugar Maple-Beech Forests of Eastern North America - Michael R. Zarfos; Gregory B. Lawrence; Colin M. Beier; Blair D. Page; Todd C. McDonnell; Timothy J. Sullivan; Mariann T. Garrison-Johnston; Martin Dovciak (Ecosystems, 2024)

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Advancing an integrated understanding of land–ocean connections in shaping the marine ecosystems of coastal temperate rainforest ecoregions - Brian P. V. Hunt; Simone Alin; Allison Bidlack; Heida L. Diefenderfer; Jennifer M. Jackson; Colleen T. E. Kellogg; Peter Kiffney; Kyra A. St. Pierre; Eddy Carmack; William C. Floyd; Eran Hood; Alexander R. Horner‐Devine; et al. (Limnology and Oceanography, 2024)
Land and ocean ecosystems are strongly connected and mutually interactive. As climate changes and other anthropogenic stressors intensify, the complex pathways that link these systems will strengthen or weaken in ways that are currently beyond reliable prediction. In this review we offer a framework of land–ocean couplings and their role in shaping marine ecosystems in coastal temperate rainforest (CTR) ecoregions, where high freshwater and materials flux result in particularly strong land–ocean connections. Using the largest contiguous expanse of CTR on Earth—the Northeast Pacific CTR (NPCTR)—as a case study, we integrate current understanding of the spatial and temporal scales of interacting processes across the land–ocean continuum, and examine how these processes structure and are defining features of marine ecosystems from nearshore to offshore domains. We look ahead to the potential effects of climate and other anthropogenic changes on the coupled land–ocean meta‐ecosystem. Finally, we review key data gaps and provide research recommendations for an integrated, transdisciplinary approach with the intent to guide future evaluations of and management recommendations for ongoing impacts to marine ecosystems of the NPCTR and other CTRs globally. In the light of extreme events including heatwaves, fire, and flooding, which are occurring almost annually, this integrative agenda is not only necessary but urgent.

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

A methodological framework for assessing sea level rise impacts on nitrate loading in coastal agricultural watersheds using SWAT+: A case study of the Tar-Pamlico River basin, North Carolina, USA - Mahesh R. Tapas; Randall Etheridge; Thanh-Nhan-Duc Tran; Colin G. Finlay; Ariane L. Peralta; Natasha Bell; Yicheng Xu; Venkataraman Lakshmi (Science of The Total Environment, 2024)

Extruded plant protein two-dimensional scaffold structures support myoblast cell growth for potential applications in cultured meat - Marina Ikuse; Colin R. Marchus; Nathan R. Schiele; Girish M. Ganjyal (Food Research International, 2024)

From microplastics to pixels: testing the robustness of two machine learning approaches for automated, Nile red-based marine microplastic identification - Nelle Meyers; Bavo De Witte; Natascha Schmidt; Dorte Herzke; Jean-Luc Fuda; David Vanavermaete; Colin R. Janssen; Gert Everaert (Environmental Science and Pollution Research, 2024)

Quantifying the role of iron recycling by Adélie and Emperor penguins over the austral spring and summer in Prydz Bay - Lavenia Ratnarajah; Louise Emmerson; Colin Southwell; Delphine Lannuzel; Ashley T. Townsend; Andrew R. Bowie (Frontiers in Marine Science, 2024)
In large areas of the Southern Ocean, iron limits phytoplankton production. Although biologically mediated iron recycling has been studied for the higher trophic-level whales and the lower trophic-level krill, less is known of the numerically abundant seabirds foraging in Antarctic waters. In this study, we estimate the magnitude of iron recycled by two Antarctic breeding seabirds, the Adélie and emperor penguins, across the austral spring and summer in the Prydz Bay region, East Antarctica. Their contribution to iron recycling and associated pathways differs in line with their contrasting life history strategies (summer and winter breeding) and their breeding habitat (land and fast ice). We consider their breeding cycle in relation to their terrestrial activities compared to foraging periods at sea. High iron concentration (~419 mg kg −1 ) in guano of both penguin species suggests that they are a source of regenerated iron. Breeding emperor penguins supplied an average of 237 μmol iron m −2 day −1 on the fast ice that they breed on that eventually ends in the ocean when the ice melts completely in summer (November–February). During their foraging trips, the adult emperor penguins contribute between 7 × 10 −5 and 4 × 10 −4 μmol iron m −2 day −1 , as their foraging ranges increase over the breeding season. In contrast, breeding Adélie penguins supplied between 254 and 1,243 μmol iron m −2 day −1 whilst at their colony, with a fraction of guano entering the ocean via meltwater flowing into the ocean. The flux decreases to 2 × 10 −3 to 6 × 10 −2 μmol iron m −2 d −1 , whilst they are foraging. Our study finds that penguins redistribute a large flux of iron onto their colonies, which may enter the adjacent water through sea ice melt and facilitated through katabatic winds. Despite their high abundance in Prydz Bay, the contribution of penguins to iron flux during their foraging periods is minor, due to the enormous foraging range being covered. Further research into the bioavailability of iron by marine organisms coupled with parallel measurements of seawater iron concentration and phytoplankton uptake experiments will be invaluable in refining iron budgets in both this region and other hotspots along the Antarctic coast where higher trophic-level animals are abundant.

Temperature dependent sensitivity of the harpacticoid copepod Nitokra spinipes to marine algal toxins - Wenxin Liu; Ilias Semmouri; Colin R. Janssen; Jana Asselman (Chemosphere, 2024)

Towards reliable data: Validation of a machine learning-based approach for microplastics analysis in marine organisms using Nile red staining - Nelle Meyers; Gert Everaert; Kris Hostens; Natascha Schmidt; Dorte Herzke; Jean-Luc Fuda; Colin R. Janssen; Bavo De Witte (Marine Pollution Bulletin, 2024)

Impact of the 2022 New Mexico, US wildfires on air quality and health - Kamal J. Maji; Bonne Ford; Zongrun Li; Yongtao Hu; Leiqiu Hu; Chelsea Eastman Langer; Colin Hawkinson; Srikanth Paladugu; Stephanie Moraga-McHaley; Brian Woods; Melissa Vansickle; Christopher K. Uejio; et al. (Science of The Total Environment, 2024)

Optimizing extraction methods by a comprehensive experimental approach and characterizing polyphenol compositions of Ecklonia radiata - Xinyu Duan; Vigasini Subbiah; Osman Tuncay Agar; Colin J. Barrow; Muthupandian Ashokkumar; Frank R. Dunshea; Hafiz A.R. Suleria (Food Chemistry, 2024)

Decadal trends and dynamics in the abundance and biomass of marine branchiopods in the southern part of the North Sea - Ilias Semmouri; Jonas Mortelmans; Charlie Roland; Colin R. Janssen; Jana Asselman (Journal of Marine Systems, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Simulation of chloropicrin emissions in response to soil conditions and applicator practices - Colin R. Brown; Atac Tuli; Yvan A. Delgado de la flor; Jazmin G. Johnson; Maziar Kandelous (Science of The Total Environment, 2024)

Effect of accelerated aging on shelf-stability, product loss, sensory and biochemical characteristics in 2 lower quality beef cuts - Haley J. Jeneske; Colin K.Y. Chun; Larissa A. Koulicoff; Sara R. Hene; Jessie Vipham; Travis G. O'Quinn; Morgan D. Zumbaugh; Michael D. Chao (Meat Science, 2024)

Evidence for the differential efficacy of yaw and pitch gaze stabilization mechanisms in people with multiple sclerosis - Colin R. Grove; Brian J. Loyd; Leland E. Dibble; Michael C. Schubert (Experimental Brain Research, 2024)

Aerosolization of micro- and nanoplastics via sea spray: Investigating the role of polymer type, size, and concentration, and potential implications for human exposure - Silke Lambert; Maaike Vercauteren; Ana Isabel Catarino; Yunmeng Li; Josefien Van Landuyt; Nico Boon; Gert Everaert; Maarten De Rijcke; Colin R. Janssen; Jana Asselman (Environmental Pollution, 2024)

When is it safe to go home? Post-predation assessment of risk and safety when personal information conflicts with social cues - Brian D. Wisenden; Cat M. Adkins; Seth A. Campbell; Shree Chakraborty; Madelyn E. Cloutier; Alex D. Doebler; Kathryn A. Hanson; Lou Hoff; Molly I. M. Johnson; Philip S. Larson; Claire M. Lukasik; Zoe R. Michaelson; et al. (Behavioral Ecology and Sociobiology, 2024)

Spatio‐temporal integrated Bayesian species distribution models reveal lack of broad relationships between traits and range shifts - Joris H. Wiethase; Philip S. Mostert; Christopher R. Cooney; Robert B. O'Hara; Colin M. Beale (Global Ecology and Biogeography, 2024)
Aim Climate change and habitat loss or degradation are some of the greatest threats that species face today, often resulting in range shifts. Species traits have been discussed as important predictors of range shifts, with the identification of general trends being of great interest to conservation efforts. However, studies reviewing relationships between traits and range shifts have questioned the existence of such generalized trends, due to mixed results and weak correlations, as well as analytical shortcomings. The aim of this study was to test this relationship empirically, using analytical approaches that account for common sources of bias when assessing range trends. Location Tanzania, East Africa. Time period 1980–1999 and 2000–2020. Major taxa studied 57 savannah specialist birds found in Tanzania, belonging to 26 families and 11 orders. Methods We applied recently developed integrated spatio‐temporal species distribution models in R‐INLA, combining citizen science and bird Atlas data to estimate ranges of species, quantify range shifts, and test the predictive power of traditional trait groups, as well as exposure‐related and sensitivity traits. We based our study on 40 years of bird observations in East African savannahs, a biome that has experienced increasing climatic and non‐climatic pressures over recent decades. We correlated patterns of change with species traits using linear regression models. Results We find indications of relationships identified by previous research, but low average explanatory power of traits from an ecological perspective, confirming the lack of meaningful general associations. However, our analysis finds compelling species‐specific results. Main conclusions We highlight the importance of individual assessments while demonstrating the usefulness of our analytical approach for analyses of range shifts.

The telomere-to-telomere, gapless, phased diploid genome and methylome of the green alga Scenedesmus obliquus UTEX 3031 reveals significant heterozygosity and genetic divergence of the haplotypes - Thomas C. Biondi; Colin P.S. Kruse; Samuel I. Koehler; Taehyung Kwon; Aubrey K. Davis; Wyatt Eng; Yuliya Kunde; Cheryl D. Gleasner; Kayley T. You Mak; Juergen Polle; Blake T. Hovde; Erik R. Hanschen; et al. (Algal Research, 2024)

Pathways from research to sustainable development: Insights from ten research projects in sustainability and resilience - Anna Scaini; Joseph Mulligan; Håkan Berg; Albert Brangarí; Vera Bukachi; Sebastian Carenzo; Da Chau Thi; Colin Courtney-Mustaphi; Anneli Ekblom; Hanne Fjelde; Mathias Fridahl; Anders Hansson; et al. (Ambio, 2024)
Drawing on collective experience from ten collaborative research projects focused on the Global South, we identify three major challenges that impede the translation of research on sustainability and resilience into better-informed choices by individuals and policy-makers that in turn can support transformation to a sustainable future. The three challenges comprise: (i) converting knowledge produced during research projects into successful knowledge application; (ii) scaling up knowledge in time when research projects are short-term and potential impacts are long-term; and (iii) scaling up knowledge across space, from local research sites to larger-scale or even global impact. Some potential pathways for funding agencies to overcome these challenges include providing targeted prolonged funding for dissemination and outreach, and facilitating collaboration and coordination across different sites, research teams, and partner organizations. By systematically documenting these challenges, we hope to pave the way for further innovations in the research cycle.

Genomic underpinnings of head and body shape in Arctic charr ecomorph pairs - Sam Fenton; Arne Jacobs; Colin W. Bean; Colin E. Adams; Kathryn R. Elmer (Molecular Ecology, 2024)
Across its Holarctic range, Arctic charr ( Salvelinus alpinus ) populations have diverged into distinct trophic specialists across independent replicate lakes. The major aspect of divergence between ecomorphs is in head shape and body shape, which are ecomorphological traits reflecting niche use. However, whether the genomic underpinnings of these parallel divergences are consistent across replicates was unknown but key for resolving the substrate of parallel evolution. We investigated the genomic basis of head shape and body shape morphology across four benthivore–planktivore ecomorph pairs of Arctic charr in Scotland. Through genome‐wide association analyses, we found genomic regions associated with head shape (89 SNPs) or body shape (180 SNPs) separately and 50 of these SNPs were strongly associated with both body and head shape morphology. For each trait separately, only a small number of SNPs were shared across all ecomorph pairs (3 SNPs for head shape and 10 SNPs for body shape). Signs of selection on the associated genomic regions varied across pairs, consistent with evolutionary demography differing considerably across lakes. Using a comprehensive database of salmonid QTLs newly augmented and mapped to a charr genome, we found several of the head‐ and body‐shape‐associated SNPs were within or near morphology QTLs from other salmonid species, reflecting a shared genetic basis for these phenotypes across species. Overall, our results demonstrate how parallel ecotype divergences can have both population‐specific and deeply shared genomic underpinnings across replicates, influenced by differences in their environments and demographic histories.

Microplastic-specific biofilm growth determines the vertical transport of plastics in freshwater - Maaike Vercauteren; Silke Lambert; Esther Hoogerwerf; Colin R. Janssen; Jana Asselman (Science of The Total Environment, 2024)

Holocene black carbon in New Zealand lake sediment records - Sandra O. Brugger; David B. McWethy; Nathan J. Chellman; Matiu Prebble; Colin J. Courtney Mustaphi; Sabine Eckhardt; Andreas Plach; Andreas Stohl; Janet M. Wilmshurst; Joseph R. McConnell; Cathy Whitlock (Quaternary Science Reviews, 2024)

Allelopathy in macroalgae: Ecological principles, research opportunities and pitfalls reviewed - Ilias Semmouri; Colin R. Janssen; Jana Asselman (Journal of Applied Phycology, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

The potential of high temporal resolution automatic measurements of PM2.5 composition as an alternative to the filter-based manual method used in routine monitoring - Marsailidh M. Twigg; Chiara F. Di Marco; Elizabeth A. McGhee; Christine F. Braban; Eiko Nemitz; Richard J.C. Brown; Kevin C. Blakley; Sarah R. Leeson; Agnieszka Sanocka; David C. Green; Max Priestman; Veronique Riffault; et al. (Atmospheric Environment, 2023)

A generic three-dimensional model for solar energy reflected from mirrors in circular orbits - Onur Çelik; Colin R. McInnes (Advances in Space Research, 2023)

Identification and quantification of Acanthamoeba spp. within seawater at four coastal lagoons on the east coast of Australia - Binod Rayamajhee; Nathan L.R. Williams; Nachshon Siboni; Kiri Rodgers; Mark Willcox; Fiona L. Henriquez; Justin R. Seymour; Jaimie Potts; Colin Johnson; Peter Scanes; Nicole Carnt (Science of The Total Environment, 2023)

A tsunami deposit in the Stonewall Formation (Upper Ordovician), northeastern margin of the Williston Basin, Canada, and its tectonic and stratigraphic implications - Brian R. Pratt; Colin D. Sproat (Sedimentary Geology, 2023)

Synthesis and characterization of TiO2-carbon filter materials for water decontamination by adsorption-degradation processes - Vinicius Diniz; Colin R. Crick; Susanne Rath (Journal of Environmental Management, 2023)

Community‐wide correlations between species richness, abundance and population genomic diversity in a freshwater biodiversity hotspot - Jamie R. Bucholz; Garrett W. Hopper; Irene Sánchez González; Taylor E. Kelley; Colin R. Jackson; Ryan C. Garrick; Carla L. Atkinson; Jeffrey D. Lozier (Molecular Ecology, 2023)
Understanding patterns of diversity across macro (e.g. species‐level) and micro (e.g. molecular‐level) scales can shed light on community function and stability by elucidating the abiotic and biotic drivers of diversity within ecological communities. We examined the relationships among taxonomic and genetic metrics of diversity in freshwater mussels (Bivalvia: Unionidae), an ecologically important and species‐rich group in the southeastern United States. Using quantitative community surveys and reduced‐representation genome sequencing across 22 sites in seven rivers and two river basins, we surveyed 68 mussel species and sequenced 23 of these species to characterize intrapopulation genetic variation. We tested for the presence of species diversity–abundance correlations (i.e. the more‐individuals hypothesis, MIH), species‐genetic diversity correlations (SGDCs) and abundance‐genetic diversity correlations (AGDCs) across all sites to evaluate relationships between different metrics of diversity. Sites with greater cumulative multispecies density (a standardized metric of abundance) had a greater number of species, consistent with the MIH hypothesis. Intrapopulation genetic diversity was strongly associated with the density of most species, indicating the presence of AGDCs. However, there was no consistent evidence for SGDCs. Although sites with greater overall densities of mussels had greater species richness, sites with higher genetic diversity did not always exhibit positive correlations with species richness, suggesting that there are spatial and evolutionary scales at which the processes influencing community‐level diversity and intraspecific diversity differ. Our work reveals the importance of local abundance as indicator (and possibly a driver) of intrapopulation genetic diversity.

When are environmental DNA early detections of invasive species actionable? - Adam J. Sepulveda; Christine E. Dumoulin; Denise L. Blanchette; John McPhedran; Colin Holme; Nathan Whalen; Margaret E. Hunter; Christopher M. Merkes; Catherine A. Richter; Matthew E. Neilson; Wesley M. Daniel; Devin N. Jones; et al. (Journal of Environmental Management, 2023)

Axo-glial interactions between midbrain dopamine neurons and oligodendrocyte lineage cells in the anterior corpus callosum - Megan Caldwell; Vanessa Ayo-Jibunoh; Josue Criollo Mendoza; Katherine R. Brimblecombe; Lauren M. Reynolds; Xin Yan Zhu Jiang; Colin Alarcon; Elizabeth Fiore; Jacquelyn N. Tomaio; Greg R. Phillips; Susana Mingote; Cecilia Flores; et al. (Brain Structure and Function, 2023)
Oligodendrocyte progenitor cells (OPCs) receive synaptic innervation from glutamatergic and GABAergic axons and can be dynamically regulated by neural activity, resulting in activity-dependent changes in patterns of axon myelination. However, it remains unclear to what extent other types of neurons may innervate OPCs. Here, we provide evidence implicating midbrain dopamine neurons in the innervation of oligodendrocyte lineage cells in the anterior corpus callosum and nearby white matter tracts of male and female adult mice. Dopaminergic axon terminals were identified in the corpus callosum of DAT-Cre mice after injection of an eYFP reporter virus into the midbrain. Furthermore, fast-scan cyclic voltammetry revealed monoaminergic transients in the anterior corpus callosum, consistent with the anatomical findings. Using RNAscope, we further demonstrate that ~ 40% of Olig2 + /Pdfgra + cells and ~ 20% of Olig2 + /Pdgfra- cells in the anterior corpus callosum express Drd1 and Drd2 transcripts. These results suggest that oligodendrocyte lineage cells may respond to dopamine released from midbrain dopamine axons, which could affect myelination. Together, this work broadens our understanding of neuron-glia interactions with important implications for myelin plasticity by identifying midbrain dopamine axons as a potential regulator of corpus callosal oligodendrocyte lineage cells.

Assessment of road run-off and domestic wastewater contribution to microplastic pollution in a densely populated area (Flanders, Belgium) - Maaike Vercauteren; Ilias Semmouri; Emmanuel Van Acker; Emmy Pequeur; Leen Van Esch; Inge Uljee; Jana Asselman; Colin R. Janssen (Environmental Pollution, 2023)

The development of a solid lipid nanoparticle (SLN)-based lacticin 3147 hydrogel for the treatment of wound infections - Aoibhín Ryan; Pratikkumar Patel; Poonam Ratrey; Paula M. O’Connor; Julie O’Sullivan; R. Paul Ross; Colin Hill; Sarah P. Hudson (Drug Delivery and Translational Research, 2023)
Chronic wounds affect millions of people globally. This number is set to rise with the increasing incidence of antimicrobial-resistant bacterial infections, such as methicillin-resistant Staphylococcus aureus (MRSA), which impair the healing of chronic wounds. Lacticin 3147 is a two-peptide chain bacteriocin produced by Lactococcus lactis that is active against S. aureus including MRSA strains. Previously, poor physicochemical properties of the peptides were overcome by the encapsulation of lacticin 3147 into solid lipid nanoparticles. Here, a lacticin 3147 solid lipid nanoparticle gel is proposed as a topical treatment for S. aureus and MRSA wound infections. Initially, lacticin 3147’s antimicrobial activity against S. aureus was determined before encapsulation into solid lipid nanoparticles. An optimised gel formulation with the desired physicochemical properties for topical application was developed, and the lacticin-loaded solid lipid nanoparticles and free lacticin 3147 aqueous solution were incorporated into separate gels. The release of lacticin 3147 from both the solid lipid nanoparticle and free lacticin gels was measured where the solid lipid nanoparticle gel exhibited increased activity for a longer period (11 days) compared to the free lacticin gel (9 days). Both gels displayed potent activity ex vivo against S. aureus- infected pig skin with significant bacterial eradication (> 75%) after 1 h. Thus, a long-acting potent lacticin 3147 solid lipid nanoparticle gel with the required physicochemical properties for topical delivery of lacticin 3147 to the skin for the potential treatment of S. aureus -infected chronic wounds was developed. Graphical abstract

Decadal decline of dominant copepod species in the North Sea is associated with ocean warming: Importance of marine heatwaves - Ilias Semmouri; Karel A.C. De Schamphelaere; Jonas Mortelmans; Jan Mees; Jana Asselman; Colin R. Janssen (Marine Pollution Bulletin, 2023)

Quantification of wetland vegetation communities features with airborne AVIRIS-NG, UAVSAR, and UAV LiDAR data in Peace-Athabasca Delta - Chao Wang; Tamlin M. Pavelsky; Ethan D. Kyzivat; Fenix Garcia-Tigreros; Erika Podest; Fangfang Yao; Xiao Yang; Shuai Zhang; Conghe Song; Theodore Langhorst; Wayana Dolan; Martin R. Kurek; et al. (Remote Sensing of Environment, 2023)

Clay mineral assemblages of late Holocene turbidites in the Gaoping Submarine Canyon of the northeastern South China Sea and their responses to typhoon activities - Huazhen Huang; Zhifei Liu; Yulong Zhao; Hongchao Zhao; Adrian R. Fernandez; Christophe Colin; Andrew Tien-Shun Lin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Evaluating the sustainability of the 2017 US biofuel industry with an integrated techno-economic analysis and life cycle assessment - Jack P. Smith; Braden J. Limb; Colin M. Beal; Kelly R. Banta; John L. Field; Steven J. Simske; Jason C. Quinn (Journal of Cleaner Production, 2023)

Phenolic bioaccessibility, antioxidant, and antidiabetic effects of indigenous fermented coffee beans after simulated gastrointestinal digestion and colonic fermentation - Hanjing Wu; Colin Barrow; Frank R. Dunshea; Hafiz A.R. Suleria (Food Bioscience, 2023)

Current and legacy effects of precipitation treatments on growth and nutrition in contrasting crops - Erin D. Jackson; Christian Casolaro; Ryan S. Nebeker; Eric R. Scott; Jeffrey S. Dukes; Timothy S. Griffin; Colin M. Orians (Agriculture, Ecosystems & Environment, 2023)

A reference architecture for orbiting solar reflectors to enhance terrestrial solar power plant output - Andrea Viale; Onur Çelik; Temitayo Oderinwale; Litesh Sulbhewar; Colin R. McInnes (Advances in Space Research, 2023)

Micro- and nanoplastics transfer from seawater to the atmosphere through aerosolization under controlled laboratory conditions - Ana Isabel Catarino; Maria Camila León; Yunmeng Li; Silke Lambert; Maaike Vercauteren; Jana Asselman; Colin R. Janssen; Gert Everaert; Maarten De Rijcke (Marine Pollution Bulletin, 2023)

Co-curricular Immersion as a Public–Private Capacity Building Activity - Anish Reddy; Jennifer Sieg; Emily Ristevski; Shyam Sunder Polaconda; Jennifer Buck; Rebecca Guenther; Alisa M. Jones; Laurene Sweet; Matthew R. Williams; Colin K. Drummond (Biomedical Engineering Education, 2023)

Kisspeptin neuron projections to oxytocin neurons are not necessary for parturition in the mouse - Shalini S. Kumar; Gregory T. Bouwer; Meliame K. Jackson; Michael R. Perkinson; Fiona J. McDonald; Colin H. Brown; Rachael A. Augustine (Brain Structure and Function, 2023)
Oxytocin is synthesized by hypothalamic supraoptic nucleus (SON) and paraventricular nucleus (PVN) neurons and is released from the posterior pituitary gland to trigger uterine contractions during parturition. In rats, oxytocin neuron innervation by periventricular nucleus (PeN) kisspeptin neurons increases over pregnancy and intra-SON kisspeptin administration excites oxytocin neurons only in late pregnancy. To test the hypothesis that kisspeptin neurons excite oxytocin neurons to trigger uterine contractions during birth in C57/B6J mice, double-label immunohistochemistry for kisspeptin and oxytocin first confirmed that kisspeptin neurons project to the SON and PVN. Furthermore, kisspeptin fibers expressed synaptophysin and formed close appositions with oxytocin neurons in the mouse SON and PVN before and during pregnancy. Stereotaxic viral delivery of caspase-3 into the AVPV/PeN of Kiss-Cre mice before mating reduced kisspeptin expression in the AVPV, PeN, SON and PVN by > 90% but did not affect the duration of pregnancy or the timing of delivery of each pup during parturition. Therefore, it appears that AVPV/PeN kisspeptin neuron projections to oxytocin neurons are not necessary for parturition in the mouse.

The compositional diversity and temporal evolution of an active andesitic arc stratovolcano: Tongariro, Taupō Volcanic Zone, New Zealand - Leo R. Pure; Colin J. N. Wilson; Bruce L. A. Charlier; John A. Gamble; Dougal B. Townsend; Graham S. Leonard (Contributions to Mineralogy and Petrology, 2023)
New geochemical data, including Sr–Nd–Pb isotopes for whole-rock and groundmass samples, are reported for edifice-forming eruptives at Tongariro volcano, New Zealand, which span its ~ 350 ka to late Holocene history. Tongariro eruptives are medium-K basaltic-andesites to dacites (53.0–66.2 wt% SiO 2 ) that evolved via assimilation-fractional crystallisation (AFC) processes partly or mostly in the uppermost 15 km of the crust. When ordered chronologically using a high-resolution 40 Ar/ 39 Ar-dated eruptive stratigraphy, the compositional data show systematic 10–130 kyr cycles. Mafic replenishment events inferred from MgO values occurred at ~ 230, ~ 151, ~ 88 and ~ 56 ka and in the late Holocene, with high-MgO flank vents erupting at ~ 160, ~ 117, ~ 35 and ~ 17.5 ka. Cycles in Sm/Nd, 87 Sr/ 86 Sr, 143 Nd/ 144 Nd and Pb isotopic ratios, which are decoupled from MgO, K 2 O and Rb/Sr cycles, indicate periods of prolonged crustal residence of magmas from ~ 230 to ~ 100 ka and ~ 95 to ~ 30 ka. AFC modelling shows that intermediate and silicic melt compositions, with r-values between 0.1 and 1, are needed to reproduce Tongariro compositional arrays. AFC models also indicate that ~ 20% of the average Tongariro magma comprises assimilated (meta)sedimentary basement material. Locally, Tongariro and adjacent Ruapehu volcanoes attain their most crust-like 87 Sr/ 86 Sr and 143 Nd/ 144 Nd compositions at ~ 100 and ~ 30 ka, paralleling with zircon model-age crystallisation modes at the rhyolitic Taupō volcano ~ 50 km to the NNE. These coincidences suggest that the timing and tempo of magma assembly processes at all three volcanoes were contemporaneous and may have been tectonically influenced since at least 200 ka.

Correction: Textural and micro-analytical insights into mafic–felsic interactions during the Oruanui eruption, Taupo - Shane M. Rooyakkers; Colin J. N. Wilson; C. Ian Schipper; Simon J. Barker; Aidan S. R. Allan (Contributions to Mineralogy and Petrology, 2023)

Comparative study on the effect of different drying techniques on phenolic compounds in Australian beach-cast brown seaweeds - Vigasini Subbiah; Xinyu Duan; Osman Tuncay Agar; Frank R. Dunshea; Colin J. Barrow; Hafiz A.R. Suleria (Algal Research, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Lowering temperature to 1 °C results in physiological changes, stress and mortality in cultured Atlantic Salmon (Salmo salar) - Émile Vadboncoeur; Charlotte Nelson; Jennifer R. Hall; Kathy A. Clow; Rebeccah M. Sandrelli; Colin J. Brauner; Andrew K. Swanson; A. Kurt Gamperl (Aquaculture, 2023)

The Need for and Challenges of Nutrition and Dietetics Registry Studies: An Update on the Academy of Nutrition and Dietetics Health Informatics Infrastructure - Casey R. Colin; Lindsay Woodcock; Lauri Y. Wright; Elizabeth Yakes Jimenez; Constantina Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2023)

Pre-eruptive rhyolite magma ascent rate is rapid and independent of eruption size: a case study from Ōkataina Volcanic Centre, Aotearoa New Zealand - Hannah C. Elms; Madison L. Myers; Alexander R. L. Nichols; Paul J. Wallace; Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier (Bulletin of Volcanology, 2023)
Volatile measurements in mineral-hosted sealed melt inclusions, and open-ended embayments, have previously been used to study magma ascent dynamics in large rhyolitic eruptions. However, despite occurring more frequently, smaller-volume explosive events remain under-studied. We present magmatic volatile data from quartz-hosted melt inclusions and embayments for eight post-25.4 ka rhyolitic eruptions at Ōkataina Volcanic Centre, Aotearoa New Zealand. Seven originated from within the main caldera, and the other erupted from the associated Ōkareka Structural Embayment. Melt inclusions preserve volatile contents of 2.92–5.82 wt% H 2 O and 13–126 ppm CO 2 , indicating pre-eruptive storage depths of 4.5–7.4 km, with younger eruptions being more shallow. The lack of correlation between H 2 O, CO 2 , inclusion size or distance to the crystal rim suggests magma bodies experienced variable degrees of degassing during magma storage, with some amount of post-entrapment volatile modification prior to and concurrent with final magma ascent. Diffusion modelling of measured H 2 O gradients in melt embayments indicates ascent rates of 0.10–1.67 m.s −1 over time spans of 20–230 min for the intra-caldera events. In contrast, ascent rates for the eruption from the Ōkareka Structural Embayment may be more rapid, at 1.59–4.4 m.s −1 over a time span of 22–34 min. Our findings imply that the final, pre-eruptive magma movement towards the surface could be less than a few hours. Comparisons with published data for caldera-forming explosive events reveal no clear relationships between final ascent rate, eruption size or initial volatile content, implying that other factors besides eruption volume control rhyolite magma ascent.

Are we there yet? Management baselines and biodiversity indicators for the protection and restoration of subtidal bivalve shellfish habitats - Jose M. Fariñas-Franco; Robert L. Cook; Fiona R. Gell; Dan B. Harries; Natalie Hirst; Flora Kent; Rebecca MacPherson; Colin Moore; James M. Mair; Joanne S. Porter; William G. Sanderson (Science of The Total Environment, 2023)

Projecting COVID-19 cases and hospital burden in Ohio - Wasiur R. KhudaBukhsh; Caleb Deen Bastian; Matthew Wascher; Colin Klaus; Saumya Yashmohini Sahai; Mark H. Weir; Eben Kenah; Elisabeth Root; Joseph H. Tien; Grzegorz A. Rempała (Journal of Theoretical Biology, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

The future is bright: Biofortification of common foods can improve vitamin D status - Holly R. Neill; Chris I. R. Gill; Emma J. McDonald; W. Colin McRoberts; L. Kirsty Pourshahidi (Critical Reviews in Food Science and Nutrition, 2023)

Synthesizing the impact of sea-dumped munition and related chemicals on humans and the environment - João Barbosa; Jana Asselman; Colin R. Janssen (Marine Pollution Bulletin, 2023)

Virgin queen behaviour and controlled mating in the stingless bee Tetragonula carbonaria (Meliponini) - F. G. B. Bueno; R. Hajjar; T. Colin; G. Buchmann; T. Latty; R. Gloag (Insectes Sociaux, 2023)
Improving knowledge of virgin queen behaviour and mating biology in stingless bees (Meliponini) is an important step towards artificial selection programmes for managed colonies. Here we study the Australian stingless bee Tetragonula carbonaria to (1) describe the behaviour of queens from eclosion until egg-laying, and (2) assess whether young queens can be reared and mated under constrained conditions. We extracted mature virgin queen cells of T. carbonaria from large colonies and reared them in queen maturation boxes containing a limited number of workers (“micro-colonies”) . Queen behaviour followed a typical pattern with three phases: a period of high activity and wing-flapping on top of the brood (5 ± 2 days of age), attempts to leave the colony for the nuptial flight (12 ± 3 days of age), and oviposition (20 ± 6 days of age). In total, 71% (68 of 95) of queen cells hatched in our maturation boxes and 57% (39 of 68) survived to mating age, with some observed to be actively killed by workers within the first week of life (8 of 68; 11%). For a subset of our queens, we performed controlled matings (either with or without CO 2 narcosis) by presenting constrained females to males in mating aggregations, allowing one male to mate (deposit mating plug) and then returning queens to their box. In the absence of CO 2 narcosis, 30% of queens mated this way were subsequently found to have sperm in their spermathecae, indicative of a successful mating (5 of 17). The remaining 70% however contained no sperm, despite the presence of the male mating plug. Amongst queens that were CO 2 narcotized before and during the controlled mating, none had sperm in their spermathecae (0 of 12), though most went on to activate their ovaries following the mating and lay male (haploid) eggs. Together, these trials indicate that controlled matings with T. carbonaria are possible, but suggest that queens may need to actively accept mating for successful sperm transfer.

Polaris Gold: An Attractive, Yellow-fleshed Tablestock Cultivar with Chipping Potential - Thomas R. Stefaniak; Jeffrey Miller; Colin R. Jones; Michael Miller; Muyideen Yusuf; Megan A. Harder; John C. Larsen; Cari A. Schmitz Carley; Darrin Haagenson; Asunta Thompson; Thomas E. Michaels; Christian Thill; et al. (American Journal of Potato Research, 2023)

Coordination of photosynthetic traits across soil and climate gradients - Andrea C. Westerband; Ian J. Wright; Vincent Maire; Jennifer Paillassa; Iain Colin Prentice; Owen K. Atkin; Keith J. Bloomfield; Lucas A. Cernusak; Ning Dong; Sean M. Gleason; Caio Guilherme Pereira; Hans Lambers; et al. (Global Change Biology, 2023)
“Least‐cost theory” posits that C 3 plants should balance rates of photosynthetic water loss and carboxylation in relation to the relative acquisition and maintenance costs of resources required for these activities. Here we investigated the dependency of photosynthetic traits on climate and soil properties using a new Australia‐wide trait dataset spanning 528 species from 67 sites. We tested the hypotheses that plants on relatively cold or dry sites, or on relatively more fertile sites, would typically operate at greater CO 2 drawdown (lower ratio of leaf internal to ambient CO 2 , C i : C a ) during light‐saturated photosynthesis, and at higher leaf N per area (N area ) and higher carboxylation capacity ( V cmax 25 ) for a given rate of stomatal conductance to water vapour, g sw . These results would be indicative of plants having relatively higher water costs than nutrient costs. In general, our hypotheses were supported. Soil total phosphorus (P) concentration and (more weakly) soil pH exerted positive effects on the N area – g sw and V cmax 25 – g sw slopes, and negative effects on C i : C a . The P effect strengthened when the effect of climate was removed via partial regression. We observed similar trends with increasing soil cation exchange capacity and clay content, which affect soil nutrient availability, and found that soil properties explained similar amounts of variation in the focal traits as climate did. Although climate typically explained more trait variation than soil did, together they explained up to 52% of variation in the slope relationships and soil properties explained up to 30% of the variation in individual traits. Soils influenced photosynthetic traits as well as their coordination. In particular, the influence of soil P likely reflects the Australia's geologically ancient low‐relief landscapes with highly leached soils. Least‐cost theory provides a valuable framework for understanding trade‐offs between resource costs and use in plants, including limiting soil nutrients.

Characterization of the molecular mechanisms of silicon uptake in coccolithophores - Sarah Ratcliffe; Erin M. Meyer; Charlotte E. Walker; Michael Knight; Heather M. McNair; Paul G. Matson; Debora Iglesias‐Rodriguez; Mark Brzezinski; Gerald Langer; Aleksey Sadekov; Mervyn Greaves; Colin Brownlee; et al. (Environmental Microbiology, 2023)
Coccolithophores are an important group of calcifying marine phytoplankton. Although coccolithophores are not silicified, some species exhibit a requirement for Si in the calcification process. These species also possess a novel protein (SITL) that resembles the SIT family of Si transporters found in diatoms. However, the nature of Si transport in coccolithophores is not yet known, making it difficult to determine the wider role of Si in coccolithophore biology. Here, we show that coccolithophore SITLs act as Na + ‐coupled Si transporters when expressed in heterologous systems and exhibit similar characteristics to diatom SITs. We find that CbSITL from Coccolithus braarudii is transcriptionally regulated by Si availability and is expressed in environmental coccolithophore populations. However, the Si requirement of C. braarudii and other coccolithophores is very low, with transport rates of exogenous Si below the level of detection in sensitive assays of Si transport. As coccoliths contain only low levels of Si, we propose that Si acts to support the calcification process, rather than forming a structural component of the coccolith itself. Si is therefore acting as a micronutrient in coccolithophores and natural populations are only likely to experience Si limitation in circumstances where dissolved silicon (DSi) is depleted to extreme levels.

Conceptual frameworks and key questions for assessing the contribution of marine protected areas to shark and ray conservation - Andrew Chin; Fergus John Molloy; Darren Cameron; Jon C. Day; Jessica Cramp; Karin Leeann Gerhardt; Michelle R. Heupel; Mark Read; Colin A. Simpfendorfer (Conservation Biology, 2023)
Marine protected areas (MPAs) are key tools in addressing the global decline of sharks and rays, and marine parks and shark sanctuaries of various configurations have been established to conserve shark populations. However, assessments of their efficacy are compromised by inconsistent terminology, lack of standardized approaches to assess how MPAs contribute to shark and ray conservation, and ambiguity about how to integrate movement data in assessment processes. We devised a conceptual framework to standardize key terms (e.g., protection , contribution , potential impact , risk , threat ) and used the concept of portfolio risk to identify key attributes of sharks and rays (assets), the threats they face (portfolio risk), and the specific role of MPAs in risk mitigation (insurance). Movement data can be integrated into the process by informing risk exposure and mitigation through MPAs. The framework is operationalized by posing 8 key questions that prompt practitioners to consider the assessment scope, MPA type and purpose, range of existing and potential threats, species biology and ecology, and management and operational contexts. Ultimately, MPA contributions to shark and ray conservation differ according to a complex set of human and natural factors and interactions that should be carefully considered in MPA design, implementation, and evaluation.

Quantifying and mapping species threat abatement opportunities to support national target setting - Louise Mair; Eduardo Amorim; Monira Bicalho; Thomas M. Brooks; Vincente Calfo; Renata de T. Capellão; Colin Clubbe; Marianne Evju; Eduardo P. Fernandez; Gláucia C. Ferreira; Frank Hawkins; Randall R. Jiménez; et al. (Conservation Biology, 2023)
The successful implementation of the Convention on Biological Diversity's post‐2020 Global Biodiversity Framework will rely on effective translation of targets from global to national level and increased engagement across diverse sectors of society. Species conservation targets require policy support measures that can be applied to a diversity of taxonomic groups, that link action targets to outcome goals, and that can be applied to both global and national data sets to account for national context, which the species threat abatement and restoration (STAR) metric does. To test the flexibility of STAR, we applied the metric to vascular plants listed on national red lists of Brazil, Norway, and South Africa. The STAR metric uses data on species’ extinction risk, distributions, and threats, which we obtained from national red lists to quantify the contribution that threat abatement and habitat restoration activities could make to reducing species’ extinction risk. Across all 3 countries, the greatest opportunity for reducing plant species’ extinction risk was from abating threats from agricultural activities, which could reduce species’ extinction risk by 54% in Norway, 36% in South Africa, and 29% in Brazil. Species extinction risk could be reduced by a further 21% in South Africa by abating threats from invasive species and by 21% in Brazil by abating threats from urban expansion. Even with different approaches to red‐listing among countries, the STAR metric yielded informative results that identified where the greatest conservation gains could be made for species through threat‐abatement and restoration activities. Quantifiably linking local taxonomic coverage and data collection to global processes with STAR would allow national target setting to align with global targets and enable state and nonstate actors to measure and report on their potential contributions to species conservation.

Baseline levels and characterization of hydrocarbons in surface marine sediments along the transportation corridor in Hudson Bay: A multivariate analysis of n-alkanes, PAHs and biomarkers - Gary A. Stern; Colin R. Macdonald; Paloma Calabria Carvalho; Teresinha Wolfe; Fernanda Ferraz (Science of The Total Environment, 2023)

Multi-year evaluation of muskellunge (Esox masquinongy) spatial ecology during winter drawdowns in a regulated, urban waterway in Canada - Jordanna N. Bergman; Kate L. Neigel; Sean J. Landsman; Danny Glassman; Luc LaRochelle; Joseph R. Bennett; Colin D. Rennie; Jesse C. Vermaire; Steven J. Cooke (Hydrobiologia, 2023)

Attitude control actuator scaling laws for orbiting solar reflectors - Andrea Viale; Colin R. McInnes (Advances in Space Research, 2023)

Identification of next-generation International Humic Substances Society reference materials for advancing the understanding of the role of natural organic matter in the Anthropocene - Yu-Ping Chin; Diane M. McKnight; Juliana D’Andrilli; Nicole Brooks; Kaelin Cawley; Jennifer Guerard; E. Michael Perdue; Colin A. Stedmon; Paul G. Tratnyek; Paul Westerhoff; Andrew S. Wozniak; Paul R. Bloom; et al. (Aquatic Sciences, 2023)
Many challenges remain before we can fully understand the multifaceted role that natural organic matter (NOM) plays in soil and aquatic systems. These challenges remain despite the considerable progress that has been made in understanding NOM’s properties and reactivity using the latest analytical techniques. For nearly 4 decades, the International Humic Substances Society (IHSS, which is a non-profit scientific society) has distributed standard substances that adhere to strict isolation protocols and reference materials that are collected in bulk and originate from clearly defined sites. These NOM standard and reference samples offer relatively uniform materials for designing experiments and developing new analytical methods. The protocols for isolating NOM, and humic and fulvic acid fractions of NOM utilize well-established preparative scale column chromatography and reverse osmosis methods. These standard and reference NOM samples are used by the international scientific community to study NOM across a range of disciplines from engineered to natural systems, thereby seeding the transfer of knowledge across research fields. Recently, powerful new analytical techniques used to characterize NOM have revealed complexities in its composition that transcend the “microbial” vs. “terrestrial” precursor paradigm. To continue to advance NOM research in the Anthropocene epoch, a workshop was convened to identify potential new sites for NOM samples that would encompass a range of sources and precursor materials and would be relevant for studying NOM’s role in mediating environmental and biogeochemical processes. We anticipate that expanding the portfolio of IHSS reference and standard NOM samples available to the research community will enable this diverse group of scientists and engineers to better understand the role that NOM plays globally under the influence of anthropogenic mediated changes.

PIM3 kinase promotes tumor metastasis in hepatoblastoma by upregulating cell surface expression of chemokine receptor cxcr4 - Raoud Marayati; Janet Julson; Laura V. Bownes; Colin H. Quinn; Laura L. Stafman; Andee M. Beierle; Hooper R. Markert; Sara C. Hutchins; Jerry E. Stewart; David K. Crossman; Anita B. Hjelmeland; Elizabeth Mroczek-Musulman; et al. (Clinical & Experimental Metastasis, 2022)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Oceanic lobate ctenophores possess feeding mechanics similar to the impactful coastal species Mnemiopsis leidyi - Malaika Cordeiro; John H. Costello; Brad J. Gemmell; Kelly R. Sutherland; Sean P. Colin (Limnology and Oceanography, 2022)
Lobate ctenophores are often numerically dominant members of oceanic epipelagic and midwater ecosystems. Despite this, little is known about their trophic ecology. Multiple, co‐occurring species are often found in these ecosystems and appear to feed similarly via feeding currents that entrain prey. We quantified the hydrodynamics, morphology, and behavior of four co‐occurring, cosmopolitan lobate species ( Eurhamphaea vexilligera , Ocyropsis crystallina , Bolinopsis vitrea , and Leucothea multicornis ) to evaluate whether their feeding mechanics lead to differential feeding rates and prey selection. We compared the feeding characteristics of these four oceanic species to the coastal lobate ctenophore, Mnemiopsis leidyi , which is known as a voracious zooplanktivore. We found that despite their morphological diversity, the five lobate species used the same mechanism to generate their feeding current—the hydrodynamics of their feeding currents were similarly laminar and with very low fluid deformation rates. Despite having similar feeding current traits, the species had different in situ swimming behaviors and feeding postures. We show that these different behaviors and postures lead to different prey encounter rates and that several of the oceanic species have the potential to feed at rates similar to or greater than M. leidyi . As such, the individual and combined trophic impact of oceanic lobate ctenophores is likely to be much greater than previously predicted.

Substrate size modifies stream grazer–biofilm interactions in the presence of invertivorous fish - Ricardo J. Albariño; Gerard P. Closs; Christoph D. Matthaei; Colin R. Townsend; Daniel Zamorano (Ecology, 2022)
When herbivore abundance is controlled by predators there may be an indirect positive effect on primary producers due to reduced grazing pressure, but the potential of predation refuges to modify such trophic cascades has rarely been studied. By experimentally manipulating substrate particle size and fish predation regime, we assessed the outcome of invertebrate grazer–biofilm interactions in streams. Locations at the center of larger substrate particles were predicted to pose a higher predation risk, and therefore be subjected to a lower grazing pressure. In our 52‐day experiment in a New Zealand stream, small‐sized substrates (terracotta tiles) remained virtually free of periphyton across their entire upper surface, whereas a thick periphyton mat was formed across large tiles with only edges remaining free. In channels containing fish (either native Galaxias vulgaris or exotic Salmo trutta ), grazing on tiles was lower than in the absence of fish. A preference for grazing near to the edge of tiles was clearest in fish channels but was also evident even in the absence of fish, probably reflecting fish presence and/or fish kairomones in the stream from where the colonizing invertebrates had been derived. Total grazer density was similar across treatments with or without fish, suggesting that our results can be explained mostly by changes in the behavior of grazers. We suggest that refuge availability, interacting with grazer predator‐avoidance behavior, may produce a context‐dependent patchwork of trophic cascades in streams and other ecosystems.

Investigating the behaviour of Atlantic salmon ( Salmo salar L.) post‐smolts during their early marine migration through the Clyde Marine Region - Jessie Lilly; Hannele M. Honkanen; David M. Bailey; Colin W. Bean; Ruaidhri Forrester; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2022)
It is thought that survival during migration is particularly poor for Atlantic salmon post‐smolts immediately after entry into sea and particularly in the estuarine environment. Nonetheless, there is currently a lack of information on Atlantic salmon post‐smolt movement behaviour in estuaries in the UK. This study used acoustic tagging to estimate loss rates and compare the behaviour of Atlantic salmon post‐smolts migrating from two distinctly different rivers draining into the Clyde Estuary, the River Endrick ( n = 145) and the Gryffe ( n = 102). Contrary to most literature, post‐smolts undertook rapid migrations through the estuary, potentially decreasing their exposure to predators/anthropogenic stressors and reducing their estimated loss rates (river: 1%–3% km –1 ; estuary: 0.20%–0.60% km –1 ). The low loss rates in the estuary occurred despite post‐smolts engaging in passive reversal movements with the tide upon entering the estuary, possibly allowing them more time to adapt to the increased salinity. Atlantic salmon post‐smolts from both the rivers used similar migration pathways exiting into the coastal marine zone during ebbing tide. This study provides novel information on the timing and migratory routes of Atlantic salmon post‐smolts in the Clyde Estuary that can ultimately be used to inform management decisions on how to assess and reduce the potential impacts of current natural and anthropogenic stressors. Temporal repeatability of this study over multiple years is required to determine if there is variation in the factors driving the migratory patterns and loss rates of smolts in this system.

Comparative biology of the grenadiers Macrourus caml and M. whitsoni in the Ross Sea region, Antarctica - Bradley R. Moore; Steven J. Parker; Peter M. Marriott; Colin Sutton; Matthew H. Pinkerton (Frontiers in Marine Science, 2022)
The grenadiers Macrourus caml and M. whitsoni form a significant bycatch component of longline fisheries for Antarctic toothfish ( Dissostichus mawsoni ) in the Southern Ocean. A lack of species-level biological and catch data has to date hindered the development of quantitative assessments for these deepwater species. This paper examines species- and sex-specific life histories of M . caml and M . whitsoni in the Ross Sea region, Antarctica, from samples collected from the commercial fishery and research collections. Macrourus caml was found to live longer, grow slower, and attain a larger maximum length than M . whitsoni , reaching at least 65 years of age and 97 cm total length (TL) vs. 43 years and 78 cm TL for M . whitsoni . In addition, M . caml attains a larger length for a given age and a greater weight for a given length. For each species, females of a given age were larger and reached a greater maximum age than males. Assuming that selectivity of the fishing gear is related to fish size, greater fishing pressure on females than males is likely, and was evidenced by female-biased sex ratios of both species. Estimates of natural and fishing mortality rates were low for both species. Despite having a shorter lifespan and attaining a smaller maximum length, M . whitsoni matured later in life and at larger lengths than M . caml . Although sampling opportunities are constrained seasonally due to sea ice cover, gonad staging and interannual patterns in gonadosomatic indices suggest prolonged spawning for both species, with available data indicating peak spawning during austral summer. The differences in life history observed between these two closely related and morphologically similar species illustrates the importance of understanding species-specific life histories to infer responses to exploitation, provide key biological inputs to inform parameters for future risk assessments and ecosystem models as well as baseline information for comparative work over both time and space, contribute to greater clarity in managing fisheries that interact with these two species, and further our understanding of grenadier life history.

Perspectives on strengthening local food systems in Small Island Developing States - Cornelia Guell; Catherine R. Brown; Otto W. Navunicagi; Viliamu Iese; Neela Badrie; Morgan Wairiu; Arlette Saint Ville; Nigel Unwin; Sashi Kiran; T. Alafia Samuels; Ian Hambleton; Colin Tukuitonga; et al. (Food Security, 2022)
Small Island Developing States (SIDS) share high burdens of nutrition-related conditions, including non-communicable diseases, associated with an increasing reliance on imported, processed foods. Improving health through increasing the production and consumption of local, nutritious foods is a policy objective of many SIDS governments. This study aimed to understand contemporary challenges and opportunities to strengthening local food systems in two case study settings, Fiji and St. Vincent and the Grenadines. Fifty-two in-depth, semi-structured interviews were conducted with key stakeholders involved in local food production. Interviews were analysed by both country teams using thematic analysis. Local food production networks in both settings included formal governance bodies as well as more informal connections through civil society and communities. Their main function was the sharing of resources and knowledge, but levels of trust and cooperation between the stakeholders varied in a market open to intense competition from imports. Local food production was hindered by few and slow investments by local governments, dated technology, and lack of knowledge. Stakeholders believed this marginalisation was occurring against a background of rising preferences for imported foods in the population, and increasing disinterest in employment in the sector. Despite the challenges, strong narratives of resilience and opportunity were highlighted such as national pride in local produce for commercialisation and local diets. Efforts to support local food production in SIDS should focus on strengthening governance structures to prioritise local produce over corporate and import markets, assist collaboration and co-learning, and support alternative agro-food practices.

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

A global climate model ensemble for downscaled monthly climate normals over North America - Colin R. Mahony; Tongli Wang; Andreas Hamann; Alex J. Cannon (International Journal of Climatology, 2022)
Use of downscaled global climate model projections is expanding rapidly as climate change vulnerability assessments and adaptation planning become mainstream in many sectors. Many climate change impact analyses use climate model projections downscaled at very high spatial resolution (~1 km) but very low temporal resolution (20‐ to 30‐year normals). These applications have model selection priorities that are distinct from analyses at high temporal resolution. Here, we select a 13‐model ensemble and an 8‐model subset designed for robust change‐factor downscaling of monthly climate normals, and describe their attributes in North America. All models are selected from the Coupled Model Intercomparison Project Phase 6 (CMIP6) archives. The 13‐model ensemble is representative of the distribution of equilibrium climate sensitivity, grid resolution, and transient regional climate changes in the CMIP6 generation. The 8‐model subset is consistent with the IPCC's recent assessment of the very likely range of Earth's equilibrium climate sensitivity. Our results emphasize several principles for selection and use of downscaled climate ensembles: (a) the ensemble must be observationally constrained to be meaningful; (b) analysis of multiple models is essential as the ensemble mean alone can be misleading; (c) small ( http://climatena.ca/ ). An accompanying web application ( https://bcgov-env.shinyapps.io/cmip6-NA/ ) provides tools for further model selection and visualization of the ensemble.

Mapping risk to plant populations from short fire intervals via relationships between maturation period and environmental productivity - Carl R. Gosper; Ben P. Miller; Rachael V. Gallagher; Janine Kinloch; Richard van Dongen; Emma Adams; Sarah Barrett; Anne Cochrane; Sarah Comer; Lachlan McCaw; Russell G. Miller; Suzanne M. Prober; et al. (Plant Ecology, 2022)

Aging and white matter microstructure and macrostructure: a longitudinal multi-site diffusion MRI study of 1218 participants - Kurt G. Schilling; Derek Archer; Fang-Cheng Yeh; Francois Rheault; Leon Y. Cai; Colin Hansen; Qi Yang; Karthik Ramdass; Andrea T. Shafer; Susan M. Resnick; Kimberly R. Pechman; Katherine A. Gifford; et al. (Brain Structure and Function, 2022)

Cortico-amygdalar connectivity and externalizing/internalizing behavior in children with neurodevelopmental disorders - Hajer Nakua; Colin Hawco; Natalie J. Forde; Grace R. Jacobs; Michael Joseph; Aristotle N. Voineskos; Anne L. Wheeler; Meng-Chuan Lai; Peter Szatmari; Elizabeth Kelley; Xudong Liu; Stelios Georgiades; et al. (Brain Structure and Function, 2022)
Background Externalizing and internalizing behaviors contribute to clinical impairment in children with neurodevelopmental disorders (NDDs). Although associations between externalizing or internalizing behaviors and cortico-amygdalar connectivity have been found in clinical and non-clinical pediatric samples, no previous study has examined whether similar shared associations are present across children with different NDDs. Methods Multi-modal neuroimaging and behavioral data from the Province of Ontario Neurodevelopmental Disorders (POND) Network were used. POND participants aged 6–18 years with a primary diagnosis of autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD) or obsessive–compulsive disorder (OCD), as well as typically developing children (TDC) with T1-weighted, resting-state fMRI or diffusion weighted imaging (DWI) and parent-report Child Behavioral Checklist (CBCL) data available, were analyzed (total n = 346). Associations between externalizing or internalizing behavior and cortico-amygdalar structural and functional connectivity indices were examined using linear regressions, controlling for age, gender, and image-modality specific covariates. Behavior-by-diagnosis interaction effects were also examined. Results No significant linear associations (or diagnosis-by-behavior interaction effects) were found between CBCL-measured externalizing or internalizing behaviors and any of the connectivity indices examined. Post-hoc bootstrapping analyses indicated stability and reliability of these null results. Conclusions The current study provides evidence towards an absence of a shared linear relationship between internalizing or externalizing behaviors and cortico-amygdalar connectivity properties across a transdiagnostic sample of children with different primary NDD diagnoses and TDC. Different methodological approaches, including incorporation of multi-dimensional behavioral data (e.g., task-based fMRI) or clustering approaches may be needed to clarify complex brain-behavior relationships relevant to externalizing/internalizing behaviors in heterogeneous clinical NDD populations.

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Sediment dynamics at different timescales on an embayed coast in southeastern Australia - Colin D. Woodroffe; R. C. Carvalho; T. S. N. Oliver; B. G. Thom (Journal of Coastal Conservation, 2022)
The concept of coastal sediment compartments has recently been adopted at a national scale in Australia to better understand sediment and shoreline dynamics and to underpin management of future shoreline behaviour in response to impacts of climate change. Geomorphological studies in southern NSW have provided a foundation for development of conceptual models of estuary and sandy barrier evolution. Geochronological reconstructions using radiocarbon, optically-stimulated luminescence, and other dating techniques, reviewed in this paper, demonstrate that adjacent compartments are at successive stages. Three compartments, Illawarra, Shoalhaven and Moruya, are compared, each with different catchment characteristics and different levels of human intervention. Landform change and sediment accumulation at millennial timescales enable estimates of past sediment accretion (vertical accumulation) and horizontal displacement of shorelines (particularly progradation), as a first step towards quantifying volumetric changes of morphology. Lake Illawarra is a barrier estuary at an early stage of infill, but land-use change, urbanisation, and engineering structures at the entrance have accelerated rates of sediment accumulation. The Shoalhaven River has infilled its estuary and delivers sand to the coast. It has been subject to several conspicuous anthropogenic interventions. At Moruya, ongoing supply of sand, primarily from offshore rather than from the catchment, has resulted in beach-ridge plains (strandplains) with changes in their alongshore inter-connectivity driven by differential embayment infilling. Millennial-scale geomorphology indicates landform change providing a means to determine natural trajectories of sediment transfer. However, variability is apparent at century and decadal timescales, compounded by various anthropogenic interventions. Disentangling natural and anthropogenic influences will be necessary to provide greater confidence in estimating past and present sediment budgets. Assessing sand sources and transport rates is important in relation to engineering interventions at entrances, and long-term resilience of coastal habitats. Such issues are the focus of coastal management programs, and this synthesis emphasises the relevance of a sediment budget approach to understand contemporary sediment pathways and provide an indication of future response to engineering interventions and sensitivity to climate change.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Impact of climate change on volcanic processes: current understanding and future challenges - Thomas J. Aubry; Jamie I. Farquharson; Colin R. Rowell; Sebastian F. L. Watt; Virginie Pinel; Frances Beckett; John Fasullo; Peter O. Hopcroft; David M. Pyle; Anja Schmidt; John Staunton Sykes (Bulletin of Volcanology, 2022)
The impacts of volcanic eruptions on climate are increasingly well understood, but the mirror question of how climate changes affect volcanic systems and processes, which we term “climate-volcano impacts”, remains understudied. Accelerating research on this topic is critical in view of rapid climate change driven by anthropogenic activities. Over the last two decades, we have improved our understanding of how mass distribution on the Earth’s surface, in particular changes in ice and water distribution linked to glacial cycles, affects mantle melting, crustal magmatic processing and eruption rates. New hypotheses on the impacts of climate change on eruption processes have also emerged, including how eruption style and volcanic plume rise are affected by changing surface and atmospheric conditions, and how volcanic sulfate aerosol lifecycle, radiative forcing and climate impacts are modulated by background climate conditions. Future improvements in past climate reconstructions and current climate observations, volcanic eruption records and volcano monitoring, and numerical models all have a role in advancing our understanding of climate-volcano impacts. Important mechanisms remain to be explored, such as how changes in atmospheric circulation and precipitation will affect the volcanic ash life cycle. Fostering a holistic and interdisciplinary approach to climate-volcano impacts is critical to gain a full picture of how ongoing climate changes may affect the environmental and societal impacts of volcanic activity.

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Development and application of a contaminant transport model for groundwater remediation and reservoir protection: a case study from India - Colins Johnny Jesudhas; Sashikkumar Madurai Chidambaram; Rajesh Banu Jeyakumar; Eldon R. Rene (Environmental Monitoring and Assessment, 2022)

Tracking the early stages of an invasion with biotelemetry: behaviour of round goby (Neogobius melanostomus) in Canada’s historic Rideau Canal - Jordanna N. Bergman; Graham D. Raby; Kate L. Neigel; Colin D. Rennie; Sigal Balshine; Joseph R. Bennett; Aaron T. Fisk; Steven J. Cooke (Biological Invasions, 2022)

An opinion piece: the evolutionary and ecological consequences of changing selection pressures on marine migration in Atlantic salmon - Colin E. Adams; Louise Chavarie; Jessica R. Rodger; Hannele M. Honkanen; Davide Thambithurai; Matthew P. Newton (Journal of Fish Biology, 2022)
There are strong signals that the selection forces favouring the expression of long‐distance sea migration by Atlantic salmon ( Salmo salar ) are changing. Unlike many other behavioural traits, the costs of migration are incurred before any fitness benefits become apparent to the migrant. The expression of this behaviour has thus been shaped by selection forces over multiple generations and cannot respond to short interval (within a single generation) environmental change as many other behavioural traits can. Here we provide a framework to examine the evolutionary and ecological consequences of a sustained increase in migration cost. We argue that Atlantic salmon may have entered an evolutionary trap , where long‐distance sea migration has become maladaptive because of shifting environmental conditions. We predict that if higher migration costs (affecting survivorship and ultimately fitness) persist, then shifting selection pressures will result in continuing declines in population size. We suggest, however, that in some populations there is demonstrable capacity for evolutionary rescue responses within the species which is to be found in the variation in the expression of migration. Under a scenario of low to moderate change in the selection forces that previously promoted migration, we argue that disruptive, sex‐based selection would result in partial migration, where females retain sea migration but with anadromy loss predominantly in males. With more acute selection forces, anadromy may be strongly selected against, under these conditions both sexes may become freshwater resident. We suggest that as the migration costs appear to be higher in catchments with standing waters, then this outcome is more likely in such systems. We also speculate that as a result of the genetic structuring in this species, not all populations may have the capacity to respond adequately to change. The consequences of this for the species and its management are discussed.

Structure and permeability of the egg capsule of the placental Australian sharpnose shark, Rhizoprionodon taylori - Alice L. Buddle; James U. Van Dyke; Michael B. Thompson; Colin A. Simpfendorfer; Christopher R. Murphy; Margot L. Day; Camilla M. Whittington (Journal of Comparative Physiology B, 2022)
Shark placentae are derived from modifications to the fetal yolk sac and the maternal uterine mucosa. In almost all placental sharks, embryonic development occurs in an egg capsule that remains intact for the entire pregnancy, separating the fetal tissues from the maternal tissues at the placental interface. Here, we investigate the structure and permeability of the egg capsules that surround developing embryos of the placental Australian sharpnose shark ( Rhizoprionodon taylori ) during late pregnancy. The egg capsule is an acellular fibrous structure that is 0.42 ± 0.04 μm thick at the placental interface between the yolk sac and uterine tissues, and 0.67 ± 0.08 μm thick in the paraplacental regions. This is the thinnest egg capsule of any placental shark measured so far, which may increase the diffusion rate of respiratory gases, fetal wastes, water and nutrients between maternal and fetal tissues. Molecules smaller than or equal to ~ 1000 Da can diffuse through the egg capsule, but larger proteins (~ 3000–26,000 Da) cannot. Similar permeability characteristics between the egg capsule of R. taylori and other placental sharks suggest that molecular size is an important determinant of the molecules that can be exchanged between the mother and her embryos during pregnancy.

Sleeping Site and Tree Selection by Bale Monkeys (Chlorocebus djamdjamensis) at Kokosa Forest Fragment in Southern Ethiopia - Addisu Mekonnen; Peter J. Fashing; Vivek V. Venkataraman; Colin A. Chapman; Nils Chr. Stenseth; R. Adriana Hernandez-Aguilar (International Journal of Primatology, 2021)
Although selecting advantageous sleeping sites is crucial for nonhuman primates, the extent to which different factors contribute to their selection remains largely unknown for many species. We investigated hypotheses relating to predator avoidance, food access, and thermoregulation to explain the sleeping behavior of Bale monkeys ( Chlorocebus djamdjamensis ) occupying a degraded fragmented forest, Kokosa, in the southern Ethiopian Highlands. We found that the study group reused 11 out of 20 sleeping sites used during the 42 study days over a 6-month period. Sleeping sites were usually close to the last feeding trees of the day (mean distance =15.2 m) and/or the first feeding trees of the next morning (mean distance = 13.5 m). This may reflect an attempt to maximize feeding efficiency and reduce travel costs. Compared to the mean trees in the study area, sleeping trees were significantly shorter. Bale monkeys selected sleeping places in trees with high foliage density above and below them, lending support to the hypothesis that they select sleeping places that can conceal them from predators and at the same time offer shelter from cold weather. The monkeys also frequently huddled at night. Our results suggest that predator avoidance, access to food resources, and thermoregulation all likely influence the selection of sleeping sites by Bale monkeys.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Incursions of divergent genotypes, evolution of virulence and host jumps shape a continental clonal population of the stripe rust pathogen Puccinia striiformis - Yi Ding; Will S. Cuddy; Colin R. Wellings; Peng Zhang; Tine Thach; Mogens S. Hovmøller; Dinah Qutob; Gurcharn S. Brar; Hadley R. Kutcher; Robert F. Park (Molecular Ecology, 2021)
Long‐distance migration and host adaptation by transboundary plant pathogens often brings detrimental effects to important agroecosystems. Efficient surveillance as a basis for responding to the dynamics of such pathogens is often hampered by a lack of information on incursion origin, evolutionary pathways and the genetic basis of rapidly evolving virulence across larger timescales. Here, we studied these genetic features by using historical isolates of the obligate biotrophic pathogen Puccinia striiformis f. sp. tritici ( Pst ), which causes one of the most widespread and devastating diseases, stripe (yellow) rust, of wheat. Through a combination of genotypic, phenotypic and genomic analyses, we assigned eight Pst isolates representing putative exotic Pst incursions into Australia to four previously defined genetic groups, PstS0, PstS1, PstS10 and PstS13. We showed that isolates of an additional incursion of P . striiformis , known locally as P . striiformis f. sp. pseudo ‐ hordei , had a new and unique multilocus SSR genotype (MLG). We provide results of overall genomic variation of representative Pst isolates from each genetic group by comparative genomic analyses. We showed that isolates within the PstS1 and PstS13 genetic groups are most distinct at the whole‐genome variant level from isolates belonging to genetic group PstS0, whereas the isolate from the PstS10 genetic group is intermediate. We further explored variable gene content, including putative effectors, representing both shared but also unique genetic changes that have occurred following introduction, some of which may additionally account for local adaptation of these isolates to triticale. Our genotypic and genomic data revealed new genetic insights into the evolution of diverse phenotypes of rust pathogens following incursion into a geographically isolated continental region.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

An efficient and high-yielding method for extraction and purification of linamarin from Cassava; in vitro biological evaluation - K. A. U. Samanthi; Dhanushi T. Welideniya; Anjana Delpe Acharige; Sameera R. Samarakoon; Rajitha K. Rathnayaka; Madhavi de Silva; Shashika S. Perera; Colin Pieris; Umayangani K. Wanninayake; Adeesha Jayathilaka; Veranja Karunaratne; G. A. J. Amaratunga; et al. (Natural Product Research, 2021)

Searching for structure in collective systems - Colin R. Twomey; Andrew T. Hartnett; Matthew M. G. Sosna; Pawel Romanczuk (Theory in Biosciences, 2021)
From fish schools and bird flocks to biofilms and neural networks, collective systems in nature are made up of many mutually influencing individuals that interact locally to produce large-scale coordinated behavior. Although coordination is central to what it means to behave collectively, measures of large-scale coordination in these systems are ad hoc and system specific. The lack of a common quantitative scale makes broad cross-system comparisons difficult. Here we identify a system-independent measure of coordination based on an information-theoretic measure of multivariate dependence and show it can be used in practice to give a new view of even classic, well-studied collective systems. Moreover, we use this measure to derive a novel method for finding the most coordinated components within a system and demonstrate how this can be used in practice to reveal intrasystem organizational structure.

Age estimation comparison between whole and thin-sectioned otoliths and pelvic fin-ray sections of long-lived lake trout, Salvelinus namaycush, from Great Bear Lake, Northwest Territories, Canada - Colin P. Gallagher; Rick J. Wastle; Julie R. Marentette; Louise Chavarie; Kimberly L. Howland (Polar Biology, 2021)
Studies to determine precision and bias of both methods and age-readers are important to evaluate reliability of age data used for developing fisheries management objectives. We assessed within-reader, between-reader, and between-method precision (coefficient of variation, CV%) and bias of age estimations for long-lived lake trout, Salvelinus namaycush, from Great Bear Lake using three readers with different levels of experience. The assessment used independent age estimates ( n = 3 per reader) from whole and transverse-sectioned otoliths (range = 1–67 years), and pelvic fin-ray sections (range = 3–26 years). We also examined between-method differences in assigned confidence scores. Within readers, age estimates from sectioned otoliths were more precise (2.6–3.0%) than whole (3.6–4.5%) otoliths. Between whole and sectioned otoliths, precision of age estimates was 5.4% and bias was low up to age 20. Age was typically under-estimated from whole otoliths compared to sections for fish ≥ 34 years. Increased reader confidence was correlated with greater precision and younger age estimates, particularly for whole otoliths, but less so for fin rays. Age was estimated with higher confidence from otolith sections than other methods. The least experienced reader estimated age with the lowest precision, and between-reader bias was evident among older ages. Age was consistently under-estimated and less precise from pelvic fins compared to sectioned otoliths, and are therefore an unsuitable non-lethal alternative. Sectioned otoliths revealed longevity was greater (67 years) than historically documented using whole otoliths (53 years) for these fish. Our findings contribute to those relying on otoliths or pelvic fin rays to estimate ages of long-lived lake trout populations, which are a key component of freshwater fauna in polar North America.

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

Pharmaceutical design of a delivery system for the bacteriocin lacticin 3147 - Aoibhín Ryan; Pratikkumar Patel; Paula M. O’Connor; R. Paul Ross; Colin Hill; Sarah P. Hudson (Drug Delivery and Translational Research, 2021)
Lacticin 3147 is a dual-acting two-peptide bacteriocin which is generally active against Gram-positive bacteria, including Listeria monocytogenes and antimicrobial-resistant bacteria such as Closteroides difficile in the colon. L. monocytogenes infections can cause life-long effects in the elderly and vulnerable and can cause severe complications in pregnant women. C. difficile causes one of the most common healthcare-associated infections and can be fatal in vulnerable groups such as the elderly. Although lacticin 3147 is degraded by intestinal proteases and has poor aqueous solubility, encapsulation of the bacteriocin could enable its use as an antimicrobial for treating these bacterial infections locally in the gastrointestinal tract. Lacticin 3147 displayed activity in aqueous solutions at a range of pH values and in gastric and intestinal fluids. Exposure to trypsin and α-chymotrypsin resulted in complete inactivation, implying that lacticin 3147 should be protected from these enzymes to achieve successful local delivery to the gastrointestinal tract. The amount of lacticin 3147 dissolved, i.e. its solution concentration, in water or buffered solutions at pH 1.6 and 7.4 was low and varied with time but increased and was stabilized in gastrointestinal fluids by the phospholipid and bile salt components present. Thus, the feasibility of a solid lipid nanoparticle (SLN) delivery system for local administration of lacticin 3147 was investigated. Bacteriocin activity was observed after encapsulation and release from a lipid matrix. Moreover, activity was seen after exposure to degrading enzymes. Further optimization of SLN delivery systems could enable the successful pharmaceutical development of active lacticin 3147 as an alternative to traditional antibiotics. Graphical abstract

Intra-specific variation in movement and habitat connectivity of a mobile predator revealed by acoustic telemetry and network analyses - Mario Espinoza; Elodie J. I. Lédée; Amy F. Smoothey; Michelle R. Heupel; Victor M. Peddemors; Andrew J. Tobin; Colin A. Simpfendorfer (Marine Biology, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Low dispersal and ploidy differences in a grass maintain photosynthetic diversity despite gene flow and habitat overlap - Jill K. Olofsson; Emma V. Curran; Florence Nyirenda; Matheus E. Bianconi; Luke T. Dunning; Vanja Milenkovic; Graciela Sotelo; Oriane Hidalgo; Robyn F. Powell; Marjorie R. Lundgren; Ilia J. Leitch; Patrik Nosil; et al. (Molecular Ecology, 2021)
Geographical isolation facilitates the emergence of distinct phenotypes within a single species, but reproductive barriers or selection are needed to maintain the polymorphism after secondary contact. Here, we explore the processes that maintain intraspecific variation of C 4 photosynthesis, a complex trait that results from the combined action of multiple genes. The grass Alloteropsis semialata includes C 4 and non‐C 4 populations, which have coexisted as a polyploid series for more than 1 million years in the miombo woodlands of Africa. Using population genomics, we show that there is genome‐wide divergence for the photosynthetic types, but the current geographical distribution does not reflect a simple habitat displacement scenario as the genetic clusters overlap, being occasionally mixed within a given habitat. Despite evidence of recurrent introgression between non‐C 4 and C 4 groups, in both diploids and polyploids, the distinct genetic lineages retain their identity, potentially because of selection against hybrids. Coupled with strong isolation by distance within each genetic group, this selection created a geographical mosaic of photosynthetic types. Diploid C 4 and non‐C 4 types never grew together, and the C 4 type from mixed populations constantly belonged to the hexaploid lineage. By limiting reproductive interactions between photosynthetic types, the ploidy difference probably allows their co‐occurrence, reinforcing the functional diversity within this species. Together, these factors enabled the persistence of divergent physiological traits of ecological importance within a single species despite gene flow and habitat overlap.

Functional importance and diversity of fungi during standing grass litter decomposition - Matthew B. Lodato; Jerrid S. Boyette; Rachel A. Smilo; Colin R. Jackson; Halvor M. Halvorson; Kevin A. Kuehn (Oecologia, 2021)

Highly diverse mesophotic reef fish communities in Raja Ampat, West Papua - Dominic A. Andradi-Brown; Angela J. E. Beer; Luigi Colin; Hastuti; Catherine E. I. Head; Nur Ismu Hidayat; Steven J. Lindfield; Catherine R. Mitchell; Defy N. Pada; Nikola M. Piesinger; Purwanto; Gabby N. Ahmadia (Coral Reefs, 2021)
Mesophotic coral ecosystems (MCEs; reefs 30–150 m depth) are poorly studied, with existing research heavily geographically biased away from the most species-rich reef regions. Yet, MCEs are of high interest because of their unique species and potential to act as refuges from the impacts of fishing. Using baited remote underwater video systems, we surveyed reef fish communities from 2 to 85 m depths throughout the Raja Ampat archipelago in West Papua, Indonesia—an area considered the heart of the Coral Triangle where coral reef biodiversity is greatest. We sought to provide the first assessment of fish communities across this depth gradient in the region and identify whether human population density and market access differently affected fish abundance based on depth. Here we show that—similar to shallow reefs—Raja Ampat MCEs are exceptionally diverse, with 152 fish species recorded at depths greater than 40 m. We found that fish community structures were highly depth driven, with declines in fish abundance at increased depth. In contrast to previous studies elsewhere in the world, we found that the proportion of planktivores declined across the shallow reef to MCE depth gradient. While greater human population density correlated with lower Epinephelidae and Lutjanidae abundance (two key fisheries families), we did not find evidence that MCEs provide a depth refuge from fishing. Surprisingly, we also found that fish abundance declined at greater distances from the major regional market—likely caused by historical fisheries pressure in more remote areas. These results both expand upon and contrast some previously established MCE-depth patterns and human impact patterns on fish communities, suggesting that regional context and historical pressures matters. Our findings highlight the need for future MCE studies within the Coral Triangle region.

Monitoring water status in apple trees using a sensitive morning crop water stress index* - Abdelmoneim Z. Mohamed; Yasin Osroosh; R. Troy Peters; Travis Bates; Colin S. Campbell; Francesc Ferrer‐Alegre (Irrigation and Drainage, 2021)
The crop water stress index (CWSI) has shown to be a good indicator of water status in fruit trees. Conventional CWSI measured over solar noon is widely used to monitor plant water status. This study compared the theoretical CWSI averaged over morning hours, CWSI mo , and over solar noon hours, CWSI md , of apple trees. This study also assessed their sensitivity to the changes in soil water status (soil water deficit [SWD, %] and soil water potential [SWP, kPa]) at different root zone depths. Four different types of commercial and experimental apple orchards with different characteristics growing under semi‐arid conditions in Washington State, United States, were chosen to assess CWSI mo against CWSI md sensitivity to soil water status. In some of these locations, soil water status ranged from fully watered to severely stressed (low water deficit to high water deficit). Ground‐based thermal and microclimate measurements were recorded continuously at 10‐s intervals and acquired for the 15‐min average on a daily basis throughout the study period. The linear relationship between SWD and CWSI mo at the effective root zone depth (average of 0–150 mm and 0–460 mm) resulted in a slightly higher correlation ( R 2 = 0.42–0.64, p md ( R 2 = 0.32–0.60, p mo and SWP ( R 2 = 0.38–0.69, p mo and SWD, while SWP was less correlated with CWSI md ( R 2 = 0.33–0.55, p mo and CWSI md was observed using a nadir view orientation thermal measurement. The CWSI mo showed higher sensitivity to SWP than SWD.

Glossary on atmospheric electricity and its effects on biology - Pablo Fdez-Arroyabe; Konstantinos Kourtidis; Christos Haldoupis; Snezana Savoska; James Matthews; Lluis M. Mir; Pavlos Kassomenos; Michal Cifra; Susana Barbosa; Xuemeng Chen; Snezana Dragovic; Christos Consoulas; et al. (International Journal of Biometeorology, 2021)

Challenges in coupling atmospheric electricity with biological systems - Ellard R. Hunting; James Matthews; Pablo Fernández de Arróyabe Hernáez; Sam J. England; Konstantinos Kourtidis; Kuang Koh; Keri Nicoll; R. Giles Harrison; Konstantine Manser; Colin Price; Snezana Dragovic; Michal Cifra; et al. (International Journal of Biometeorology, 2021)
The atmosphere is host to a complex electric environment, ranging from a global electric circuit generating fluctuating atmospheric electric fields to local lightning strikes and ions. While research on interactions of organisms with their electrical environment is deeply rooted in the aquatic environment, it has hitherto been confined to interactions with local electrical phenomena and organismal perception of electric fields. However, there is emerging evidence of coupling between large- and small-scale atmospheric electrical phenomena and various biological processes in terrestrial environments that even appear to be tied to continental waters. Here, we synthesize our current understanding of this connectivity, discussing how atmospheric electricity can affect various levels of biological organization across multiple ecosystems. We identify opportunities for research, highlighting its complexity and interdisciplinary nature and draw attention to both conceptual and technical challenges lying ahead of our future understanding of the relationship between atmospheric electricity and the organization and functioning of biological systems.

Techniques for In Vivo Measurement of Ligament and Tendon Strain: A Review - Qiang Zhang; Naomi C. Adam; S. H. Hosseini Nasab; William R. Taylor; Colin R. Smith (Annals of Biomedical Engineering, 2021)
The critical clinical and scientific insights achieved through knowledge of in vivo musculoskeletal soft tissue strains has motivated the development of relevant measurement techniques. This review provides a comprehensive summary of the key findings, limitations, and clinical impacts of these techniques to quantify musculoskeletal soft tissue strains during dynamic movements. Current technologies generally leverage three techniques to quantify in vivo strain patterns, including implantable strain sensors, virtual fibre elongation, and ultrasound. (1) Implantable strain sensors enable direct measurements of tissue strains with high accuracy and minimal artefact, but are highly invasive and current designs are not clinically viable. (2) The virtual fibre elongation method tracks the relative displacement of tissue attachments to measure strains in both deep and superficial tissues. However, the associated imaging techniques often require exposure to radiation, limit the activities that can be performed, and only quantify bone-to-bone tissue strains. (3) Ultrasound methods enable safe and non-invasive imaging of soft tissue deformation. However, ultrasound can only image superficial tissues, and measurements are confounded by out-of-plane tissue motion. Finally, all in vivo strain measurement methods are limited in their ability to establish the slack length of musculoskeletal soft tissue structures. Despite the many challenges and limitations of these measurement techniques, knowledge of in vivo soft tissue strain has led to improved clinical treatments for many musculoskeletal pathologies including anterior cruciate ligament reconstruction, Achilles tendon repair, and total knee replacement. This review provides a comprehensive understanding of these measurement techniques and identifies the key features of in vivo strain measurement that can facilitate innovative personalized sports medicine treatment.

Warming temperatures could expose more than 1.3 billion new people to Zika virus risk by 2050 - Sadie J. Ryan; Colin J. Carlson; Blanka Tesla; Matthew H. Bonds; Calistus N. Ngonghala; Erin A. Mordecai; Leah R. Johnson; Courtney C. Murdock (Global Change Biology, 2021)
In the aftermath of the 2015 pandemic of Zika virus (ZIKV), concerns over links between climate change and emerging arboviruses have become more pressing. Given the potential that much of the world might remain at risk from the virus, we used a previously established temperature‐dependent transmission model for ZIKV to project climate change impacts on transmission suitability risk by mid‐century (a generation into the future). Based on these model predictions, in the worst‐case scenario, over 1.3 billion new people could face suitable transmission temperatures for ZIKV by 2050. The next generation will face substantially increased ZIKV transmission temperature suitability in North America and Europe, where naïve populations might be particularly vulnerable. Mitigating climate change even to moderate emissions scenarios could significantly reduce global expansion of climates suitable for ZIKV transmission, potentially protecting around 200 million people. Given these suitability risk projections, we suggest an increased priority on research establishing the immune history of vulnerable populations, modeling when and where the next ZIKV outbreak might occur, evaluating the efficacy of conventional and novel intervention measures, and increasing surveillance efforts to prevent further expansion of ZIKV.

Volatile Organic Compounds as Insect Repellents and Plant Elicitors: an Integrated Pest Management (IPM) Strategy for Glasshouse Whitefly (Trialeurodes vaporariorum) - Niall J.A. Conboy; Thomas McDaniel; David George; Adam Ormerod; Martin Edwards; Paul Donohoe; Angharad M. R Gatehouse; Colin R. Tosh (Journal of Chemical Ecology, 2020)
The glasshouse whitefly ( Trialeurodes vaporariorum Westwood) is a polyphagous arthropod pest that is of particular detriment to glasshouse grown tomato ( Solanum lycopersicum ) across temperate regions of the world. Control of whiteflies with synthetic pesticides has resulted in the evolution of resistant genotypes and a reduction in natural enemies, thus highlighting the need for environmentally sound control strategies. Volatile organic compounds (VOCs) offer an environmentally benign alternative to synthetic chemical sprays and this study explored the use of VOCs as insect repellents and plant defence elicitors to control whiteflies on tomato in a commercial glasshouse setting. Limonene in the form of a volatile dispenser system was found to successfully repel whitefly from the target crop and increased fruit yield by 32% during a heavy whitefly infestation. Analysis of tomato herbivore induced plant volatiles (HIPVs) led us to select methyl salicylate (MeSA) as the plant elicitor and application of MeSA to un-infested tomato plants was found to successfully reduce whitefly population development and increase yield by 11%, although this difference was marginally statistically significant. Combination of these two methods was also effective but whitefly abundance in combined plots was similar to the standalone limonene treatment across the course of the experiment. All of the VOC based control methods we used had a negative impact on whitefly performance, with more pronounced effects during the first few weeks of infestation. In subsequent laboratory experiments, we found elevated peroxidase (POD) activity and a significant increase in TPX1 and PR1 transcripts in MeSA treated plants. This led us to deduce that MeSA immediately induced plant defences, rather than priming them. We did however see evidence for residual priming, as plants treated with MeSA and infested with whiteflies produced significantly higher levels of POD activity than whitefly infestation alone. Despite the fact that our treatments failed to synergise, our methods can be optimised further, and the effectiveness of the standalone treatments is promising for future studies. In particular, our repellent limonene dispensers were extremely effective at deterring whiteflies and offer a low economic cost and easy to implement whitefly control option. The methods we have used here could be incorporated into current integrated pest management (IPM) systems, a sustainable approach to pest control which will be central to our efforts to manage whitefly populations under glass in the future.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Inter‐ and intra‐specific interactions affecting crustacean trap fisheries—Implications for management - Daniel J. Skerritt; R. Colin A. Bannister; Nicholas V. C. Polunin; Clare Fitzsimmons (Fisheries Management and Ecology, 2020)
The UK coastal trap fisheries target two key species, European lobster Homarus gammarus (L.) and brown crab Cancer pagurus L. Their stock status is assessed periodically using size‐based, yield‐per‐recruit analysis. Fishery trends are described using landings and, where available, effort data to estimate catch per unit of effort (CPUE), nominally proportional to abundance. Despite being caught together, assessments assume that concurrent capture of these species does not distort their individual CPUE estimates. Here, an in situ experiment tested impacts of inter‐specific and intra‐specific interactions by pre‐loading baited traps with different species and observing subsequent catches. Pre‐loaded European lobster significantly reduced brown crab catches, whereas, other species produced no such effects. The findings highlight the likely inconsistency of using CPUE as an index of abundance if landings data originate from a mixed‐species fishery in which species interactions and targeting behaviour of fishers are unknown or un‐quantified.

Drivers of the enhanced decline of land near-surface relative humidity to abrupt 4xCO2 in CNRM-CM6-1 - Hervé Douville; B. Decharme; C. Delire; J. Colin; E. Joetzjer; R. Roehrig; D. Saint-Martin; T. Oudar; R. Stchepounoff; A. Voldoire (Climate Dynamics, 2020)

Incorporating connectivity into conservation planning for the optimal representation of multiple species and ecosystem services - Sara H. Williams; Sarah A. Scriven; David F. R. P. Burslem; Jane K. Hill; Glen Reynolds; Agnes L. Agama; Frederick Kugan; Colin R. Maycock; Eyen Khoo; Alexander Y. L. Hastie; John B. Sugau; Reuben Nilus; et al. (Conservation Biology, 2020)
Conservation planning tends to focus on protecting species’ ranges or landscape connectivity but seldom both—particularly in the case of diverse taxonomic assemblages and multiple planning goals. Therefore, information on potential trade‐offs between maintaining landscape connectivity and achieving other conservation objectives is lacking. We developed an optimization approach to prioritize the maximal protection of species’ ranges, ecosystem types, and forest carbon stocks, while also including habitat connectivity for range‐shifting species and dispersal corridors to link protected area. We applied our approach to Sabah, Malaysia, where the state government mandated an increase in protected‐area coverage of approximately 305,000 ha but did not specify where new protected areas should be. Compared with a conservation planning approach that did not incorporate the 2 connectivity features, our approach increased the protection of dispersal corridors and elevational connectivity by 13% and 21%, respectively. Coverage of vertebrate and plant species’ ranges and forest types were the same whether connectivity was included or excluded. Our approach protected 2% less forest carbon and 3% less butterfly range than when connectivity features were not included. Hence, the inclusion of connectivity into conservation planning can generate large increases in the protection of landscape connectivity with minimal loss of representation of other conservation targets.

Environmental analyses to inform transitions to sustainable diets in developing countries: case studies for Vietnam and Kenya - Martin C. Heller; Abhijeet Walchale; Brent R. Heard; Lesli Hoey; Colin K. Khoury; Stef De Haan; Dharani Dhar Burra; Thi Thanh Duong; Jamleck Osiemo; Thi Huong Trinh; Andrew D. Jones (The International Journal of Life Cycle Assessment, 2020)

Xentry-Gap19 inhibits Connexin43 hemichannel opening especially during hypoxic injury - Frazer P. Coutinho; Colin R. Green; Monica L. Acosta; Ilva D. Rupenthal (Drug Delivery and Translational Research, 2020)

Personality factors and cerebral glucose metabolism in community-dwelling older adults - Hamid R. Sohrabi; Kathryn Goozee; Michael Weinborn; Kaikai Shen; Belinda M. Brown; Stephanie R. Rainey-Smith; Olivier Salvado; Kevin Taddei; Romola S. Bucks; Paul Maruff; Simon M. Laws; Nat Lenzo; et al. (Brain Structure and Function, 2020)

Host Range Expansion of an Endemic Insect Herbivore is Associated With High Nitrogen and Low Fibre Content in Exotic Pasture Plants - Sylvester R. Atijegbe; Sarah Mansfield; Colin M. Ferguson; Susan P. Worner; Michael Rostás (Journal of Chemical Ecology, 2020)

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Strain-specificity in the hydrogen sulphide signalling network following dietary restriction in recombinant inbred mice - Stephen E. Wilkie; Lorna Mulvey; William A. Sands; Diana E. Marcu; Roderick N. Carter; Nicholas M. Morton; Christopher Hine; James R. Mitchell; Colin Selman (GeroScience, 2020)
Modulation of the ageing process by dietary restriction (DR) across multiple taxa is well established. While the exact mechanism through which DR acts remains elusive, the gasotransmitter hydrogen sulphide (H 2 S) may play an important role. We employed a comparative-type approach using females from three ILSXISS recombinant inbred mouse strains previously reported to show differential lifespan responses following 40% DR. Following long-term (10 months) 40% DR, strain TejJ89—reported to show lifespan extension under DR—exhibited elevated hepatic H 2 S production relative to its strain-specific ad libitum (AL) control. Strain TejJ48 (no reported lifespan effect following 40% DR) exhibited significantly reduced hepatic H 2 S production, while H 2 S production was unaffected by DR in strain TejJ114 (shortened lifespan reported following 40% DR). These differences in H 2 S production were reflected in highly divergent gene and protein expression profiles of the major H 2 S production and disposal enzymes across strains. Increased hepatic H 2 S production in TejJ89 mice was associated with elevation of the mitochondrial H 2 S-producing enzyme 3-mercaptopyruvate sulfurtransferase (MPST). Our findings further support the potential role of H 2 S in DR-induced longevity and indicate the presence of genotypic-specificity in the production and disposal of hepatic H 2 S in response to 40% DR in mice.

Correction to: The Capacity of Generic Musculoskeletal Simulations to Predict Knee Joint Loading Using the CAMS-Knee Datasets - Zohreh Imani Nejad; Khalil Khalili; Seyyed Hamed Hosseini Nasab; Pascal Schütz; Philipp Damm; Adam Trepczynski; William R. Taylor; Colin R. Smith (Annals of Biomedical Engineering, 2020)

The Capacity of Generic Musculoskeletal Simulations to Predict Knee Joint Loading Using the CAMS-Knee Datasets - Zohreh Imani Nejad; Khalil Khalili; Seyyed Hamed Hosseini Nasab; Pascal Schütz; Philipp Damm; Adam Trepczynski; William R. Taylor; Colin R. Smith (Annals of Biomedical Engineering, 2020)
Musculoskeletal models enable non-invasive estimation of knee contact forces (KCFs) during functional movements. However, the redundant nature of the musculoskeletal system and uncertainty in model parameters necessitates that model predictions are critically evaluated. This study compared KCF and muscle activation patterns predicted using a scaled generic model and OpenSim static optimization tool against in vivo measurements from six patients in the CAMS-knee datasets during level walking and squatting. Generally, the total KCFs were under-predicted (RMS: 47.55%BW, R 2 : 0.92) throughout the gait cycle, but substiantially over-predicted (RMS: 105.7%BW, R 2 : 0.81) during squatting. To understand the underlying etiology of the errors, muscle activations were compared to electromyography (EMG) signals, and showed good agreement during level walking. For squatting, however, the muscle activations showed large descrepancies especially for the biceps femoris long head. Errors in the predicted KCF and muscle activation patterns were greatest during deep squat. Hence suggesting that the errors mainly originate from muscle represented at the hip and an associated muscle co-contraction at the knee. Furthermore, there were substaintial differences in the ranking of subjects and activities based on peak KCFs in the simulations versus measurements. Thus, future simulation study designs must account for subject-specific uncertainties in musculoskeletal predictions.

Sentiment analysis as a measure of conservation culture in scientific literature - Robert J. Lennox; Diogo Veríssimo; William M. Twardek; Colin R. Davis; Ivan Jarić (Conservation Biology, 2020)
Culturomics is emerging as an important field within science, as a way to measure attitudes and beliefs and their dynamics across time and space via quantitative analysis of digitized data from literature, news, film, social media, and more. Sentiment analysis is a culturomics tool that, within the last decade, has provided a means to quantify the polarity of attitudes expressed within various media. Conservation science is a crisis discipline; therefore, accurate and effective communication are paramount. We investigated how conservation scientists communicate their findings through scientific journal articles. We analyzed 15,001 abstracts from articles published from 1998 to 2017 in 6 conservation‐focused journals selected based on indexing in scientific databases. Articles were categorized by year, focal taxa, and the conservation status of the focal species. We calculated mean sentiment score for each abstract (mean adjusted z score) based on 4 lexicons (Jockers‐Rinker, National Research Council, Bing, and AFINN). We found a significant positive annual trend in the sentiment scores of articles. We also observed a significant trend toward increasing negativity along the spectrum of conservation status categories (i.e., from least concern to extinct). There were some clear differences in the sentiments with which research on different taxa was reported, however. For example, abstracts mentioning lobe finned fishes tended to have high sentiment scores, which could be related to the rediscovery of the coelacanth driving a positive narrative. Contrastingly, abstracts mentioning elasmobranchs had low scores, possibly reflecting the negative sentiment score associated with the word shark . Sentiment analysis has applications in science, especially as it pertains to conservation psychology, and we suggest a new science‐based lexicon be developed specifically for the field of conservation.

The global distribution of grass functional traits within grassy biomes - Emma C. Jardine; Gavin H. Thomas; Elisabeth J. Forrestel; Caroline E. R. Lehmann; Colin P. Osborne (Journal of Biogeography, 2020)
Aim The sorting of functional traits along environmental gradients is an important driver of community and landscape scale patterns of functional diversity. However, the significance of environmental factors in driving functional gradients within biomes and across continents remains poorly understood. Here, we evaluate the relationship of soil nutrients and climate to leaf traits in grasses (Poaceae) that are hypothesized to reflect different strategies of resource use along gradients of resource availability. Location Global. Taxon Poaceae. Methods We made direct measurements on herbarium specimens to compile a global dataset of functional traits and realized environmental niche for 279 grass species that are common in grassland and savanna biomes. We examined the strength and direction of correlations between pairwise trait combinations and measured the distribution of traits in relation to gradients of soil properties and climate, while accounting for phylogenetic relatedness. Results Leaf trait variation among species follows two orthogonal axes. One axis represents leaf size and plant height, and we showed positive scaling relationships between these size‐related traits. The other axis corresponds to economic traits associated with resource acquisition and allocation, including leaf tensile strength (LTS), specific leaf area (SLA) and leaf nitrogen content (LNC). Global‐scale variation in LNC was primarily correlated with soil nutrients, while LTS, SLA and size‐related traits showed weak relationships to environment. However, most of the trait variation occurred within different vegetation types, independent of large‐scale environmental gradients. Main conclusions Our work provides evidence among grasses for relationships at the global scale between leaf economic traits and soil fertility, and for an influence of aridity on traits related to plant size. However, large unexplained variance and strong phylogenetic signal in the model residuals imply that at this scale the evolution of functional traits is driven by factors beyond contemporary environmental or climatic conditions.

Hydrothermal Activity and Seismicity at Teahitia Seamount: Reactivation of the Society Islands Hotspot? - Christopher R. German; Joseph A. Resing; Guangyu Xu; Isobel A. Yeo; Sharon L. Walker; Colin W. Devey; James W. Moffett; Gregory A. Cutter; Olivier Hyvernaud; Dominique Reymond (Frontiers in Marine Science, 2020)

Prostate-Specimen Antigen (PSA) Screening and Shared Decision Making Among Deaf and Hearing Male Patients - Poorna Kushalnagar; Colin Hill; Shane Carrizales; Georgia R. Sadler (Journal of Cancer Education, 2020)

A new Myzomela honeyeater (Meliphagidae) from the highlands of Alor Island, Indonesia - Mohammad Irham; Hidayat Ashari; Suparno; Colin R. Trainor; Philippe Verbelen; Meng Yue Wu; Frank E. Rheindt (Journal of Ornithology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2019)

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Impacts of acidification on brown trout Salmo trutta populations and the contribution of stocking to population recovery and genetic diversity - Paulo A. Prodöhl; Andrew Ferguson; Caroline R. Bradley; Robin Ade; Colin Roberts; E. J. Keay; Artur R. Costa; Rosaleen Hynes (Journal of Fish Biology, 2019)
Anthropogenic acidification in SW‐Scotland, from the early 19th Century onwards, led to the extinction of several loch (lake) brown trout ( Salmo trutta ) populations and substantial reductions in numbers in many others. Higher altitude populations with no stocking influence, which are isolated above natural and artificial barriers and subjected to the greatest effect of acidification, exhibited the least intrapopulation genetic diversity (34% of the allelic richness of the populations accessible to anadromous S. trutta ). These, however, were characterised by the greatest interpopulation divergence (highest pairwise D EST 0.61 and F ST 0.53 in contemporary samples) based on 16 microsatellite loci and are among the most differentiated S. trutta populations in NW‐Europe. Five lochs above impassable waterfalls, where S. trutta were thought to be extinct, are documented as having been stocked in the late 1980s or 1990s. All five lochs now support self‐sustaining S. trutta populations; three as a direct result of restoration stocking and two adjoining lochs largely arising from a small remnant wild population in one, but with some stocking input. The genetically unique Loch Grannoch S. trutta , which has been shown to have a heritable increased tolerance to acid conditions, was successfully used as a donor stock to restore populations in two acidic lochs. Loch Fleet S. trutta , which were re‐established from four separate donor sources in the late 1980s, showed differential contribution from these ancestors and a higher genetic diversity than all 17 natural loch populations examined in the area. Genetically distinct inlet and outlet spawning S. trutta populations were found in this loch. Three genetically distinct sympatric populations of S. trutta were identified in Loch Grannoch, most likely representing recruitment from the three main spawning rivers. A distinct genetic signature of Loch Leven S. trutta , the progenitor of many Scottish farm strains, facilitated detection of stocking with these strains. One artificially created loch was shown to have a population genetically very similar to Loch Leven S. trutta . In spite of recorded historical supplemental stocking with Loch Leven derived farm strains, much of the indigenous S. trutta genetic diversity in the area remains intact, aside from the effects of acidification induced bottlenecks. Overall genetic diversity and extant populations have been increased by allochthonous stocking.

Differential selection pressures result in a rapid divergence of donor and refuge populations of a high conservation value freshwater fish Coregonus lavaretus (L.) - J. Peter Koene; Marco Crotti; Kathryn R. Elmer; Colin E. Adams (Evolutionary Ecology, 2019)

Citizen science reveals female sand tiger sharks ( Carcharias taurus ) exhibit signs of site fidelity on shipwrecks - Avery B. Paxton; Erica Blair; Camryn Blawas; Michael H. Fatzinger; Madeline Marens; Jason Holmberg; Colin Kingen; Tanya Houppermans; Mark Keusenkothen; John McCord; Brian R. Silliman; Linda M. Penfold (Ecology, 2019)

Interspecific interactions, movement patterns and habitat use in a diverse coastal shark assemblage - Michelle R. Heupel; Samantha E. M. Munroe; Elodie J. I. Lédée; Andrew Chin; Colin A. Simpfendorfer (Marine Biology, 2019)

Insect population trends and the IUCN Red List process - Richard Fox; Colin A. Harrower; James R. Bell; Chris R. Shortall; Ian Middlebrook; Robert J. Wilson (Journal of Insect Conservation, 2019)

Connexin43 hemichannel block protects against the development of diabetic retinopathy signs in a mouse model of the disease - Odunayo O. Mugisho; Colin R. Green; David M. Squirrell; Sarah Bould; Helen V. Danesh-Meyer; Jie Zhang; Monica L. Acosta; Ilva D. Rupenthal (Journal of Molecular Medicine, 2019)

Correction to: The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Arthur L. Beaudet; Steve D. M. Brown; Mary E. Dickinson; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Conservation Genetics, 2019)

Atmosphere surface storm track response to resolved ocean mesoscale in two sets of global climate model experiments - R. Justin Small; Rym Msadek; Young-Oh Kwon; James F. Booth; Colin Zarzycki (Climate Dynamics, 2019)

C 4 anatomy can evolve via a single developmental change - Marjorie R. Lundgren; Luke T. Dunning; Jill K. Olofsson; Jose J. Moreno‐Villena; Jacques W. Bouvier; Tammy L. Sage; Roxana Khoshravesh; Stefanie Sultmanis; Matt Stata; Brad S. Ripley; Maria S. Vorontsova; Guillaume Besnard; et al. (Ecology Letters, 2019)
C 4 photosynthesis is a complex trait that boosts productivity in warm environments. Paradoxically, it evolved independently in numerous plant lineages, despite requiring specialised leaf anatomy. The anatomical modifications underlying C 4 evolution have previously been evaluated through interspecific comparisons, which capture numerous changes besides those needed for C 4 functionality. Here, we quantify the anatomical changes accompanying the transition between non‐C 4 and C 4 phenotypes by sampling widely across the continuum of leaf anatomical traits in the grass Alloteropsis semialata . Within this species, the only trait that is shared among and specific to C 4 individuals is an increase in vein density, driven specifically by minor vein development that yields multiple secondary effects facilitating C 4 function. For species with the necessary anatomical preconditions, developmental proliferation of veins can therefore be sufficient to produce a functional C 4 leaf anatomy, creating an evolutionary entry point to complex C 4 syndromes that can become more specialised.

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Reef Shark Science – Key Questions and Future Directions - Michelle R. Heupel; Yannis P. Papastamatiou; Mario Espinoza; Madeline E. Green; Colin A. Simpfendorfer (Frontiers in Marine Science, 2019)

Unravelling the complexity of magma plumbing at Mount St. Helens: a new trace element partitioning scheme for amphibole - Madeleine C. S. Humphreys; George F. Cooper; Jing Zhang; Matthew Loewen; Adam J. R. Kent; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

Local extinctions of insular avifauna on the most remote inhabited island in the world - Alexander L. Bond; Colin J. Carlson; Kevin R. Burgio (Journal of Ornithology, 2019)

Gauging support for macroecological patterns in helminth parasites - Tad A. Dallas; A. Alonso Aguirre; Sarah Budischak; Colin Carlson; Vanessa Ezenwa; Barbara Han; Shan Huang; Patrick R. Stephens (Global Ecology and Biogeography, 2018)
Aim To explore spatial patterns of helminth parasite diversity, and to investigate three main macroecological patterns – (a) latitude–diversity relationships, (b) positive scaling between parasite and host diversity, and (c) species–area relationships – using a largely underutilized global database of helminth parasite occurrence records. Location Global. Methods We examined the London Natural History Museum’s collection of helminth parasite occurrence records, consisting of over 18,000 unique host species and 27,000 unique helminth parasite species distributed across over 350 distinct terrestrial and aquatic localities. Results We find support for latitudinal gradients in parasite diversity and a strong relationship between host and parasite diversity at the global scale. Helminth species diversity–area relationships were not detectable as a function of host body mass, but larger geographic areas supported higher parasite richness, potentially mediated through higher host richness. Main conclusions Our findings indicate that helminth parasites may obey some of the macroecological relationships found in free‐living species, suggesting that parasites may offer further support for the generality of these patterns, while offering interesting counterexamples for others. We conclude with a discussion of future directions and potential challenges in the newly emerging macroecology of infectious disease.

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Rapid thermal adaptation in a marine diatom reveals constraints and trade‐offs - Daniel R. O'Donnell; Carolyn R. Hamman; Evan C. Johnson; Colin T. Kremer; Christopher A. Klausmeier; Elena Litchman (Global Change Biology, 2018)
Rapid evolution in response to environmental change will likely be a driving force determining the distribution of species across the biosphere in coming decades. This is especially true of microorganisms, many of which may evolve in step with warming, including phytoplankton, the diverse photosynthetic microbes forming the foundation of most aquatic food webs. Here we tested the capacity of a globally important, model marine diatom Thalassiosira pseudonana , for rapid evolution in response to temperature. Selection at 16 and 31°C for 350 generations led to significant divergence in several temperature response traits, demonstrating local adaptation and the existence of trade‐offs associated with adaptation to different temperatures. In contrast, competitive ability for nitrogen (commonly limiting in marine systems), measured after 450 generations of temperature selection, did not diverge in a systematic way between temperatures. This study shows how rapid thermal adaptation affects key temperature and nutrient traits and, thus, a population's long‐term physiological, ecological, and biogeographic response to climate change.

Reevaluating sighting models and moving beyond them to test and contextualize the extinction of the thylacine - Colin J. Carlson; Alexander L. Bond; Kevin R. Burgio (Conservation Biology, 2018)
Article impact statement : All available models suggest the thylacine remains extinct until rediscovered; hope remains for other species.

Reef-scale variability in fish and coral assemblages on the central Great Barrier Reef - Stacy L. Bierwagen; Michael J. Emslie; Michelle R. Heupel; Andrew Chin; Colin A. Simpfendorfer (Marine Biology, 2018)

An Extracellular Polysaccharide-Rich Organic Layer Contributes to Organization of the Coccosphere in Coccolithophores - Charlotte E. Walker; Sarah Heath; Deborah L. Salmon; Nicholas Smirnoff; Gerald Langer; Alison R. Taylor; Colin Brownlee; Glen L. Wheeler (Frontiers in Marine Science, 2018)

Groundwater sustainability and groundwater/surface-water interaction in arid Dunhuang Basin, northwest China - Jingjing Lin; Rui Ma; Yalu Hu; Ziyong Sun; Yanxin Wang; Colin P. R. McCarter (Hydrogeology Journal, 2018)

Targeting therapeutics to endothelium: are we there yet? - Raisa Yu. Kiseleva; Patrick M. Glassman; Colin F. Greineder; Elizabeth D. Hood; Vladimir V. Shuvaev; Vladimir R. Muzykantov (Drug Delivery and Translational Research, 2018)

The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Steve D. M. Brown; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Martin Hrabě de Angelis; Jong Kyoung Kim; K. C. Kent Lloyd; et al. (Conservation Genetics, 2018)
The International Mouse Phenotyping Consortium (IMPC) is building a catalogue of mammalian gene function by producing and phenotyping a knockout mouse line for every protein-coding gene. To date, the IMPC has generated and characterised 5186 mutant lines. One-third of the lines have been found to be non-viable and over 300 new mouse models of human disease have been identified thus far. While current bioinformatics efforts are focused on translating results to better understand human disease processes, IMPC data also aids understanding genetic function and processes in other species. Here we show, using gorilla genomic data, how genes essential to development in mice can be used to help assess the potentially deleterious impact of gene variants in other species. This type of analyses could be used to select optimal breeders in endangered species to maintain or increase fitness and avoid variants associated to impaired-health phenotypes or loss-of-function mutations in genes of critical importance. We also show, using selected examples from various mammal species, how IMPC data can aid in the identification of candidate genes for studying a condition of interest, deliver information about the mechanisms involved, or support predictions for the function of genes that may play a role in adaptation. With genotyping costs decreasing and the continued improvements of bioinformatics tools, the analyses we demonstrate can be routinely applied.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Biodiversity effects on ecosystem functioning respond unimodally to environmental stress - Jan M. Baert; Nico Eisenhauer; Colin R. Janssen; Frederik De Laender (Ecology Letters, 2018)
Understanding how biodiversity (B) affects ecosystem functioning (EF) is essential for assessing the consequences of ongoing biodiversity changes. An increasing number of studies, however, show that environmental conditions affect the shape of BEF relationships. Here, we first use a game‐theoretic community model to reveal that a unimodal response of the BEF slope can be expected along environmental stress gradients, but also how the ecological mechanisms underlying this response may vary depending on how stress affects species interactions. Next, we analysed a global dataset of 44 experiments that crossed biodiversity with environmental conditions. Confirming our main model prediction, the effect of biodiversity on ecosystem functioning tends to be greater at intermediate levels of environmental stress, but varies among studies corresponding to differences in stress‐effects on species interactions. Together, these results suggest that increases in stress from ongoing global environmental changes may amplify the consequences of biodiversity changes.

Counterintuitive migration patterns by Atlantic salmon Salmo salar smolts in a large lake - Hannele M. Honkanen; Jessica R. Rodger; Alastair Stephen; Keith Adams; James Freeman; Colin E. Adams (Journal of Fish Biology, 2018)
What little is known about the seaward migration of Salmo salar smolt migration through standing waters indicates that it is both slow and results in high mortality rates, compared with riverine migration. This may be partly because smolts in lakes need to swim more actively and require more complex directional cues than they do in rivers. In this telemetry study of smolt migration through Loch Lomond, S. salar smolts made repeated movements in directions away from the outflowing river, which considerably increased migration time.

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2018)

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2018)

Interactions among plants, bacteria, and fungi reduce extracellular enzyme activities under long‐term N fertilization - Joseph E. Carrara; Christopher A. Walter; Jennifer S. Hawkins; William T. Peterjohn; Colin Averill; Edward R. Brzostek (Global Change Biology, 2018)
Atmospheric nitrogen (N) deposition has enhanced soil carbon (C) stocks in temperate forests. Most research has posited that these soil C gains are driven primarily by shifts in fungal community composition with elevated N leading to declines in lignin degrading Basidiomycetes . Recent research, however, suggests that plants and soil microbes are dynamically intertwined, whereby plants send C subsidies to rhizosphere microbes to enhance enzyme production and the mobilization of N. Thus, under elevated N, trees may reduce belowground C allocation leading to cascading impacts on the ability of microbes to degrade soil organic matter through a shift in microbial species and/or a change in plant–microbe interactions. The objective of this study was to determine the extent to which couplings among plant, fungal, and bacterial responses to N fertilization alter the activity of enzymes that are the primary agents of soil decomposition. We measured fungal and bacterial community composition, root–microbial interactions, and extracellular enzyme activity in the rhizosphere, bulk, and organic horizon of soils sampled from a long‐term (>25 years), whole‐watershed, N fertilization experiment at the Fernow Experimental Forest in West Virginia, USA. We observed significant declines in plant C investment to fine root biomass (24.7%), root morphology, and arbuscular mycorrhizal (AM) colonization (55.9%). Moreover, we found that declines in extracellular enzyme activity were significantly correlated with a shift in bacterial community composition, but not fungal community composition. This bacterial community shift was also correlated with reduced AM fungal colonization indicating that declines in plant investment belowground drive the response of bacterial community structure and function to N fertilization. Collectively, we find that enzyme activity responses to N fertilization are not solely driven by fungi, but instead reflect a whole ecosystem response, whereby declines in the strength of belowground C investment to gain N cascade through the soil environment.

Drought timing and local climate determine the sensitivity of eastern temperate forests to drought - Loïc D'Orangeville; Justin Maxwell; Daniel Kneeshaw; Neil Pederson; Louis Duchesne; Travis Logan; Daniel Houle; Dominique Arseneault; Colin M. Beier; Daniel A. Bishop; Daniel Druckenbrod; Shawn Fraver; et al. (Global Change Biology, 2018)
Projected changes in temperature and drought regime are likely to reduce carbon (C) storage in forests, thereby amplifying rates of climate change. While such reductions are often presumed to be greatest in semi‐arid forests that experience widespread tree mortality, the consequences of drought may also be important in temperate mesic forests of Eastern North America ( ENA ) if tree growth is significantly curtailed by drought. Investigations of the environmental conditions that determine drought sensitivity are critically needed to accurately predict ecosystem feedbacks to climate change. We matched site factors with the growth responses to drought of 10,753 trees across mesic forests of ENA , representing 24 species and 346 stands, to determine the broad‐scale drivers of drought sensitivity for the dominant trees in ENA . Here we show that two factors—the timing of drought, and the atmospheric demand for water (i.e., local potential evapotranspiration; PET )—are stronger drivers of drought sensitivity than soil and stand characteristics. Drought‐induced reductions in tree growth were greatest when the droughts occurred during early‐season peaks in radial growth, especially for trees growing in the warmest, driest regions (i.e., highest PET ). Further, mean species trait values (rooting depth and ψ 50 ) were poor predictors of drought sensitivity, as intraspecific variation in sensitivity was equal to or greater than interspecific variation in 17 of 24 species. From a general circulation model ensemble, we find that future increases in early‐season PET may exacerbate these effects, and potentially offset gains in C uptake and storage in ENA owing to other global change factors.

Textural and micro-analytical insights into mafic–felsic interactions during the Oruanui eruption, Taupo - Shane M. Rooyakkers; Colin J. N. Wilson; C. Ian Schipper; Simon J. Barker; Aidan S. R. Allan (Contributions to Mineralogy and Petrology, 2018)

Enhanced hemoglobin–oxygen unloading in migratory salmonids - Jacelyn J. Shu; Till S. Harter; Phillip R. Morrison; Colin J. Brauner (Journal of Comparative Physiology B, 2018)

Valuable elements in Chinese coals: a review - Shifeng Dai; Xiaoyun Yan; Colin R. Ward; James C. Hower; Lei Zhao; Xibo Wang; Lixin Zhao; Deyi Ren; Robert B. Finkelman (International Geology Review, 2018)

The microbiology and treatment of human mastitis - Angeliki Angelopoulou; Des Field; C. Anthony Ryan; Catherine Stanton; Colin Hill; R. Paul Ross (Medical Microbiology and Immunology, 2018)

Differences in soil fungal assemblages associated with native and non-native tree species of varying weediness - David R. Toole; Gabrielle H. Cannon; Colin J. Brislawn; Jennifer M. Graves; Regina Lamendella; Theodore R. Muth; Norris Z. Muth (Biological Invasions, 2018)

Pathogen spillover during land conversion - Christina L. Faust; Hamish I. McCallum; Laura S. P. Bloomfield; Nicole L. Gottdenker; Thomas R. Gillespie; Colin J. Torney; Andrew P. Dobson; Raina K. Plowright (Ecology Letters, 2018)
Pathogen spillover from wildlife to domestic animals and humans, and the reverse, has caused significant epidemics and pandemics worldwide. Although pathogen emergence has been linked to anthropogenic land conversion, a general framework to disentangle underlying processes is lacking. We develop a multi‐host model for pathogen transmission between species inhabiting intact and converted habitat. Interspecies contacts and host populations vary with the proportion of land converted; enabling us to quantify infection risk across a changing landscape. In a range of scenarios, the highest spillover risk occurs at intermediate levels of habitat loss, whereas the largest, but rarest, epidemics occur at extremes of land conversion. This framework provides insights into the mechanisms driving disease emergence and spillover during land conversion. The finding that the risk of spillover is highest at intermediate levels of habitat loss provides important guidance for conservation and public health policy.

Going through the motions: incorporating movement analyses into disease research - Eric R. Dougherty; Dana P. Seidel; Colin J. Carlson; Orr Spiegel; Wayne M. Getz (Ecology Letters, 2018)
Though epidemiology dates back to the 1700s, most mathematical representations of epidemics still use transmission rates averaged at the population scale, especially for wildlife diseases. In simplifying the contact process, we ignore the heterogeneities in host movements that complicate the real world, and overlook their impact on spatiotemporal patterns of disease burden. Movement ecology offers a set of tools that help unpack the transmission process, letting researchers more accurately model how animals within a population interact and spread pathogens. Analytical techniques from this growing field can also help expose the reverse process: how infection impacts movement behaviours, and therefore other ecological processes like feeding, reproduction, and dispersal. Here, we synthesise the contributions of movement ecology in disease research, with a particular focus on studies that have successfully used movement‐based methods to quantify individual heterogeneity in exposure and transmission risk. Throughout, we highlight the rapid growth of both disease and movement ecology and comment on promising but unexplored avenues for research at their overlap. Ultimately, we suggest, including movement empowers ecologists to pose new questions, expanding our understanding of host–pathogen dynamics and improving our predictive capacity for wildlife and even human diseases.

Estimating the extinction date of the thylacine with mixed certainty data - Colin J. Carlson; Alexander L. Bond; Kevin R. Burgio (Conservation Biology, 2018)
The thylacine ( Thylacinus cynocephalus ), one of Australia's most characteristic megafauna, was the largest marsupial carnivore until hunting, and potentially disease, drove it to extinction in 1936. Although thylacines were restricted to Tasmania for 2 millennia prior to their extinction, recent so‐called plausible sightings on the Cape York Peninsula in northern Queensland have emerged, leading some to speculate the species may have persisted undetected. We compiled a data set that included physical evidence, expert‐validated sightings, and unconfirmed sightings up to the present day and implemented a range of extinction models (focusing on a Bayesian approach that incorporates all 3 types of data by modeling valid and invalid sightings as independent processes) to evaluate the likelihood of the thylacine's persistence. Although the last captive individual died in September 1936, our results suggested that the most likely extinction date would be 1940. Our other extinction models estimated the thylacine's extinction date between 1936 and 1943, and the most optimistic scenario indicated that the species did not persist beyond 1956. The search for the thylacine, much like similar efforts to rediscover other recently extinct charismatic taxa, is likely to be fruitless, especially given that persistence on Tasmania would have been no guarantee the species could reappear in regions that had been unoccupied for millennia. The search for the thylacine may become a rallying point for conservation and wildlife biology and could indirectly help fund and support critical research in understudied areas such as Cape York. However, our results suggest that attempts to rediscover the thylacine will be unsuccessful and that the continued survival of the thylacine is entirely implausible based on most current mathematical theories of extinction.

Trophodynamics as a Tool for Understanding Coral Reef Ecosystems - Stacy L. Bierwagen; Michelle R. Heupel; Andrew Chin; Colin A. Simpfendorfer (Frontiers in Marine Science, 2018)

Integrating community assembly and biodiversity to better understand ecosystem function: the Community Assembly and the Functioning of Ecosystems ( CAFE ) approach - Katherine H. Bannar‐Martin; Colin T. Kremer; S.K. Morgan Ernest; Mathew A. Leibold; Harald Auge; Jonathan Chase; Steven A.J. Declerck; Nico Eisenhauer; Stanley Harpole; Helmut Hillebrand; Forest Isbell; Thomas Koffel; et al. (Ecology Letters, 2018)
The research of a generation of ecologists was catalysed by the recognition that the number and identity of species in communities influences the functioning of ecosystems. The relationship between biodiversity and ecosystem functioning ( BEF ) is most often examined by controlling species richness and randomising community composition. In natural systems, biodiversity changes are often part of a bigger community assembly dynamic. Therefore, focusing on community assembly and the functioning of ecosystems ( CAFE ), by integrating both species richness and composition through species gains, losses and changes in abundance, will better reveal how community changes affect ecosystem function. We synthesise the BEF and CAFE perspectives using an ecological application of the Price equation, which partitions the contributions of richness and composition to function. Using empirical examples, we show how the CAFE approach reveals important contributions of composition to function. These examples show how changes in species richness and composition driven by environmental perturbations can work in concert or antagonistically to influence ecosystem function. Considering how communities change in an integrative fashion, rather than focusing on one axis of community structure at a time, will improve our ability to anticipate and predict changes in ecosystem function.

Making ecological models adequate - Wayne M. Getz; Charles R. Marshall; Colin J. Carlson; Luca Giuggioli; Sadie J. Ryan; Stephanie S. Romañach; Carl Boettiger; Samuel D. Chamberlain; Laurel Larsen; Paolo D’Odorico; David O’Sullivan (Ecology Letters, 2018)
Critical evaluation of the adequacy of ecological models is urgently needed to enhance their utility in developing theory and enabling environmental managers and policymakers to make informed decisions. Poorly supported management can have detrimental, costly or irreversible impacts on the environment and society. Here, we examine common issues in ecological modelling and suggest criteria for improving modelling frameworks. An appropriate level of process description is crucial to constructing the best possible model, given the available data and understanding of ecological structures. Model details unsupported by data typically lead to over parameterisation and poor model performance. Conversely, a lack of mechanistic details may limit a model's ability to predict ecological systems’ responses to management. Ecological studies that employ models should follow a set of model adequacy assessment protocols that include: asking a series of critical questions regarding state and control variable selection, the determinacy of data, and the sensitivity and validity of analyses. We also need to improve model elaboration, refinement and coarse graining procedures to better understand the relevancy and adequacy of our models and the role they play in advancing theory, improving hind and forecasting, and enabling problem solving and management.

Resilience in moving water: Effects of turbulence on the predatory impact of the lobate ctenophore Mnemiopsis leidyi - Cornelia Jaspers; John H. Costello; Kelly R. Sutherland; Brad Gemmell; Kelsey N. Lucas; Jennifer Tackett; Kara Dodge; Sean P. Colin (Limnology and Oceanography, 2018)
Despite its delicate morphology, the lobate ctenophore Mnemiopsis leidyi thrives in coastal ecosystems as an influential zooplankton predator. Coastal ecosystems are often characterized as energetic systems with high levels of natural turbulence in the water column. To understand how natural wind‐driven turbulence affects the feeding ecology of M. leidyi , we used a combination of approaches to quantify how naturally and laboratory generated turbulence affects the behavior, feeding processes and feeding impact of M. leidyi . Experiments using laboratory generated turbulence demonstrated that turbulence can reduce M. leidyi feeding rates on copepods and Artemia nauplii by > 50%. However, detailed feeding data from the field, collected during highly variable surface conditions, showed that wind‐driven turbulence did not affect the feeding rates or prey selection of M. leidyi . Additional laboratory experiments and field observations suggest that the feeding process of M. leidyi is resilient to wind‐driven turbulence because M. leidyi shows a behavioral response to turbulence by moving deeper in the water column. Seeking refuge in deeper waters enables M. leidyi to maintain high feeding rates even under high turbulence conditions generated by wind driven mixing. As a result, M. leidyi exerted a consistently high predatory impact on prey populations during highly variable and often energetic wind‐driven mixing conditions. This resilience adds to our understanding of how M. leidyi can thrive in a wide spectrum of environments around the world. The limits to this resilience also set boundaries to its range expansion into novel areas.

Barriers and Solutions to Conducting Large International, Interdisciplinary Research Projects - Erin C. Pischke; Jessie L. Knowlton; Colin C. Phifer; Jose Gutierrez Lopez; Tamara S. Propato; Amarella Eastmond; Tatiana Martins de Souza; Mark Kuhlberg; Valentin Picasso Risso; Santiago R. Veron; Carlos Garcia; Marta Chiappe; et al. (Environmental Management, 2017)

Lower crustal hydrothermal circulation at slow-spreading ridges: evidence from chlorine in Arctic and South Atlantic basalt glasses and melt inclusions - Froukje M. van der Zwan; Colin W. Devey; Thor H. Hansteen; Renat R. Almeev; Nico Augustin; Matthias Frische; Karsten M. Haase; Ali Basaham; Jonathan E. Snow (Contributions to Mineralogy and Petrology, 2017)

Bird community responses to afforested eucalyptus plantations in the Argentine pampas - Colin C. Phifer; Jessie L. Knowlton; Christopher R. Webster; David J. Flaspohler; Julian A. Licata (Biodiversity and Conservation, 2017)

Effects of a natural flood disturbance on species richness and beta diversity of stream benthic diatom communities - Fabiana Schneck; Katharina Lange; Adriano S. Melo; Colin R. Townsend; Christoph D. Matthaei (Aquatic Ecology, 2017)

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2017)

Characterisation of Peptide5 systemic administration for treating traumatic spinal cord injured rats - Yilin Mao; Tara Nguyen; Ryan S. Tonkin; Justin G. Lees; Caitlyn Warren; Simon J. O’Carroll; Louise F. B. Nicholson; Colin R. Green; Gila Moalem-Taylor; Catherine A. Gorrie (Experimental Brain Research, 2017)

Social and spatial effects on genetic variation between foraging flocks in a wild bird population - Reinder Radersma; Colin J. Garroway; Anna W. Santure; Isabelle de Cauwer; Damien R. Farine; Jon Slate; Ben C. Sheldon (Molecular Ecology, 2017)
Social interactions are rarely random. In some instances, animals exhibit homophily or heterophily, the tendency to interact with similar or dissimilar conspecifics, respectively. Genetic homophily and heterophily influence the evolutionary dynamics of populations, because they potentially affect sexual and social selection. Here, we investigate the link between social interactions and allele frequencies in foraging flocks of great tits ( Parus major ) over three consecutive years. We constructed co‐occurrence networks which explicitly described the splitting and merging of 85,602 flocks through time (fission–fusion dynamics), at 60 feeding sites. Of the 1,711 birds in those flocks, we genotyped 962 individuals at 4,701 autosomal single nucleotide polymorphisms ( SNP s). By combining genomewide genotyping with repeated field observations of the same individuals, we were able to investigate links between social structure and allele frequencies at a much finer scale than was previously possible. We explicitly accounted for potential spatial effects underlying genetic structure at the population level. We modelled social structure and spatial configuration of great tit fission–fusion dynamics with eigenvector maps. Variance partitioning revealed that allele frequencies were strongly affected by group fidelity (explaining 27%–45% of variance) as individuals tended to maintain associations with the same conspecifics. These conspecifics were genetically more dissimilar than expected, shown by genomewide heterophily for pure social (i.e., space‐independent) grouping preferences. Genomewide homophily was linked to spatial configuration, indicating spatial segregation of genotypes. We did not find evidence for homophily or heterophily for putative socially relevant candidate genes or any other SNP markers. Together, these results demonstrate the importance of distinguishing social and spatial processes in determining population structure.

A closer look at novel climates: new methods and insights at continental to landscape scales - Colin R. Mahony; Alex J. Cannon; Tongli Wang; Sally N. Aitken (Global Change Biology, 2017)
Novel climates – emerging conditions with no analog in the observational record – are an open problem in ecological modeling. Detecting extrapolation into novel conditions is a critical step in evaluating bioclimatic projections of how species and ecosystems will respond to climate change. However, biologically informed novelty detection methods remain elusive for many modeling algorithms. To assist with bioclimatic model design and evaluation, we present a first‐approximation assessment of general novelty based on a simple and consistent characterization of climate. We build on the seminal global analysis of Williams et al . (2007 PNAS, 104, 5738) by assessing of end‐of‐21st‐century novelty for North America at high spatial resolution and by refining their standardized Euclidean distance into an intuitive Mahalanobian metric called sigma dissimilarity. Like this previous study, we found extensive novelty in end‐of‐21st‐century projections for the warm southern margin of the continent as well as the western Arctic. In addition, we detected localized novelty in lower topographic positions at all latitudes: By the end of the 21st century, novel climates are projected to emerge at low elevations in 80% and 99% of ecoregions in the RCP 4.5 and RCP 8.5 emissions scenarios, respectively. Novel climates are limited to 7% of the continent's area in RCP 4.5, but are much more extensive in RCP 8.5 (40% of area). These three risk factors for novel climates – regional susceptibility, topographic position, and the magnitude of projected climate change – represent a priori evaluation criteria for the credibility of bioclimatic projections. Our findings indicate that novel climates can emerge in any landscape. Interpreting climatic novelty in the context of nonlinear biological responses to climate is an important challenge for future research.

Temperature–nutrient interactions exacerbate sensitivity to warming in phytoplankton - Mridul K. Thomas; María Aranguren‐Gassis; Colin T. Kremer; Marilyn R. Gould; Krista Anderson; Christopher A. Klausmeier; Elena Litchman (Global Change Biology, 2017)
Temperature and nutrients are fundamental, highly nonlinear drivers of biological processes, but we know little about how they interact to influence growth. This has hampered attempts to model population growth and competition in dynamic environments, which is critical in forecasting species distributions, as well as the diversity and productivity of communities. To address this, we propose a model of population growth that includes a new formulation of the temperature–nutrient interaction and test a novel prediction: that a species’ optimum temperature for growth, T opt , is a saturating function of nutrient concentration. We find strong support for this prediction in experiments with a marine diatom, Thalassiosira pseudonana : T opt decreases by 3–6 °C at low nitrogen and phosphorus concentrations. This interaction implies that species are more vulnerable to hot, low‐nutrient conditions than previous models accounted for. Consequently the interaction dramatically alters species’ range limits in the ocean, projected based on current temperature and nitrate levels as well as those forecast for the future. Ranges are smaller not only than projections based on the individual variables, but also than those using a simpler model of temperature–nutrient interactions. Nutrient deprivation is therefore likely to exacerbate environmental warming's effects on communities.

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2017)

A cascade of magmatic events during the assembly and eruption of a super-sized magma body - Aidan. S. R. Allan; Simon J. Barker; Marc-Alban Millet; Daniel J. Morgan; Shane M. Rooyakkers; C. Ian Schipper; Colin J. N. Wilson (Contributions to Mineralogy and Petrology, 2017)

Zincoberaunite, ZnFe3+ 5(PO4)4(OH)5⋅6H2O, a new mineral from the Hagendorf South pegmatite, Germany - Nikita V. Chukanov; Igor V. Pekov; Ian E. Grey; Jason R. Price; Sergey N. Britvin; Maria G. Krzhizhanovskaya; Anthony R. Kampf; Bernhard Dünkel; Erich Keck; Dmitry I. Belakovskiy; Colin M. MacRae (Mineralogy and Petrology, 2017)

Population PBPK modelling of trastuzumab: a framework for quantifying and predicting inter-individual variability - Paul R. V. Malik; Abdullah Hamadeh; Colin Phipps; Andrea N. Edginton (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Decreasing worker size diversity does not affect colony performance during laboratory challenges in the ant Temnothorax nylanderi - T. Colin; C. Doums; R. Péronnet; M. Molet (Behavioral Ecology and Sociobiology, 2017)

Gulf Ribbed Mussels (Geukensia granosissima) Increase Methane Emissions from a Coastal Spartina alterniflora Marsh - Anthony J. Rietl; John A. Nyman; Charles W. Lindau; Colin R. Jackson (Estuaries and Coasts, 2017)

Circumpolar analysis of the Adélie Penguin reveals the importance of environmental variability in phenological mismatch - Casey Youngflesh; Stephanie Jenouvrier; Yun Li; Rubao Ji; David G. Ainley; Grant Ballard; Christophe Barbraud; Karine Delord; Katie M. Dugger; Louise M. Emmerson; William R. Fraser; Jefferson T. Hinke; et al. (Ecology, 2017)
Evidence of climate‐change‐driven shifts in plant and animal phenology have raised concerns that certain trophic interactions may be increasingly mismatched in time, resulting in declines in reproductive success. Given the constraints imposed by extreme seasonality at high latitudes and the rapid shifts in phenology seen in the Arctic, we would also expect Antarctic species to be highly vulnerable to climate‐change‐driven phenological mismatches with their environment. However, few studies have assessed the impacts of phenological change in Antarctica. Using the largest database of phytoplankton phenology, sea‐ice phenology, and Adélie Penguin breeding phenology and breeding success assembled to date, we find that, while a temporal match between Penguin breeding phenology and optimal environmental conditions sets an upper limit on breeding success, only a weak relationship to the mean exists. Despite previous work suggesting that divergent trends in Adélie Penguin breeding phenology are apparent across the Antarctic continent, we find no such trends. Furthermore, we find no trend in the magnitude of phenological mismatch, suggesting that mismatch is driven by interannual variability in environmental conditions rather than climate‐change‐driven trends, as observed in other systems. We propose several criteria necessary for a species to experience a strong climate‐change‐driven phenological mismatch, of which several may be violated by this system.

Flood mapping in the lower Mekong River Basin using daily MODIS observations - Jessica V. Fayne; John D. Bolten; Colin S. Doyle; Sven Fuhrmann; Matthew T. Rice; Paul R. Houser; Venkat Lakshmi (International Journal of Remote Sensing, 2017)

Non-additive effects of dispersal and selective stress on structure, evenness, and biovolume production in marine diatom communities - Jonathan De Raedt; Jan M. Baert; Colin R. Janssen; Frederik De Laender (Hydrobiologia, 2017)

Concentrations of select dissolved trace elements and anthropogenic organic compounds in the Mississippi River and major tributaries during the summer of 2012 and 2013 - Derek D. Bussan; Clifford A. Ochs; Colin R. Jackson; Tarun Anumol; Shane A. Snyder; James V. Cizdziel (Environmental Monitoring and Assessment, 2017)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Coccidioidomycosis in Patients with Selected Solid Organ Cancers: A Case Series and Review of Medical Literature - Colin Fitterer; Zachary Berg; Thorvardur R. Halfdanarson; Holenarasipur R. Vikram; Shimon Kusne; Robert Orenstein; Maria Teresa Seville; Janis E. Blair (Mycopathologia, 2016)

Lesion recovery and the bacterial microbiome in two Caribbean gorgonian corals - Kartick P. Shirur; Colin R. Jackson; Tamar L. Goulet (Marine Biology, 2016)

Genome biogeography reveals the intraspecific spread of adaptive mutations for a complex trait - Jill K. Olofsson; Matheus Bianconi; Guillaume Besnard; Luke T. Dunning; Marjorie R. Lundgren; Helene Holota; Maria S. Vorontsova; Oriane Hidalgo; Ilia J. Leitch; Patrik Nosil; Colin P. Osborne; Pascal‐Antoine Christin (Molecular Ecology, 2016)
Physiological novelties are often studied at macro‐evolutionary scales such that their micro‐evolutionary origins remain poorly understood. Here, we test the hypothesis that key components of a complex trait can evolve in isolation and later be combined by gene flow. We use C 4 photosynthesis as a study system, a derived physiology that increases plant productivity in warm, dry conditions. The grass Alloteropsis semialata includes C 4 and non‐C 4 genotypes, with some populations using laterally acquired C 4 ‐adaptive loci, providing an outstanding system to track the spread of novel adaptive mutations. Using genome data from C 4 and non‐C 4 A. semialata individuals spanning the species’ range, we infer and date past migrations of different parts of the genome. Our results show that photosynthetic types initially diverged in isolated populations, where key C 4 components were acquired. However, rare but recurrent subsequent gene flow allowed the spread of adaptive loci across genetic pools. Indeed, laterally acquired genes for key C 4 functions were rapidly passed between populations with otherwise distinct genomic backgrounds. Thus, our intraspecific study of C 4 ‐related genomic variation indicates that components of adaptive traits can evolve separately and later be combined through secondary gene flow, leading to the assembly and optimization of evolutionary innovations.

Biodiversity increases functional and compositional resistance, but decreases resilience in phytoplankton communities - Jan M. Baert; Frederik De Laender; Koen Sabbe; Colin R. Janssen (Ecology, 2016)
There is now ample evidence that biodiversity stabilizes aggregated ecosystem functions, such as primary production, in changing environments. In primary producer systems, this stabilizing effect is found to be driven by higher functional resistance (i.e., reduced changes in functions by environmental changes) rather than through higher functional resilience (i.e., rapid recovery following environmental changes) in more diverse systems. The stability of aggregated ecosystem functions directly depends on changes in species composition and by consequence their functional contributions to ecosystem functions. Still, it remains only theoretically explored how biodiversity can stabilize ecosystem functions by affecting compositional stability. Here, we demonstrate how biodiversity effects on compositional stability drive biodiversity effects on functional stability in diatom communities. In a microcosm experiment, we exposed 39 communities of five different levels of species richness (1, 2, 4, 6, and 8 species) to three concentrations of a chemical stressor (0, 25, and 250 μg/L atrazine) for four weeks, after which all communities were transferred to atrazine‐free medium for three more weeks. Biodiversity simultaneously increased, increasing functional and compositional resistance, but decreased functional and compositional resilience. These results confirm the theoretically proposed link between biodiversity effects on functional and compositional stability in primary producer systems, and provide a mechanistic underpinning for observed biodiversity–stability relationships. Finally, we discuss how higher compositional stability can be expected to become increasingly important in stabilizing ecosystem functions under field conditions when multiple environmental stressors fluctuate simultaneously.

The role of digital data entry in participatory environmental monitoring - Jeremy R. Brammer; Nicolas D. Brunet; A. Cole Burton; Alain Cuerrier; Finn Danielsen; Kanwaljeet Dewan; Thora Martina Herrmann; Micha V. Jackson; Rod Kennett; Guillaume Larocque; Monica Mulrennan; Arun Kumar Pratihast; et al. (Conservation Biology, 2016)
Many argue that monitoring conducted exclusively by scientists is insufficient to address ongoing environmental challenges. One solution entails the use of mobile digital devices in participatory monitoring (PM) programs. But how digital data entry affects programs with varying levels of stakeholder participation, from nonscientists collecting field data to nonscientists administering every step of a monitoring program, remains unclear. We reviewed the successes, in terms of management interventions and sustainability, of 107 monitoring programs described in the literature (hereafter programs) and compared these with case studies from our PM experiences in Australia, Canada, Ethiopia, Ghana, Greenland, and Vietnam (hereafter cases). Our literature review showed that participatory programs were less likely to use digital devices, and 2 of our 3 more participatory cases were also slow to adopt digital data entry. Programs that were participatory and used digital devices were more likely to report management actions, which was consistent with cases in Ethiopia, Greenland, and Australia. Programs engaging volunteers were more frequently reported as ongoing, but those involving digital data entry were less often sustained when data collectors were volunteers. For the Vietnamese and Canadian cases, sustainability was undermined by a mismatch in stakeholder objectives. In the Ghanaian case, complex field protocols diminished monitoring sustainability. Innovative technologies attract interest, but the foundation of effective participatory adaptive monitoring depends more on collaboratively defined questions, objectives, conceptual models, and monitoring approaches. When this foundation is built through effective partnerships, digital data entry can enable the collection of more data of higher quality. Without this foundation, or when implemented ineffectively or unnecessarily, digital data entry can be an additional expense that distracts from core monitoring objectives and undermines project sustainability. The appropriate role of digital data entry in PM likely depends more on the context in which it is used and less on the technology itself.

The Neurobiology and Age-Related Prevalence of the ε4 Allele of Apolipoprotein E in Alzheimer’s Disease Cohorts - Amy L. Heffernan; Cameron Chidgey; Po Peng; Colin L. Masters; Blaine R. Roberts (Journal of Molecular Neuroscience, 2016)

Prey capture by the cosmopolitan hydromedusae, Obelia spp., in the viscous regime - Kelly R. Sutherland; Brad J. Gemmell; Sean P. Colin; John H. Costello (Limnology and Oceanography, 2016)

Using mass-emergence devices to introduce an insect biocontrol agent to a new region and assist its dispersal - Scott Hardwick; Colin M. Ferguson; Mark R. McNeill; Craig B. Phillips (Journal of Pest Science, 2016)

Microbiome evolution along divergent branches of the vertebrate tree of life: what is known and unknown - Timothy J. Colston; Colin R. Jackson (Molecular Ecology, 2016)
Vertebrates harbour microbes both internally and externally, and collectively, these microorganisms (the ‘microbiome’) contain genes that outnumber the host's genetic information 10‐fold. The majority of the microorganisms associated with vertebrates are found within the gut, where they influence host physiology, immunity and development. The development of next‐generation sequencing has led to a surge in effort to characterize the microbiomes of various vertebrate hosts, a necessary first step to determine the functional role these communities play in host evolution or ecology. This shift away from a culture‐based microbiological approach, limited in taxonomic breadth, has resulted in the emergence of patterns suggesting a core vertebrate microbiome dominated by members of the bacterial phyla Bacteroidetes, Proteobacteria and Firmicutes. Still, there is a substantial variation in the methodology used to characterize the microbiome, from differences in sample type to issues of sampling captive or wild hosts, and the majority (>90%) of studies have characterized the microbiome of mammals, which represent just 8% of described vertebrate species. Here, we review the state of microbiome studies of nonmammalian vertebrates and provide a synthesis of emerging patterns in the microbiome of those organisms. We highlight the importance of collection methods, and the need for greater taxonomic sampling of natural rather than captive hosts, a shift in approach that is needed to draw ecologically and evolutionarily relevant inferences. Finally, we recommend future directions for vertebrate microbiome research, so that attempts can be made to determine the role that microbial communities play in vertebrate biology and evolution.

Paradigms for parasite conservation - Eric R. Dougherty; Colin J. Carlson; Veronica M. Bueno; Kevin R. Burgio; Carrie A. Cizauskas; Christopher F. Clements; Dana P. Seidel; Nyeema C. Harris (Conservation Biology, 2016)
Parasitic species, which depend directly on host species for their survival, represent a major regulatory force in ecosystems and a significant component of Earth's biodiversity. Yet the negative impacts of parasites observed at the host level have motivated a conservation paradigm of eradication, moving us farther from attainment of taxonomically unbiased conservation goals. Despite a growing body of literature highlighting the importance of parasite‐inclusive conservation, most parasite species remain understudied, underfunded, and underappreciated. We argue the protection of parasitic biodiversity requires a paradigm shift in the perception and valuation of their role as consumer species, similar to that of apex predators in the mid‐20th century. Beyond recognizing parasites as vital trophic regulators, existing tools available to conservation practitioners should explicitly account for the unique threats facing dependent species. We built upon concepts from epidemiology and economics (e.g., host‐density threshold and cost‐benefit analysis) to devise novel metrics of margin of error and minimum investment for parasite conservation. We define margin of error as the risk of accidental host extinction from misestimating equilibrium population sizes and predicted oscillations, while minimum investment represents the cost associated with conserving the additional hosts required to maintain viable parasite populations. This framework will aid in the identification of readily conserved parasites that present minimal health risks. To establish parasite conservation, we propose an extension of population viability analysis for host–parasite assemblages to assess extinction risk. In the direst cases, ex situ breeding programs for parasites should be evaluated to maximize success without undermining host protection. Though parasitic species pose a considerable conservation challenge, adaptations to conservation tools will help protect parasite biodiversity in the face of an uncertain environmental future.

Continental‐scale syntheses of Australian pyromes – misclassification of south‐western eucalypt woodlands misinforms management - Carl R. Gosper; Suzanne M. Prober; Colin J. Yates (Journal of Biogeography, 2016)
Global and continental‐scale analysis of ecological phenomena can offer important insights through the identification of patterns and associations not detectable at smaller scales. However, using proxies for ecological phenomena, such as vegetation mapping for spatially projecting fire regime niches and post‐fire plant responses, require critical examination of predictions to determine utility. Using local studies in south‐western Australia, we demonstrate that while this approach has been largely successful in mallee woodland and shrubland, it has failed in eucalypt woodland, with the consequence that values for a range of fire‐related parameters from the continent‐wide approaches, if adopted in informing management, would result in undesirable conservation outcomes for the world's largest extant temperate woodland.

Tectonic subsidence provides insight into possible coral reef futures under rapid sea-level rise - Megan I. Saunders; Simon Albert; Chris M. Roelfsema; Javier X. Leon; Colin D. Woodroffe; Stuart R. Phinn; Peter J. Mumby (Coral Reefs, 2016)

Corrigendum: Fluorescence Quantum Yields of Natural Organic Matter and Organic Compounds: Implications for the Fluorescence-based Interpretation of Organic Matter Composition - Urban J. Wünsch; Kathleen R. Murphy; Colin A. Stedmon (Frontiers in Marine Science, 2016)

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2016)

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2016)

Beyond arctic and alpine: the influence of winter climate on temperate ecosystems - Laura M. Ladwig; Zak R. Ratajczak; Troy W. Ocheltree; Katya A. Hafich; Amber C. Churchill; Sarah J. K. Frey; Colin B. Fuss; Clare E. Kazanski; Juan D. Muñoz; Matthew D. Petrie; Andrew B. Reinmann; Jane G. Smith (Ecology, 2016)
Winter climate is expected to change under future climate scenarios, yet the majority of winter ecology research is focused in cold‐climate ecosystems. In many temperate systems, it is unclear how winter climate relates to biotic responses during the growing season. The objective of this study was to examine how winter weather relates to plant and animal communities in a variety of terrestrial ecosystems ranging from warm deserts to alpine tundra. Specifically, we examined the association between winter weather and plant phenology, plant species richness, consumer abundance, and consumer richness in 11 terrestrial ecosystems associated with the U.S. Long‐Term Ecological Research ( LTER ) Network. To varying degrees, winter precipitation and temperature were correlated with all biotic response variables. Bud break was tightly aligned with end of winter temperatures. For half the sites, winter weather was a better predictor of plant species richness than growing season weather. Warmer winters were correlated with lower consumer abundances in both temperate and alpine systems. Our findings suggest winter weather may have a strong influence on biotic activity during the growing season and should be considered in future studies investigating the effects of climate change on both alpine and temperate systems.

Complementary resistance genes in wheat selection ‘Avocet R’ confer resistance to stripe rust - Peter M. Dracatos; Peng Zhang; Robert F. Park; Robert A. McIntosh; Colin R. Wellings (Theoretical and Applied Genetics, 2016)

Home range size of adult Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) in a coastal and estuarine system is habitat and sex‐specific - Kate R. Sprogis; Holly C. Raudino; Robert Rankin; Colin D. MacLeod; Lars Bejder (Marine Mammal Science, 2016)
This study examined sex‐specific differences in home range size of adult Indo‐Pacific bottlenose dolphins off Bunbury, Western Australia. We applied a new kernel density estimation approach that accounted for physical barriers to movements. A Bayesian mixture model was developed to estimate a sex effect in home range size with latent group partitioning constrained by association data. A post hoc analysis investigated group partitioning relating to the proportion of time spent in open vs . sheltered waters. From 2007 to 2013, photographic‐identification data were collected along boat‐based systematic transect lines ( n = 586). Analyses focused on adult dolphins of known sex (sighted ≥ 30 times; n = 22 males and 34 females). The 95% utilization distributions of males varied between 27 and 187 km 2 ( ; 94.8 ± 48.15) and for females between 20 and 133 km 2 (65.6 ± 30.9). The mixture model indicated a 99% probability that males had larger home ranges than females. Dolphins mostly sighted in open waters had larger home ranges than those in sheltered waters. Home ranges of dolphins sighted in sheltered waters overlapped with areas of highest human activity. We suggest that sex differences in home ranges are driven by male mating strategies, and home range size differences between habitats may be influenced by prey availability and predation risk.

Eruptive and environmental processes recorded by diatoms in volcanically dispersed lake sediments from the Taupo Volcanic Zone, New Zealand - Margaret A. Harper; Shirley A. Pledger; Euan G. C. Smith; Alexa R. Van Eaton; Colin J. N. Wilson (Journal of Paleolimnology, 2015)

Howler Monkeys (Alouatta palliata mexicana) Produce Tannin-Binding Salivary Proteins - F. Espinosa Gómez; Juan Santiago García; Sergio Gómez Rosales; Ian R. Wallis; Colin A. Chapman; Jorge Morales Mávil; Domingo Canales Espinosa; Laura Hernández Salazar (International Journal of Primatology, 2015)

Assessing environmental correlates of fish movement on a coral reef - Leanne M. Currey; Michelle R. Heupel; Colin A. Simpfendorfer; Ashley J. Williams (Coral Reefs, 2015)

A multiplex microsatellite set for non-invasive genotyping and sexing of the osprey (Pandion haliaetus) - Deborah A. Dawson; Oddmund Kleven; Natalie dos Remedios; Gavin J. Horsburgh; Rolf T. Kroglund; Teresa Santos; Colin R. A. Hewitt (Conservation Genetics Resources, 2015)

Fluorescence Quantum Yields of Natural Organic Matter and Organic Compounds: Implications for the Fluorescence-based Interpretation of Organic Matter Composition - Urban J. Wünsch; Kathleen R. Murphy; Colin A. Stedmon (Frontiers in Marine Science, 2015)

Development of a Generic Anti-PEG Antibody Assay Using BioScale’s Acoustic Membrane MicroParticle Technology - Huijin Dong; Johanna R. Mora; Catherine Brockus; Shannon D. Chilewski; Robert Dodge; Colin Merrifield; W. Matthew Dickerson; Binodh DeSilva (The AAPS Journal, 2015)

Spatio-Temporal Occurrence Patterns of Young Sharks in Tropical Coastal Waters - Peter M. Yates; Michelle R. Heupel; Andrew J. Tobin; Colin A. Simpfendorfer (Estuaries and Coasts, 2015)

Sensory integration during foraging: the importance of fruit hardness, colour, and odour to brown lemurs - Kim Valenta; Kevin A. Brown; Radoniaina R. Rafaliarison; Sarah A. Styler; Derek Jackson; Shawn M. Lehman; Colin A. Chapman; Amanda D. Melin (Behavioral Ecology and Sociobiology, 2015)

Prediction and Validation of Load-Dependent Behavior of the Tibiofemoral and Patellofemoral Joints During Movement - Rachel L. Lenhart; Jarred Kaiser; Colin R. Smith; Darryl G. Thelen (Annals of Biomedical Engineering, 2015)

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2015)

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2015)

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2015)

Book Review - Colin R. Meyer (Pure and Applied Geophysics, 2015)

Publishing and sharing multi-dimensional image data with OMERO - Jean-Marie Burel; Sébastien Besson; Colin Blackburn; Mark Carroll; Richard K. Ferguson; Helen Flynn; Kenneth Gillen; Roger Leigh; Simon Li; Dominik Lindner; Melissa Linkert; William J. Moore; et al. (Mammalian Genome, 2015)

Social and Ecological Correlates of Parasitic Infections in Adult Male Gray-Cheeked Mangabeys (Lophocebus albigena) - Małgorzata E. Arlet; Colin A. Chapman; Lynne A. Isbell; Freerk Molleman; Raivo Mänd; Peeter Hõrak; James R. Carey (International Journal of Primatology, 2015)

Intravitreal injection of lipoamino acid-modified connexin43 mimetic peptide enhances neuroprotection after retinal ischemia - Ying-Shan Chen; Colin R. Green; Rebecca Teague; Joshua Perrett; Helen V. Danesh-Meyer; Istvan Toth; Ilva D. Rupenthal (Drug Delivery and Translational Research, 2015)

Combining asset- and species-led alien plant management priorities in the world’s most intact Mediterranean-climate landscape - Carl R. Gosper; Suzanne M. Prober; Colin J. Yates; John K. Scott (Biodiversity and Conservation, 2015)

Photosynthetic innovation broadens the niche within a single species - Marjorie R. Lundgren; Guillaume Besnard; Brad S. Ripley; Caroline E. R. Lehmann; David S. Chatelet; Ralf G. Kynast; Mary Namaganda; Maria S. Vorontsova; Russell C. Hall; John Elia; Colin P. Osborne; Pascal‐Antoine Christin (Ecology Letters, 2015)
Adaptation to changing environments often requires novel traits, but how such traits directly affect the ecological niche remains poorly understood. Multiple plant lineages have evolved C 4 photosynthesis, a combination of anatomical and biochemical novelties predicted to increase productivity in warm and arid conditions. Here, we infer the dispersal history across geographical and environmental space in the only known species with both C 4 and non‐C 4 genotypes, the grass Alloteropsis semialata . While non‐C 4 individuals remained confined to a limited geographic area and restricted ecological conditions, C 4 individuals dispersed across three continents and into an expanded range of environments, encompassing the ancestral one. This first intraspecific investigation of C 4 evolutionary ecology shows that, in otherwise similar plants, C 4 photosynthesis does not shift the ecological niche, but broadens it, allowing dispersal into diverse conditions and over long distances. Over macroevolutionary timescales, this immediate effect can be blurred by subsequent specialisation towards more extreme niches.

Movement patterns of silvertip sharks (Carcharhinus albimarginatus) on coral reefs - Mario Espinoza; Michelle. R. Heupel; Andrew J. Tobin; Colin A. Simpfendorfer (Coral Reefs, 2015)

Invasive toads shift predator–prey densities in animal communities by removing top predators - J. Sean Doody; Rebekah Soanes; Christina M. Castellano; David Rhind; Brian Green; Colin R. McHenry; Simon Clulow (Ecology, 2015)
Although invasive species can have substantial impacts on animal communities, cases of invasive species facilitating native species by removing their predators have rarely been demonstrated across vertebrate trophic linkages. The predictable spread of the invasive cane toad ( Rhinella marina ), however, offered a unique opportunity to quantify cascading effects. In northern Australia, three species of predatory monitor lizards suffered severe population declines due to toad‐induced lethal toxic ingestion (yellow‐spotted monitor [ Varanus panoptes ], Mertens' water monitor [ V. mertensi ], Mitchell's water monitor [ V. mitchelli ]). We, thus, predicted subsequent increases in the abundance and recruitment of prey species due to the reduction of those predators. Toad‐induced population‐level declines in the water monitor species approached 50% over a five‐year period spanning the toad invasion, apparently causing fledging success of the Crimson Finch ( Neochmia phaeton ) to increase from 55% to 81%. The consensus of our original and published long‐term data is that invasive cane toads are causing predators to lose a foothold on top‐down regulation of their prey, triggering shifts in the relative densities of predator and prey in the Australian tropical savannah ecosystem.

Noradrenergic modulation of risk/reward decision making - David R. Montes; Colin M. Stopper; Stan B. Floresco (Psychopharmacology, 2015)

Fine-scale temporal recovery, reconstruction and evolution of a post-supereruption magmatic system - Simon J. Barker; Colin J. N. Wilson; Aidan S. R. Allan; C. Ian Schipper (Contributions to Mineralogy and Petrology, 2015)

MAGIC populations in crops: current status and future prospects - B. Emma Huang; Klara L. Verbyla; Arunas P. Verbyla; Chitra Raghavan; Vikas K. Singh; Pooran Gaur; Hei Leung; Rajeev K. Varshney; Colin R. Cavanagh (Theoretical and Applied Genetics, 2015)

Reproductive consequences of the timing of seasonal movements in a nonmigratory wild bird population - Eleni Matechou; San Chye Cheng; Lindall R. Kidd; Colin J. Garroway (Ecology, 2015)
Animal movement patterns, whether related to dispersal, migration, or ranging behaviors, vary in time. Individual movements reflect the outcomes of interactions between an individual's condition and a multitude of underlying ecological processes. Theory predicts that when competition for breeding territories is high, individuals should arrive at breeding sites earlier than what would otherwise be optimal for breeding in the absence of competition. This is because priority at a site can confer significant competitive advantages leading to better breeding outcomes. Empirical data from long‐distance migrants support this theory. However, it has not been tested within the context of fine‐scale movements in nonmigratory populations. We assessed the effect of arrival time at a breeding site on reproductive outcomes in an intensively monitored resident population of Great Tits ( Parus major ). The population was monitored passively, via passive integrated transponder (PIT) tag loggers, and actively, via catching, during breeding and nonbreeding seasons. We developed new capture–recapture–resight models that use both data types to model breeding outcome conditional on the unknown individual arrival times. In accordance with theory, individuals arrived at the woods synchronously in waves that were large at the beginning of the nonbreeding season and small toward the end, with very few arrivals in the intervening period. There was a strong effect of arrival time on the probability of breeding; the earlier an individual arrived, the more likely it was to successfully establish a nest that reached the incubation period. However, once nests were established, they had equal probabilities of failing early, regardless of arrival time. Finally, there was moderate evidence of a negative effect of arrival time on the probability of successfully fledging nestlings. These empirical findings are consistent with theoretical models that suggest an important role for competition in shaping fine‐scale seasonal movements. Our capture–recapture–resight models are extensible and suitable for a variety of applications, particularly when the goal is to estimate the effects of unobservable arrival times on subsequent ecological outcomes.

Inferring social structure from temporal data - Ioannis Psorakis; Bernhard Voelkl; Colin J. Garroway; Reinder Radersma; Lucy M. Aplin; Ross A. Crates; Antica Culina; Damien R. Farine; Josh A. Firth; Camilla A. Hinde; Lindall R. Kidd; Nicole D. Milligan; et al. (Behavioral Ecology and Sociobiology, 2015)

Climate warming and agricultural stressors interact to determine stream macroinvertebrate community dynamics - Jeremy J. Piggott; Colin R. Townsend; Christoph D. Matthaei (Global Change Biology, 2015)
Global climate change is likely to modify the ecological consequences of currently acting stressors, but potentially important interactions between climate warming and land‐use related stressors remain largely unknown. Agriculture affects streams and rivers worldwide, including via nutrient enrichment and increased fine sediment input. We manipulated nutrients (simulating agricultural run‐off) and deposited fine sediment (simulating agricultural erosion) (two levels each) and water temperature (eight levels, 0–6°C above ambient) simultaneously in 128 streamside mesocosms to determine the individual and combined effects of the three stressors on macroinvertebrate community dynamics (community composition and body size structure of benthic, drift and insect emergence assemblages). All three stressors had pervasive individual effects, but in combination often produced additive or antagonistic outcomes. Changes in benthic community composition showed a complex interplay among habitat quality (with or without sediment), resource availability (with or without nutrient enrichment) and the behavioural/physiological tendency to drift or emerge as temperature rose. The presence of sediment and raised temperature both resulted in a community of smaller organisms. Deposited fine sediment strongly increased the propensity to drift. Stressor effects were most prominent in the benthic assemblage, frequently reflected by opposite patterns in individuals quitting the benthos (in terms of their propensity to drift or emerge). Of particular importance is that community measures of stream health routinely used around the world (taxon richness, EPT richness and diversity) all showed complex three‐way interactions, with either a consistently stronger temperature response or a reversal of its direction when one or both agricultural stressors were also in operation. The negative effects of added fine sediment, which were often stronger at raised temperatures, suggest that streams already impacted by high sediment loads may be further degraded under a warming climate. However, the degree to which this will occur may also depend on in‐stream nutrient conditions.

Adaptive evolution in urban ecosystems - Colin M. Donihue; Max R. Lambert (Ambio, 2015)

Conserved transcriptional responses to cyanobacterial stressors are mediated by alternate regulation of paralogous genes in Daphnia - Jana Asselman; Michael E. Pfrender; Jacqueline A. Lopez; Dieter I. M. De Coninck; Colin R. Janssen; Joseph R. Shaw; Karel A. C. De Schamphelaere (Molecular Ecology, 2015)
Despite a significant increase in genomic data, our knowledge of gene functions and their transcriptional responses to environmental stimuli remains limited. Here, we use the model keystone species Daphnia pulex to study environmental responses of genes in the context of their gene family history to better understand the relationship between genome structure and gene function in response to environmental stimuli. Daphnia were exposed to five different treatments, each consisting of a diet supplemented with one of five cyanobacterial species, and a control treatment consisting of a diet of only green algae. Differential gene expression profiles of Daphnia exposed to each of these five cyanobacterial species showed that genes with known functions are more likely to be shared by different expression profiles, whereas genes specific to the lineage of Daphnia are more likely to be unique to a given expression profile. Furthermore, while only a small number of nonlineage‐specific genes were conserved across treatment type, there was a high degree of overlap in expression profiles at the functional level. The conservation of functional responses across the different cyanobacterial treatments can be attributed to the treatment‐specific expression of different paralogous genes within the same gene family. Comparison with available gene expression data in the literature suggests differences in nutritional composition in diets with cyanobacterial species compared to diets of green algae as a primary driver for cyanobacterial effects on Daphnia . We conclude that conserved functional responses in Daphnia across different cyanobacterial treatments are mediated through alternate regulation of paralogous gene families.

Conservation challenges of sharks with continental scale migrations - Michelle R. Heupel; Colin A. Simpfendorfer; Mario Espinoza; Amy F. Smoothey; Andrew Tobin; Victor Peddemors (Frontiers in Marine Science, 2015)

The genetic basis of resistance to barley grass yellow rust (Puccinia striiformis f. sp. pseudo-hordei) in Australian barley cultivars - Lida Derevnina; Meixue Zhou; Davinder Singh; Colin R. Wellings; Robert F. Park (Theoretical and Applied Genetics, 2015)

Quantifying the effects of light intensity on bioproduction and maintenance energy during photosynthetic growth of Rhodobacter sphaeroides - Saheed Imam; Colin M. Fitzgerald; Emily M. Cook; Timothy J. Donohue; Daniel R. Noguera (Photosynthesis Research, 2015)

Enrichment of U–Se–Mo–Re–V in coals preserved within marine carbonate successions: geochemical and mineralogical data from the Late Permian Guiding Coalfield, Guizhou, China - Shifeng Dai; Vladimir V. Seredin; Colin R. Ward; James C. Hower; Yunwei Xing; Weiguo Zhang; Weijiao Song; Peipei Wang (Mineralium Deposita, 2015)

Residency patterns and movements of grey reef sharks (Carcharhinus amblyrhynchos) in semi-isolated coral reef habitats - Mario Espinoza; Michelle. R. Heupel; Andrew J. Tobin; Colin A. Simpfendorfer (Marine Biology, 2015)

Determinants of Reproductive Performance Among Female Gray-Cheeked Mangabeys (Lophocebus albigena) in Kibale National Park, Uganda - Małgorzata E. Arlet; Lynne A. Isbell; Ants Kaasik; Freerk Molleman; Rebecca L. Chancellor; Colin A. Chapman; Raivo Mänd; James R. Carey (International Journal of Primatology, 2015)

Climate warming and agricultural stressors interact to determine stream periphyton community composition - Jeremy J. Piggott; Romana K. Salis; Gavin Lear; Colin R. Townsend; Christoph D. Matthaei (Global Change Biology, 2015)
Lack of knowledge about how the various drivers of global climate change will interact with multiple stressors already affecting ecosystems is the basis for great uncertainty in projections of future biological change. Despite concerns about the impacts of changes in land use, eutrophication and climate warming in running waters, the interactive effects of these stressors on stream periphyton are largely unknown. We manipulated nutrients (simulating agricultural runoff), deposited fine sediment (simulating agricultural erosion) (two levels each) and water temperature (eight levels, 0–6 °C above ambient) simultaneously in 128 streamside mesocosms. Our aim was to determine the individual and combined effects of the three stressors on the algal and bacterial constituents of the periphyton. All three stressors had pervasive individual effects, but in combination frequently produced synergisms at the population level and antagonisms at the community level. Depending on sediment and nutrient conditions, the effect of raised temperature frequently produced contrasting response patterns, with stronger or opposing effects when one or both stressors were augmented. Thus, warming tended to interact negatively with nutrients or sediment by weakening or reversing positive temperature effects or strengthening negative ones. Five classes of algal growth morphology were all affected in complex ways by raised temperature, suggesting that these measures may prove unreliable in biomonitoring programs in a warming climate. The evenness and diversity of the most abundant bacterial taxa increased with temperature at ambient but not with enriched nutrient levels, indicating that warming coupled with nutrient limitation may lead to a more evenly distributed bacterial community as temperatures rise. Freshwater management decisions that seek to avoid or mitigate the negative effects of agricultural land use on stream periphyton should be informed by knowledge of the interactive effects of multiple stressors in a warming climate.

Computationally efficient map construction in the presence of segregation distortion - Rohan Shah; Colin R. Cavanagh; B. Emma Huang (Theoretical and Applied Genetics, 2014)

Influence of environmental factors on shark and ray movement, behaviour and habitat use: a review - Audrey M. Schlaff; Michelle R. Heupel; Colin A. Simpfendorfer (Reviews in Fish Biology and Fisheries, 2014)

Discriminative stimulus and hypothermic effects of some derivatives of the nAChR agonist epibatidine in mice - Jesse S. Rodriguez; Colin S. Cunningham; Fernando B. Moura; Pauline Ondachi; F. Ivy Carroll; Lance R. McMahon (Psychopharmacology, 2014)

Targeting IL-6 and RANKL signaling inhibits prostate cancer growth in bone - Yu Zheng; Dennis Basel; Shu-Oi Chow; Colette Fong-Yee; Sarah Kim; Frank Buttgereit; Colin R. Dunstan; Hong Zhou; Markus J. Seibel (Clinical & Experimental Metastasis, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Sedentary or mobile? Variability in space and depth use of an exploited coral reef fish - Leanne M. Currey; Michelle R. Heupel; Colin A. Simpfendorfer; Ashley J. Williams (Marine Biology, 2014)

Distribution of sea snakes in the Great Barrier Reef Marine Park: observations from 10 yrs of baited remote underwater video station (BRUVS) sampling - Vinay Udyawer; Mike Cappo; Colin A. Simpfendorfer; Michelle R. Heupel; Vimoksalehi Lukoschek (Coral Reefs, 2014)

Whole-genome QTL analysis for MAGIC - Arūnas P. Verbyla; Andrew W. George; Colin R. Cavanagh; Klara L. Verbyla (Theoretical and Applied Genetics, 2014)

The relative controls on forest fires and fuel source fluctuations in the Holocene deciduous forests of southern Wisconsin, USA - JOSHUA R. MUELLER; COLIN J. LONG; JOSEPH J. WILLIAMS; ANDREA NURSE; KENDRA K. MCLAUCHLAN (Journal of Quaternary Science, 2014)
Reconstructing fire regimes and fuel characteristics is an important aspect of understanding past forest ecosystem processes. Fuel sources and fire regimes in the upper Midwestern United States have been shown to be sensitive to regional climatic variability, such as drought periods on millennial timescales. Yet, records documenting the connections between disturbance activity and the corresponding fuel source fluctuations in mesic deciduous forests and prairie/oak savanna in this region are limited. Thus, it has been difficult to provide a framework to evaluate changes in moisture availability on fire activity and the relationships with fuel source fluctuations in this region. We present high‐resolution charcoal analyses of lake sediments from four sites in southern Wisconsin (USA) to characterize fire activity and fuel source fluctuation in mesic deciduous forests and prairie/oak savanna over the last 10 000 years. We found that fire occurrence across the four study sites has been asynchronous throughout the Holocene, because of site‐specific differences that have strongly influenced local fire regimes. Additionally, we found that during periods of high fire activity the primary fuels were from arboreal sources, and during periods of low fire activity the primary fuels were from non‐arboreal sources. However, fluctuations in fuel sources did not always correspond to changes in vegetation, or changes in fire frequency.

Temporal evolution and compositional signatures of two supervolcanic systems recorded in zircons from Mangakino volcanic centre, New Zealand - George F. Cooper; Colin J. N. Wilson; Bruce L. A. Charlier; Joseph L. Wooden; Trevor R. Ireland (Contributions to Mineralogy and Petrology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Increasing Group Size Alters Behavior of a Folivorous Primate - Jan F. Gogarten; Tyler R. Bonnell; Leone M. Brown; Marco Campenni; Michael D. Wasserman; Colin A. Chapman (International Journal of Primatology, 2014)

Maternal Investment and Infant Survival in Gray-Cheeked Mangabeys (Lophocebus albigena) - Małgorzata E. Arlet; Lynne A. Isbell; Freerk Molleman; Ants Kaasik; Rebecca L. Chancellor; Colin A. Chapman; Raivo Mänd; James R. Carey (International Journal of Primatology, 2014)

Investigation of the Antimicrobial Activity of Bacillus licheniformis Strains Isolated from Retail Powdered Infant Milk Formulae - Avelino Alvarez-Ordóñez; Máire Begley; Tanya Clifford; Thérèse Deasy; Kiera Considine; Paula O’Connor; R. Paul Ross; Colin Hill (Probiotics and Antimicrobial Proteins, 2014)

The ChimERA project: coupling mechanistic exposure and effect models into an integrated platform for ecological risk assessment - F. De Laender; Paul J. van den Brink; Colin R. Janssen; Antonio Di Guardo (Environmental Science and Pollution Research, 2014)

Plant biostimulants: a review on the processing of macroalgae and use of extracts for crop management to reduce abiotic and biotic stresses - H. S. Shekhar Sharma; Colin Fleming; Chris Selby; J. R. Rao; Trevor Martin (Journal of Applied Phycology, 2014)

The contribution of intra‐ and interspecific tolerance variability to biodiversity changes along toxicity gradients - Frederik De Laender; Carlos J. Melian; Richard Bindler; Paul J. Van den Brink; Michiel Daam; Helene Roussel; Jonas Juselius; Dirk Verschuren; Colin R. Janssen (Ecology Letters, 2014)
The worldwide distribution of toxicants is an important yet understudied driver of biodiversity, and the mechanisms relating toxicity to diversity have not been adequately explored. Here, we present a community model integrating demography, dispersal and toxicant‐induced effects on reproduction driven by intraspecific and interspecific variability in toxicity tolerance. We compare model predictions to 458 species abundance distributions (SADs) observed along concentration gradients of toxicants to show that the best predictions occur when intraspecific variability is five and ten times higher than interspecific variability. At high concentrations, lower settings of intraspecific variability resulted in predictions of community extinction that were not supported by the observed SADs. Subtle but significant species losses at low concentrations were predicted only when intraspecific variability dominated over interspecific variability. Our results propose intraspecific variability as a key driver for biodiversity sustenance in ecosystems challenged by environmental change.

Environmental controls of temporal and spatial variability in CO 2 and CH 4 fluxes in a neotropical peatland - Emma L. Wright; Colin R. Black; Benjamin L. Turner; Sofie Sjögersten (Global Change Biology, 2013)
Tropical peatlands play an important role in the global storage and cycling of carbon (C) but information on carbon dioxide ( CO 2 ) and methane ( CH 4 ) fluxes from these systems is sparse, particularly in the Neotropics. We quantified short and long‐term temporal and small scale spatial variation in CO 2 and CH 4 fluxes from three contrasting vegetation communities in a domed ombrotrophic peatland in Panama. There was significant variation in CO 2 fluxes among vegetation communities in the order Campnosperma panamensis > Raphia taedigera > Cyperus . There was no consistent variation among sites and no discernible seasonal pattern of CH 4 flux despite the considerable range of values recorded (e.g. −1.0 to 12.6 mg m −2 h −1 in 2007). CO 2 fluxes varied seasonally in 2007, being greatest in drier periods (300–400 mg m −2 h −1 ) and lowest during the wet period (60–132 mg m −2 h −1 ) while very high emissions were found during the 2009 wet period, suggesting that peak CO 2 fluxes may occur following both low and high rainfall. In contrast, only weak relationships between CH 4 flux and rainfall (positive at the C. panamensis site) and solar radiation (negative at the C. panamensis and Cyperus sites) was found. CO 2 fluxes showed a diurnal pattern across sites and at the Cyperus sp. site CO 2 and CH 4 fluxes were positively correlated. The amount of dissolved carbon and nutrients were strong predictors of small scale within‐site variability in gas release but the effect was site‐specific. We conclude that (i) temporal variability in CO 2 was greater than variation among vegetation communities; (ii) rainfall may be a good predictor of CO 2 emissions from tropical peatlands but temporal variation in CH 4 does not follow seasonal rainfall patterns; and (iii) diurnal variation in CO 2 fluxes across different vegetation communities can be described by a Fourier model.

The involvement of gibberellin signalling in the effect of soil resistance to root penetration on leaf elongation and tiller number in wheat - Mauricio A. Coelho Filho; Ellen H. Colebrook; David P. A. Lloyd; Colin P. Webster; Sacha J. Mooney; Andrew L. Phillips; Peter Hedden; William R. Whalley (Plant and Soil, 2013)

Native fish avoid parasite spillback from multiple exotic hosts: consequences of host density and parasite competency - Rachel A. Paterson; Carlos A. Rauque; M. Valeria Fernandez; Colin R. Townsend; Robert Poulin; Daniel M. Tompkins (Biological Invasions, 2013)

Mechanical double layer model for Saccharomyces Cerevisiae cell wall - Ruben Mercadé-Prieto; Colin R. Thomas; Zhibing Zhang (European Biophysics Journal, 2013)

Multiple nicotine training doses in mice as a basis for differentiating the effects of smoking cessation aids - Colin S. Cunningham; Lance R. McMahon (Psychopharmacology, 2013)

Risk of dietary magnesium deficiency is low in most African countries based on food supply data - Edward J. M. Joy; Scott D. Young; Colin R. Black; E. Louise Ander; Michael J. Watts; Martin R. Broadley (Plant and Soil, 2013)

From mush to eruption in centuries: assembly of the super-sized Oruanui magma body - Aidan S. R. Allan; Daniel J. Morgan; Colin J. N. Wilson; Marc-Alban Millet (Contributions to Mineralogy and Petrology, 2013)

Movements of juvenile endangered smalltooth sawfish, Pristis pectinata, in an estuarine river system: use of non-main-stem river habitats and lagged responses to freshwater inflow-related changes - Gregg R. Poulakis; Philip W. Stevens; Amy A. Timmers; Christopher J. Stafford; Colin A. Simpfendorfer (Environmental Biology of Fishes, 2013)

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

The Influence of Vegetation on Microbial Enzyme Activity and Bacterial Community Structure in Freshwater Constructed Wetland Sediments - Rani Menon; Colin R. Jackson; Marjorie M. Holland (Wetlands, 2013)

Genetic and molecular analyses of resistance to a variant of Puccinia striiformis in barley - Prashant G. Golegaonkar; Colin R. Wellings; Davinder Singh; Robert F. Park (Journal of Applied Genetics, 2013)

Are Primates Ecosystem Engineers? - Colin A. Chapman; Tyler R. Bonnell; Jan F. Gogarten; Joanna E. Lambert; Patrick A. Omeja; Dennis Twinomugisha; Michael D. Wasserman; Jessica M. Rothman (International Journal of Primatology, 2013)

Growth of volcanic ash aggregates in the presence of liquid water and ice: an experimental approach - Alexa R. Van Eaton; James D. Muirhead; Colin J. N. Wilson; Corrado Cimarelli (Bulletin of Volcanology, 2012)

Investigation of the Cry4B–Prohibitin Interaction in Aedes aegypti Cells - Atichat Kuadkitkan; Duncan R. Smith; Colin Berry (Current Microbiology, 2012)

A Common View of the Opportunities, Challenges, and Research Actions for Pongamia in Australia - Helen T. Murphy; Deborah A. O’Connell; Gary Seaton; R. John Raison; Luis C. Rodriguez; Andrew L. Braid; Darren J. Kriticos; Tom Jovanovic; Amir Abadi; Michael Betar; Heather Brodie; Malcolm Lamont; et al. (BioEnergy Research, 2012)

Temperate and tropical brown macroalgae thrive, despite decalcification, along natural CO 2 gradients - Vivienne R. Johnson; Bayden D. Russell; Katharina E. Fabricius; Colin Brownlee; Jason M. Hall‐Spencer (Global Change Biology, 2012)
Predicting the impacts of ocean acidification on coastal ecosystems requires an understanding of the effects on macroalgae and their grazers, as these underpin the ecology of rocky shores. Whilst calcified coralline algae (Rhodophyta) appear to be especially vulnerable to ocean acidification, there is a lack of information concerning calcified brown algae (Phaeophyta), which are not obligate calcifiers but are still important producers of calcium carbonate and organic matter in shallow coastal waters. Here, we compare ecological shifts in subtidal rocky shore systems along CO 2 gradients created by volcanic seeps in the Mediterranean and Papua New Guinea, focussing on abundant macroalgae and grazing sea urchins. In both the temperate and tropical systems the abundances of grazing sea urchins declined dramatically along CO 2 gradients. Temperate and tropical species of the calcifying macroalgal genus Padina (Dictyoaceae, Phaeophyta) showed reductions in Ca CO 3 content with CO 2 enrichment. In contrast to other studies of calcified macroalgae, however, we observed an increase in the abundance of Padina spp. in acidified conditions. Reduced sea urchin grazing pressure and significant increases in photosynthetic rates may explain the unexpected success of decalcified Padina spp. at elevated levels of CO 2 . This is the first study to provide a comparison of ecological changes along CO 2 gradients between temperate and tropical rocky shores. The similarities we found in the responses of Padina spp. and sea urchin abundance at several vent systems increases confidence in predictions of the ecological impacts of ocean acidification over a large geographical range .

To roam or to home: site fidelity in a tropical coastal shark - Danielle M. Knip; Michelle R. Heupel; Colin A. Simpfendorfer (Marine Biology, 2012)

A comment on: ‘TitaniQ under pressure: the effect of pressure and temperature on the solubility of Ti in quartz’, by Jay B. Thomas, E. Bruce Watson, Frank S. Spear, Philip T. Shemella, Saroj K. Nayak and Antonio Lanzirotti - Colin J. N. Wilson; Terry M. Seward; Aidan S. R. Allan; Bruce L. A. Charlier; Léa Bello (Contributions to Mineralogy and Petrology, 2012)

Influence of climate oscillations on dentinal deposition in teeth of Commerson's dolphin - Natalia A. Dellabianca; Aleta A. Hohn; R. Natalie P. Goodall; Jorge L. Pousa; Colin D. MacLeod; Mauricio Lima (Global Change Biology, 2012)
Effects of climatic oscillations on populations in marine environments are produced mainly through the lower trophic levels. Marine mammals, as top predators, are affected indirectly by these fluctuations, showing variations in their survival, growth and reproduction. The main objective of this study was to determine whether we could detect the effect of climatic oscillations on Commerson's dolphins ( Cephalorhynchus c. commersonii ) off Tierra del Fuego, Argentina, by examining the presence and proportion of anomalous dentinal growth layer groups ( GLG s). The relative deposition of anomalous GLG s was determined using calendar years from 1960 to 2005, and related to the Southern Annular Mode ( SAM ) and El Niño Southern Oscillation ( ENSO ) events, and to mean annual sea surface temperatures ( SST ). Then, growth parameters between animals that did and did not show anomalous dentinal growth layer patterns in one or more of their GLG s were compared. The presence of anomalous GLG s was related to the SAM , increasing in frequency with negative values of the SAM . No relationship was found among anomalous GLG s, ENSO , and SST . There were no significant differences in growth parameters between animals with and without anomalous GLG s. Using recording structures such as teeth provided a unique way of reconstructing time series to evaluate the effects of these climatic patterns on a top predator species in an area where no similar studies have been conducted, primarily due to a lack of suitable long‐term data sets.

Regulation of Connexin43 Gap Junction Protein Triggers Vascular Recovery and Healing in Human Ocular Persistent Epithelial Defect Wounds - Susan Ormonde; Chi-Ying Chou; Lucy Goold; Con Petsoglou; Rasha Al-Taie; Trevor Sherwin; Charles N. J. McGhee; Colin R. Green (The Journal of Membrane Biology, 2012)

Soil warming accelerates decomposition of fine woody debris - Minda R. Berbeco; Jerry M. Melillo; Colin M. Orians (Plant and Soil, 2012)

Cognitive and serum BDNF correlates of BDNF Val66Met gene polymorphism in patients with schizophrenia and normal controls - Xiang Yang Zhang; Da Chun Chen; Mei Hong Xiu; Colin N. Haile; Xingguang Luo; Ke Xu; Hui Ping Zhang; Lingjun Zuo; Zhijun Zhang; Xiangrong Zhang; Therese A. Kosten; Thomas R. Kosten (Human Genetics, 2012)

Comparison of the Potency of the Lipid II Targeting Antimicrobials Nisin, Lacticin 3147 and Vancomycin Against Gram-Positive Bacteria - Catalin Iancu; Aoife Grainger; Des Field; Paul D. Cotter; Colin Hill; R. Paul Ross (Probiotics and Antimicrobial Proteins, 2012)

Intensity of Land Use in the Catchment Influences Ecosystem Functioning Along a Freshwater-Marine Continuum - Antje M. Bierschenk; Candida Savage; Colin R. Townsend; Christoph D. Matthaei (Ecosystems, 2012)

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

Evaluation of the mayfly Ephoron virgo for European sediment toxicity assessment - Lien T. H. Nguyen; Michiel B. Vandegehuchte; Harm G. van der Geest; Colin R. Janssen (Journal of Soils and Sediments, 2012)

A comparison of the short-term toxicity of cadmium to indigenous and alien gammarid species - Pieter Boets; Koen Lock; Peter L. M. Goethals; Colin R. Janssen; Karel A. C. De Schamphelaere (Ecotoxicology, 2012)

Evolutionary islands in the Andes: persistence and isolation explain high endemism in Andean dry tropical forests - Tiina Särkinen; R. Toby Pennington; Matt Lavin; Marcelo F. Simon; Colin E. Hughes (Journal of Biogeography, 2012)
Aim The tropical Andes are a world biodiversity hotspot. With diverse biomes and dramatic, geologically recent mountain uplift, they offer a system to study the relative contributions of geological and biome history to species richness. There are preliminary indications that historical species assembly in the Andes has been influenced by physiographical heterogeneity and that distinct biomes have evolved in relative isolation despite physical proximity. Here we test this ‘Andean biotic separation hypothesis’ by focusing on the low‐elevation, seasonally dry tropical forest (SDTF) biome to determine whether patterns of plant diversification within the SDTF differ from those in mid‐ and high‐elevation biomes. Location Tropical Andes, South America. Methods Densely sampled time‐calibrated phylogenies for five legume genera ( Amicia , Coursetia , Cyathostegia , Mimosa and Poissonia ) containing species endemic to the Andean SDTF biome were used to investigate divergence times and levels of geographical structure. Geographical structure was measured using isolation‐by‐distance methods. Meta‐analysis of time‐calibrated phylogenies of Andean plant groups was used to compare the pattern and tempo of endemic species diversification between the major Andean biomes. Results Long‐term persistence of SDTF in the Andes is suggested by old stem ages (5–27 Ma) of endemic genera/clades within genera, and deep divergences coupled with strong geographical structure among and within species. Comparison of species diversification patterns among different biomes shows that the relatively old, geographically confined pattern of species diversification in SDTF contrasts with the high‐elevation grasslands that show rapid and recent radiations driven by ecological opportunities. Main conclusions The SDTF biome has a long history in the Andes. We suggest that the diverse SDTF flora has been assembled gradually over the past c . 19 Ma from lineages exhibiting strong phylogenetic niche conservatism. These patterns suggest that Andean SDTFs have formed stable and strongly isolated ‘islands’ despite the upheavals of Andean uplift. Indeed, the Andean SDTFs may represent some of the most isolated and evolutionarily persistent continental plant communities, similar in many respects to floras of remote oceanic islands.

Quantifying the effect of soil compaction on three varieties of wheat (Triticum aestivum L.) using X-ray Micro Computed Tomography (CT) - Saoirse R. Tracy; Colin R. Black; Jeremy A. Roberts; Ann McNeill; Rob Davidson; Mark Tester; Marko Samec; Dean Korošak; Craig Sturrock; Sacha J. Mooney (Plant and Soil, 2012)

Detection of interspecies hybridisation in Chondrichthyes: hybrids and hybrid offspring between Australian (Carcharhinus tilstoni) and common (C. limbatus) blacktip shark found in an Australian fishery - Jess A. T. Morgan; Alastair V. Harry; David J. Welch; Raewyn Street; Jimmy White; Pascal T. Geraghty; William G. Macbeth; Andrew Tobin; Colin A. Simpfendorfer; Jennifer R. Ovenden (Conservation Genetics, 2012)

Predicting possible negative impacts of weed biocontrol by artificially suppressing invasive hawkweed in New Zealand’s tussock grasslands - Pauline Syrett; Guy J. Forrester; Helen M. Harman; Colin D. Meurk; Trevor R. Partridge; Lindsay A. Smith (BioControl, 2012)

Facilitating adaptation of biodiversity to climate change: a conceptual framework applied to the world’s largest Mediterranean-climate woodland - Suzanne M. Prober; Kevin R. Thiele; Philip W. Rundel; Colin J. Yates; Sandra L. Berry; Margaret Byrne; Les Christidis; Carl R. Gosper; Pauline F. Grierson; Kristina Lemson; Tom Lyons; Craig Macfarlane; et al. (Climatic Change, 2012)

A radical approach to beating hypoxia: depressed free radical release from heart fibres of the hypoxia-tolerant epaulette shark (Hemiscyllum ocellatum) - Anthony J. R. Hickey; Gillian M. C. Renshaw; Ben Speers-Roesch; Jeffrey G. Richards; Yuxiang Wang; Anthony P. Farrell; Colin J. Brauner (Journal of Comparative Physiology B, 2012)

Effects of acute administration of nicotine, amphetamine, diazepam, morphine, and ethanol on risky decision-making in rats - Marci R. Mitchell; Colin M. Vokes; Amy L. Blankenship; Nicholas W. Simon; Barry Setlow (Psychopharmacology, 2011)

Contrasting sedimentation rates in Lake Illawarra and St Georges Basin, two large barrier estuaries on the southeast coast of Australia - Craig R. Sloss; Brian G. Jones; Brendan P. Brooke; Henk Heijnis; Colin V. Murray-Wallace (Journal of Paleolimnology, 2011)

Herbivore-Induced Changes in Tomato (Solanum lycopersicum) Primary Metabolism: A Whole Plant Perspective - Adam D. Steinbrenner; Sara Gómez; Sonia Osorio; Alisdair R. Fernie; Colin M. Orians (Journal of Chemical Ecology, 2011)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Expansion of human mesenchymal stem cells on microcarriers - Christopher J. Hewitt; Ken Lee; Alvin W. Nienow; Robert J. Thomas; Mark Smith; Colin R. Thomas (Biotechnology Letters, 2011)

Contribution of subsurface peat to CO 2 and CH 4 fluxes in a neotropical peatland - EMMA L. WRIGHT; COLIN R. BLACK; ALEXANDER W. CHEESMAN; TREVOR DRAGE; DAVID LARGE; BENJAMIN L. TURNER; SOFIE SJÖGERSTEN (Global Change Biology, 2011)
Tropical peatlands play an important role in the global carbon cycling but little is known about factors regulating carbon dioxide (CO 2 ) and methane (CH 4 ) fluxes from these ecosystems. Here, we test the hypotheses that (i) CO 2 and CH 4 are produced mainly from surface peat and (ii) that the contribution of subsurface peat to net C emissions is governed by substrate availability. To achieve this, in situ and ex situ CO 2 and CH 4 fluxes were determined throughout the peat profiles under three vegetation types along a nutrient gradient in a tropical ombrotrophic peatland in Panama. The peat was also characterized with respect to its organic composition using 13 C solid state cross‐polarization magic‐angle spinning nuclear magnetic resonance spectroscopy. Deep peat contributed substantially to CO 2 effluxes both with respect to actual in situ and potential ex situ fluxes. CH 4 was produced throughout the peat profile with distinct subsurface peaks, but net emission was limited by oxidation in the surface layers. CO 2 and CH 4 production were strongly substrate‐limited and a large proportion of the variance in their production (30% and 63%, respectively) was related to the quantity of carbohydrates in the peat. Furthermore, CO 2 and CH 4 production differed between vegetation types, suggesting that the quality of plant‐derived carbon inputs is an important driver of trace gas production throughout the peat profile. We conclude that the production of both CO 2 and CH 4 from subsurface peat is a substantial component of the net efflux of these gases, but that gas production through the peat profile is regulated in part by the degree of decomposition of the peat.

Atmospheric nitrogen deposition explains patterns of plant species loss - COLIN J. McCLEAN; LEON J. L. van den BERG; MIKE R. ASHMORE; CHRIS D. PRESTON (Global Change Biology, 2011)
Atmospheric nitrogen ( N ) deposition across Europe increased substantially from the 1950s to the 1990s. Targeted surveys suggest a negative correlation between N deposition and species richness within quadrats in sensitive habitats. However, it remains unclear whether plant species losses at national recording scales are correlated with nitrogen deposition. We relate plant species losses before 1987 in Great Britain to reduced and oxidized N deposition, land use change and climate change. The mean Ellenberg fertility ( N ) indices of plant species lost in each 100 km 2 cell before 1987 was compared with those of species that were recorded between 1987 and 1999. In 45% of squares, indices of species lost were significantly lower than those for species present after 1986. For 17%, primarily upland, squares, the opposite effect was found. A generalized least squares regression model, with difference in the mean Ellenberg N index between samples as the dependent variable, showed that higher deposition of reduced N was significantly associated with selective loss of species with a lower index. Arable land use and change in arable land use also demonstrated this positive relationship. Rough grazing, change in rough grazing, change in pasture and change in annual precipitation showed negative effects. Difference in Ellenberg R index was highly correlated with difference in Ellenberg N and was negatively correlated with oxidized N deposition, suggesting that the lack of a significant effect of oxidized N deposition on Ellenberg N was because it had effects through both acidification and eutrophication, while the effect of reduced N deposition was primarily through eutrophication. Our results suggest that N deposition, along with land use and precipitation changes, has been a significant driver of local plant extinctions. With N deposition increasing in many parts of the world, local extinctions of plant species may be experienced in other regions.

Negligible evidence for regional genetic population structure for two shark species Rhizoprionodon acutus (Rüppell, 1837) and Sphyrna lewini (Griffith & Smith, 1834) with contrasting biology - Jennifer R. Ovenden; Jess A. T. Morgan; Raewyn Street; Andrew Tobin; Colin Simpfendorfer; William Macbeth; David Welch (Marine Biology, 2011)

Multi-parameter flow cytometry and cell sorting reveal extensive physiological heterogeneity in Bacillus cereus batch cultures - Andrew Want; Helen Hancocks; Colin R. Thomas; Stuart M. Stocks; Gerhard Nebe-von-Caron; Christopher J. Hewitt (Biotechnology Letters, 2011)

Global status of stripe rust: a review of historical and current threats - Colin R. Wellings (Euphytica, 2011)

Epigenetics and its implications for ecotoxicology - Michiel B. Vandegehuchte; Colin R. Janssen (Ecotoxicology, 2011)

Enhanced decomposition of selenium hyperaccumulator litter in a seleniferous habitat—evidence for specialist decomposers? - Colin F. Quinn; Karl A. Wyant; Ami L. Wangeline; Jeremy Shulman; Miriam L. Galeas; Jose Rodolfo Valdez; James R. Self; Mark W. Paschke; Elizabeth A. H. Pilon-Smits (Plant and Soil, 2011)

Further Identification of Novel Lantibiotic Operons Using LanM-Based Genome Mining - Orla O’Sullivan; Máire Begley; R. Paul Ross; Paul D. Cotter; Colin Hill (Probiotics and Antimicrobial Proteins, 2011)

Fire does not facilitate invasion by alien annual grasses in an infertile Australian agricultural landscape - Carl R. Gosper; Colin J. Yates; Suzanne M. Prober; Matthew R. Williams (Biological Invasions, 2011)

Stepping in Elton’s footprints: a general scaling model for body masses and trophic levels across ecosystems - Jens O. Riede; Ulrich Brose; Bo Ebenman; Ute Jacob; Ross Thompson; Colin R. Townsend; Tomas Jonsson (Ecology Letters, 2011)
Ecology Letters (2011) 14: 169–178 Abstract Despite growing awareness of the significance of body‐size and predator–prey body‐mass ratios for the stability of ecological networks, our understanding of their distribution within ecosystems is incomplete. Here, we study the relationships between predator and prey size, body‐mass ratios and predator trophic levels using body‐mass estimates of 1313 predators (invertebrates, ectotherm and endotherm vertebrates) from 35 food‐webs (marine, stream, lake and terrestrial). Across all ecosystem and predator types, except for streams (which appear to have a different size structure in their predator–prey interactions), we find that (1) geometric mean prey mass increases with predator mass with a power‐law exponent greater than unity and (2) predator size increases with trophic level. Consistent with our theoretical derivations, we show that the quantitative nature of these relationships implies systematic decreases in predator–prey body‐mass ratios with the trophic level of the predator. Thus, predators are, on an average, more similar in size to their prey at the top of food‐webs than that closer to the base. These findings contradict the traditional Eltonian paradigm and have implications for our understanding of body‐mass constraints on food‐web topology, community dynamics and stability.

Genetics and mapping of seedling resistance to Ug99 stem rust in Canadian wheat cultivars ‘Peace’ and ‘AC Cadillac’ - Colin W. Hiebert; Tom G. Fetch; Taye Zegeye; Julian B. Thomas; Daryl J. Somers; D. Gavin Humphreys; Brent D. McCallum; Sylvie Cloutier; Davinder Singh; Doug R. Knott (Theoretical and Applied Genetics, 2011)

Healthy baboon with no upper jaw or nose: an extreme case of adaptability in the Kibale National Park, Uganda - Thomas T. Struhsaker; Colin A. Chapman; Theresa R. Pope; Jeffrey R. Marcus (Primates, 2011)

Neuromelanin Activates Microglia and Induces Degeneration of Dopaminergic Neurons: Implications for Progression of Parkinson’s Disease - Wei Zhang; Kester Phillips; Albert R. Wielgus; Jie Liu; Alberto Albertini; Fabio A. Zucca; Rudolph Faust; Steven Y. Qian; David S. Miller; Colin F. Chignell; Belinda Wilson; Vernice Jackson-Lewis; et al. (Neurotoxicity Research, 2011)

Genetic tools to support the conservation of the endangered smalltooth sawfish, Pristis pectinata - Kevin A. Feldheim; Demian D. Chapman; Colin A. Simpfendorfer; Vincent P. Richards; Mahmood S. Shivji; Tonya R. Wiley; Gregg R. Poulakis; John K. Carlson; Rowena Eng; Skyler Sagarese (Conservation Genetics Resources, 2010)

Palatability mapping: a koala's eye view of spatial variation in habitat quality - Ben D. Moore; Ivan R. Lawler; Ian R. Wallis; Colin M. Beale; William J. Foley (Ecology, 2010)
Ecologists trying to understand the value of habitat to animals must first describe the value of resources contained in the habitat to animals and, second, they must describe spatial variation in resource quality at a resolution relevant to individual animal foraging. We addressed these issues in a study of koalas ( Phascolarctos cinereus ) in a Eucalyptus woodland. We measured beneficial and deterrent chemical characteristics as well as the palatability of trees using a near‐infrared spectroscopic model based on direct feeding experiments. Tree use by koalas was influenced by tree size and foliar quality but was also context‐dependent: trees were more likely to be visited if they were surrounded by small, unpalatable trees or by large, palatable trees. Spatial autocorrelation analysis and several mapping approaches demonstrated that foliar quality is spatially structured in the woodland at a scale relevant to foraging decisions by koalas and that the spatial structure is an important component of habitat quality.

An investigation into the preservation of microbial cell banks for α-amylase production during 5 l fed-batch Bacillus licheniformis fermentations - Nichola H. Hancocks; Colin R. Thomas; Stuart M. Stocks; Christopher J. Hewitt (Biotechnology Letters, 2010)

Sponge and dough bread making: genetic and phenotypic relationships with wheat quality traits - Colin R. Cavanagh; Julian Taylor; Oscar Larroque; Neil Coombes; Arunas P. Verbyla; Zena Nath; Ibrahim Kutty; Lynette Rampling; Barbara Butow; Jean-Philippe Ral; Sandor Tomoskozi; Gabor Balazs; et al. (Theoretical and Applied Genetics, 2010)

Molecular data provide strong evidence of natural hybridization between native and introduced lineages of Phragmites australis in North America - Jennifer Paul; Nicole Vachon; Colin J. Garroway; Joanna R. Freeland (Biological Invasions, 2010)

Modulation of high sensitivity C-reactive protein by soluble receptor for advanced glycation end products - Erick D. McNair; Calvin R. Wells; A. Mabood Qureshi; Rashpal Basran; Colin Pearce; Jason Orvold; Jacobus Devilliers; Kailash Prasad (Molecular and Cellular Biochemistry, 2010)

Do S-type granites commonly sample infracrustal sources? New results from an integrated O, U–Pb and Hf isotope study of zircon - Sarah K. Appleby; Martin R. Gillespie; Colin M. Graham; Richard W. Hinton; Grahame J. H. Oliver; Nigel M. Kelly (Contributions to Mineralogy and Petrology, 2010)

A virgin flight across the Tasman Sea? Satellite tracking of post-fledging movement in the Australasian Gannet Morus serrator - Stefanie M. H. Ismar; Colin Hunter; Kevin Lay; Tamsin Ward-Smith; Peter R. Wilson; Mark E. Hauber (Journal of Ornithology, 2010)

The influence of vegetation type, soil properties and precipitation on the composition of soil mite and microbial communities at the landscape scale - Uffe N. Nielsen; Graham H. R. Osler; Colin D. Campbell; David F. R. P. Burslem; René van der Wal (Journal of Biogeography, 2010)
Aim We used a landscape‐scale study of birch invasion onto heather moorland to determine the consistency of changes in vegetation type and soil properties and in the community composition of five soil organism groups. Our aim was to determine whether the degree to which soil organisms respond to natural changes and/or induced changes (e.g. changes in land‐use type and climate) in habitat is consistent across trophic and taxonomic groups in the context of conservation policies for birch woodland and heather moorland. Location Mainland Scotland. Methods We sampled mesostigmatid mites, oribatid mites, fungi, bacteria and archaea in adjacent patches of birch woodland (dominated by Betula pubescens ) and heather moorland (dominated by Calluna vulgaris ) at 12 sites for which annual rainfall ranged between 713 and 2251 mm. Differences in community composition were visualized using non‐metric multidimensional scaling based on Bray–Curtis dissimilarities. The factors contributing to differences between habitats within sites were explored using general linear models and those among sites using redundancy analysis. Results The communities of all groups differed between habitats within sites, but only the oribatid mites and fungi differed consistently between habitats across sites. Within sites, dissimilarity in fungal communities was positively related to the difference in C. vulgaris cover between habitats, whereas dissimilarities in bacteria and archaea were positively related to differences in soil pH and C:N ratio between habitats, respectively. Main conclusions The influence of vegetation type and soil properties differed between groups of soil organisms, albeit in a predictable manner, across the 12 sites. Organisms directly associated with plants (fungi), and organisms with microhabitat and resource preferences (Oribatida) were strongly responsive to changes in habitat type. The response of organisms not directly associated with plants (bacteria, archaea) depended on differences in soil properties, while organisms with less clear microhabitat and resource preferences (Mesostigmata) were not strongly responsive to either vegetation type or soil properties. These results show that it is possible to predict the impact of habitat change on specific soil organisms depending on their ecology. Moreover, the community composition of all groups was related to variation in precipitation within the study area, which shows that external factors, such as those caused by climate change, can have a direct effect on belowground communities.

Determination of total antibiotic resistance in waterborne bacteria in rivers and streams in Northern Ireland: Can antibiotic-resistant bacteria be an indicator of ecological change? - John E. Moore; Juluri R. Rao; Peter J. A. Moore; B. Cherie Millar; Colin E. Goldsmith; Anne Loughrey; Paul J. Rooney (Aquatic Ecology, 2010)

A Serial Analysis of Gene Expression Profile of the Alzheimer’s Disease Tg2576 Mouse Model - Amee J. George; Lavinia Gordon; Tim Beissbarth; Irene Koukoulas; R. M. Damian Holsinger; Victoria Perreau; Roberto Cappai; Seong-Seng Tan; Colin L. Masters; Hamish S. Scott; Qiao-Xin Li (Neurotoxicity Research, 2010)

Comparison of zooplankton vertical migration in an ice‐free and a seasonally ice‐covered Arctic fjord: An insight into the influence of sea ice cover on zooplankton behavior - Margaret I. Wallace; Finlo R. Cottier; Jørgen Berge; Geraint A. Tarling; Colin Griffiths; Andrew S. Brierley (Limnology and Oceanography, 2010)
We present observations of zooplankton diel vertical migration (DVM) over a period of 2 yr in an ice‐free and a seasonally ice‐covered Arctic fjord. The contrasting environments permitted assessment of the influences of physical and biological factors on temporal variability in DVM patterns and a test of the hypothesis that a reduction in summer sea ice extent and thickness following climatic warming will lead to changes in DVM via the loss of a shading effect on the pelagic marine environment. Acoustic backscatter and vertical velocity data from moored 300‐kHz acoustic Doppler current profilers were used to derive DVM patterns, while measurements of sea ice and snow thickness enabled assessment of the underwater light environment and consideration of its potential to influence DVM. Pronounced differences in DVM between the sites emerged during summertime when intermittent synchronized DVM was observed at the ice‐free site, whereas the ice‐covered site was characterized by asynchronous behavior, thereby highlighting the influence of sea ice. Notably, the 0.8‐m‐thick sea ice cover was deemed important for its influence on water column properties such as food, turbidity, and zooplankton species composition, as indicated by biological samples from moored sediment traps, rather than a simple shading of the ocean and direct modification of zooplankton DVM. Loss of Arctic sea ice is likely to have an indirect but substantial effect on zooplankton DVM via modification of hydrography and composition of the pelagic community.

Climate change induced hybridization in flying squirrels - COLIN J. GARROWAY; JEFF BOWMAN; TARA J. CASCADEN; GILLIAN L. HOLLOWAY; CAROLYN G. MAHAN; JAY R. MALCOLM; MICHAEL A. STEELE; GREGORY TURNER; PAUL J. WILSON (Global Change Biology, 2010)
There is now unequivocal evidence for global climate change; however, its potential impacts on evolutionary processes remain unclear. Many species have responded to contemporary climate change through shifts in their geographic range. This could lead to increased sympatry between recently diverged species; likely increasing the potential for hybridization. Recently, following a series of warm winters, southern flying squirrels ( Glaucomys volans ) in Ontario, Canada rapidly expanded their northern range limit resulting in increased sympatry with the closely related northern flying squirrel ( Glaucomys sabrinus ). This provided the opportunity to test the prediction that contemporary climate change can act as a catalyst creating conditions for the formation of hybrid zones. Following extensive sampling and molecular analyses (nuclear and mitochondrial DNA), we identified the occurrence of hybridization between sympatric G. sabrinus and G. volans . There was evidence of backcrossing but not of extensive introgession, consistent with the hypothesis of recent rather than historic hybridization. To our knowledge, this is the first report of hybrid zone formation following a range expansion induced by contemporary climate change. This is also the first report of hybridization between North American flying squirrel species.

Habitat preference and dispersal of the Duke of Burgundy butterfly (Hamearis lucina) on an abandoned chalk quarry in Bedfordshire, UK - Edgar C. Turner; Hanna M. V. Granroth; Henry R. Johnson; Colin B. H. Lucas; Alex M. Thompson; Hannah Froy; Richard N. German; Ross Holdgate (Journal of Insect Conservation, 2009)

Rapid Assessment of the Nutritional Value of Foods Eaten by Mountain Gorillas: Applying Near-Infrared Reflectance Spectroscopy to Primatology - Jessica M. Rothman; Colin A. Chapman; Julie L. Hansen; Debbie J. R. Cherney; Alice N. Pell (International Journal of Primatology, 2009)

Effect of an invasive grass on ambient rates of decomposition and microbial community structure: a search for causality - D. Christopher Holly; Gary N. Ervin; Colin R. Jackson; Susan V. Diehl; Grant T. Kirker (Biological Invasions, 2009)

Amyloid Imaging in Alzheimer’s Disease and Other Dementias - Michelle T. Fodero-Tavoletti; Roberto Cappai; Catriona A. McLean; Kerryn E. Pike; Paul A. Adlard; Tiffany Cowie; Andrea R. Connor; Colin L. Masters; Christopher C. Rowe; Victor L. Villemagne (Brain Imaging and Behavior, 2009)

Development and evaluation of a rapid immunomagnetic bead assay for the detection of classical swine fever virus antigen - James V. Conlan; Syseng Khounsy; Stuart D. Blacksell; Christopher J. Morrissy; Colin R. Wilks; Laurence J. Gleeson (Tropical Animal Health and Production, 2009)

Alternative splicing, activation of cryptic exons and amino acid substitutions in carotenoid biosynthetic genes are associated with lutein accumulation in wheat endosperm - Crispin A. Howitt; Colin R. Cavanagh; Andrew F. Bowerman; Christopher Cazzonelli; Lynette Rampling; Joanna L. Mimica; Barry J. Pogson (Functional & Integrative Genomics, 2009)

Sub-lingual oral fistulas in Sooty Terns (Onychoprion fuscata) - S. James Reynolds; Graham R. Martin; Colin P. Wearn; B. John Hughes (Journal of Ornithology, 2009)

Isolation and Analysis of Bacteria with Antimicrobial Activities from the Marine Sponge Haliclona simulans Collected from Irish Waters - Jonathan Kennedy; Paul Baker; Clare Piper; Paul D. Cotter; Marcella Walsh; Marlies J. Mooij; Marie B. Bourke; Mary C. Rea; Paula M. O’Connor; R. Paul Ross; Colin Hill; Fergal O’Gara; et al. (Marine Biotechnology, 2009)

Strain-dependent viscoelastic behaviour and rupture force of single chondrocytes and chondrons under compression - Bac V. Nguyen; Qiguang Wang; Nicola J. Kuiper; Alicia J. El Haj; Colin R. Thomas; Zhibing Zhang (Biotechnology Letters, 2009)

An Investigation into the Rheology of Pharmaceutical Inter-granular Material Bridges at High Shear Rates - Barry Crean; Xinyong Chen; Simon R. Banks; Walter G. Cook; Colin D. Melia; Clive J. Roberts (Pharmaceutical Research, 2009)

Effects of salinity and nutrients on microbial assemblages in Louisiana wetland sediments - Colin R. Jackson; Scarlett C. Vallaire (Wetlands, 2009)

Reciprocal chromosome translocation associated with TDNA-insertion mutation in Arabidopsis: genetic and cytological analyses of consequences for gametophyte development and for construction of doubly mutant lines - Marc J. Curtis; Katia Belcram; Stephanie R. Bollmann; Colin M. Tominey; Peter D. Hoffman; Raphael Mercier; John B. Hays (Planta, 2009)

Basic features, conjunctive searches, and the confusion effect in predator–prey interactions - Colin R. Tosh; Jens Krause; Graeme D. Ruxton (Behavioral Ecology and Sociobiology, 2009)

Lemur Diversity in Madagascar - Russell A. Mittermeier; Jörg U. Ganzhorn; William R. Konstant; Kenneth Glander; Ian Tattersall; Colin P. Groves; Anthony B. Rylands; Andreas Hapke; Jonah Ratsimbazafy; Mireya I. Mayor; Edward E. Louis; Yves Rumpler; et al. (International Journal of Primatology, 2008)

Spatial Distribution and Long-term Movement Patterns of Cownose Rays Rhinoptera bonasus Within an Estuarine River - Angela B. Collins; Michelle R. Heupel; Colin A. Simpfendorfer (Estuaries and Coasts, 2008)

A review of cephalopod–environment interactions in European Seas - Graham J. Pierce; Vasilis D. Valavanis; Angel Guerra; Patricia Jereb; Lydia Orsi-Relini; Jose M. Bellido; Isidora Katara; Uwe Piatkowski; João Pereira; Eduardo Balguerias; Ignacio Sobrino; Eugenia Lefkaditou; et al. (Hydrobiologia, 2008)

Evaluation of seedling and adult plant resistance in European wheat cultivars to Australian isolates of Puccinia striiformis f. sp. tritici - Amin K. Pathan; Colin R. Wellings; Harbans S. Bariana; Robert F. Park (Euphytica, 2008)

Bone resorption increases tumour growth in a mouse model of osteosclerotic breast cancer metastasis - Yu Zheng; Hong Zhou; Colette Fong-Yee; James R. K. Modzelewski; Markus J. Seibel; Colin R. Dunstan (Clinical & Experimental Metastasis, 2008)

Support for the minimal essential MHC hypothesis: a parrot with a single, highly polymorphic MHC class II B gene - Colin R. Hughes; Shana Miles; Jaclyn M. Walbroehl (Immunogenetics, 2008)

Environments during the Kaihinu Interglacial and Otira Glaciation, coastal north Westland, New Zealand - Neville Moar; R. Patrick Suggate; Colin Burrows (New Zealand Journal of Botany, 2008)
Shoreline gravel of a 47 m raised beach 15 km north of Greymouth, north‐west South Island, is overlain by 6 m of lagoonal deposits, beginning with fine organic silts from which pollen records the replacement of an early podocarp‐hardwood forest by Nothofagus‐ podocarp and then by Nothofagus forest. Plant macro‐remains, including Dacrydium cupressinum (rimu), Nothofagus menziesii (silver beech), N. truncata (red beech), and N. solandri var. cliffortioides (mountain beech), clarify the nature of these forests. Radiocarbon dates >50 000 14 C yr BP and comparison with other north Westland sequences lead to correlation with the early Kaihinu (Last) Interglacial, and assignment to MIS5e and 5d. Locally overlying are 12 m of interbedded slope deposits and alluvial gravel, together with seven organic silt layers (Bed A down to Bed G). Leaves of Nothofagus menziesii were recovered from Bed G and N. solandri var. cliffortioides from higher layers. Bed B shows a significant Poaceae maximum. Radiocarbon dates from Beds G and E are 42700 ± 1300 and 22280 ± 150 14 C yr BP, respectively. The sequence represents much of the Otira (Last) Glaciation, MIS3 and MIS2. The persistence of trees and shrubs at this coastal site is consistent with the inference of closed canopy forest from a site near Westport, but contrasts with the dominance of Poaceae and Cyperaceae at previously studied inland Otira Glaciation sites.

Assessing CLPPs using MicroResp™ - Stephen J. Chapman; Colin D. Campbell; Rebekka R. E. Artz (Journal of Soils and Sediments, 2007)

In search of a functional flora—towards a greater integration of ecology and taxonomy - Colin A. Pendry; Jan Dick; Martin R. Pullan; Sabina G. Knees; Anthony G. Miller; Sophie Neale; Mark F. Watson (Plant Ecology, 2007)

Global survey of diversity among environmental saltwater Bacteriovoracaceae - Silvia A. Pineiro; O. Colin Stine; Ashvini Chauhan; Susan R. Steyert; Richard Smith; Henry N. Williams (Environmental Microbiology, 2007)
Summary Halophilic Bacteriovorax (Bx), formerly known as the marine Bdellovibrio , are Gram‐negative, predatory bacteria found in saltwater systems. To assess their genetic diversity and geographical occurrence, the small subunit rRNA (ssu‐rRNA) gene sequences were analysed from 111 marine, salt lake and estuarine isolates recovered from 27 locations around the world. Phylogenetic analysis of these isolates using Geobacter as the outgroup revealed eight distinct ribotype clusters each with at least two isolates. Each cluster was composed of isolates with ≥ 96.5% similarity in ssu‐rRNA sequences. Three single isolate outliers were observed. Many of the Bx ribotypes were widely dispersed among different types of ecosystems (e.g. cluster III was recovered from the Great Salt Lake, the Atlantic Ocean, Pacific Ocean, Chesapeake Bay and gills of aquarium fish). However, cluster V was only recovered from a single ecosystem, estuaries. Cluster V was originally detected in the Chesapeake Bay and subsequently in the Pamlico Sound/Neuse River system. Principal coordinate analysis revealed that the sequences of the isolates from different environments were distinct from each other. The results of this study reveal the saltwater Bx to be phylogenetically and environmentally more diverse than was previously known.

Comparison of morphological effects of PGE2 and TGFβ on osteoclastogenesis induced by RANKL in mouse bone marrow cell cultures - Colin R. Gardner (Cell and Tissue Research, 2007)

The expression and genetics of resistance to stripe (yellow) rust in three European and four New Zealand wheat cultivars - Amin K. Pathan; Robert F. Park; Colin R. Wellings; Harbans S. Bariana (Journal of Applied Genetics, 2007)

Projected Changes in Terrestrial Carbon Storage in Europe under Climate and Land-use Change, 1990–2100 - Sönke Zaehle; Alberte Bondeau; Timothy R. Carter; Wolfgang Cramer; Markus Erhard; I. Colin Prentice; I. Reginster; Mark D. A. Rounsevell; Stephen Sitch; Benjamin Smith; Pascalle C. Smith; Martin Sykes (Ecosystems, 2007)

Population Declines of Colobus in Western Uganda and Conservation Value of Forest Fragments - Colin A. Chapman; Lisa Naughton-Treves; Michael J. Lawes; Michael D. Wasserman; Thomas R. Gillespie (International Journal of Primatology, 2007)

Variation in diet and ranging of black and white colobus monkeys in Kibale National Park, Uganda - Tara R. Harris; Colin A. Chapman (Primates, 2007)

Nitrogen dynamics in grassland streams along a gradient of agricultural development - Kevin S. Simon; Dev K. Niyogi; Russell D. Frew; Colin R. Townsend (Limnology and Oceanography, 2007)
We examined nitrogen (N) uptake in seven grassland streams lying in catchments along a gradient (0–84%) of agricultural land use in New Zealand using a stable isotope ( 15 N) addition of NH 4 + to quantify whole‐stream uptake rates and uptake by specific compartments within the streams. Whole‐stream uptake of NH 4 + ranged from 1.2 mmol N m −2 min −1 to 7.9 mmol N m −2 min −1 and showed no evidence of strong saturation of uptake with increasing NH 4 + availability along the land use gradient. The relatively simple pattern of increasing N uptake along the gradient occurred despite substantial shifts in uptake among community members. Uptake of NH 4 + by epilithic biofilms followed a subsidy‐stress relationship, with highest uptake rates at intermediate levels of pastoral development and lowest uptake rates at high pastoral development. At high (>60%) pastoral development, reduced uptake by epilithon was compensated for by enhanced uptake by macrophytes. Compensatory uptake can play an important role in streams when community composition is reorganized by human activity.

Ambient UV, personal sun exposure and risk of multiple primary melanomas - Anne Kricker; Bruce K. Armstrong; Chris Goumas; Melisa Litchfield; Colin B. Begg; Amanda J. Hummer; Loraine D. Marrett; Beth Theis; Robert C. Millikan; Nancy Thomas; Hoda Anton Culver; Richard P. Gallagher; et al. (Cancer Causes & Control, 2007)

Longitudinal changes in biota along four New Zealand streams: Declines and improvements in stream health related to land use - Dev K. Niyogi; Mark Koren; Chris J. Arbuckle; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 2007)
We studied four streams in southern New Zealand in 2002 to document downstream changes in water quality, habitat, and stream biota in relation to land use. Two streams were in catchments that had increasing intensity of agricultural development downstream from relatively pristine headwaters. A third stream had the most intense land use in the headwaters and a riparian corridor of regenerating native forest along its middle reaches. A fourth stream had low intensity pasturing in its lower reaches, but also downstream increases in sedimentation from natural and historic mining sources. Four to six sites were sampled along each stream. Pastoral land cover in catchments was positively related to nutrient concentrations and fine sediment cover in the streams. At the most agricultural sites, dissolved inorganic nitrogen reached concentrations of 2 mg/litre, and fine sediment covered 33% of the stream bottom. Several biotic indices for invertebrates, including the Macroinvertebrate Community Index (MCI), were lower at the agricultural sites, which had MCI scores around 100. The indices were negatively related to fine sediment cover. The site with the intact riparian zone had declines in sedimentation downstream, which were paralleled by increases in invertebrate richness and biotic indices. Our findings support the notion that the restoration of riparian zones can improve stream habitat and invertebrate health.

Assessment of NeuroAIDS in the International Setting - Kevin R. Robertson; Colin D. Hall (Journal of Neuroimmune Pharmacology, 2007)

Stream Communities Along a Catchment Land-Use Gradient: Subsidy-Stress Responses to Pastoral Development - Dev K. Niyogi; Mark Koren; Chris J. Arbuckle; Colin R. Townsend (Environmental Management, 2007)

Association of functional catechol O-methyl transferase (COMT) Val108Met polymorphism with smoking severity and age of smoking initiation in Chinese male smokers - Song Guo; Da Fang Chen; Dong Feng Zhou; Hong Qiang Sun; Gui Ying Wu; Colin N. Haile; Therese A. Kosten; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2007)

Domestication potential and marketing of Canarium indicum nuts in the Pacific: 1. A literature review - Tio Nevenimo; John Moxon; John Wemin; Mark Johnston; Colin Bunt; R. R. B. Leakey (Agroforestry Systems, 2007)

DNA banking for plant breeding, biotechnology and biodiversity evaluation - Trevor R. Hodkinson; Stephen Waldren; John A. N. Parnell; Colin T. Kelleher; Karine Salamin; Nicolas Salamin (Journal of Plant Research, 2007)

Impact of human immunodeficiency virus (HIV) subtypes on HIV-associated neurological disease - Kevin J Liner; Colin D Hall; Kevin R Robertson (Journal of NeuroVirology, 2007)

Soil water dynamics in cropping systems containing Gliricidia sepium, pigeonpea and maize in southern Malawi - Paxie W. Chirwa; Chin K. Ong; Jumanne Maghembe; Colin R. Black (Agroforestry Systems, 2007)

The changing of the guard: Molecular diversity and rapid evolution of β-defensins - Colin A. Semple; Phillipe Gautier; Karen Taylor; Julia R. Dorin (Molecular Diversity, 2006)

Validated age and growth of the sandbar shark, Carcharhinus plumbeus (Nardo 1827) in the waters off Western Australia - Rory B. McAuley; Colin A. Simpfendorfer; Glenn A. Hyndes; Rick R. Allison; Justin A. Chidlow; Stephen J. Newman; Rod C. J. Lenanton (Environmental Biology of Fishes, 2006)

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)

Downscaling heavy precipitation over the United Kingdom: a comparison of dynamical and statistical methods and their future scenarios - Malcolm R. Haylock; Gavin C. Cawley; Colin Harpham; Rob L. Wilby; Clare M. Goodess (International Journal of Climatology, 2006)
Six statistical and two dynamical downscaling models were compared with regard to their ability to downscale seven seasonal indices of heavy precipitation for two station networks in northwest and southeast England. The skill among the eight downscaling models was high for those indices and seasons that had greater spatial coherence. Generally, winter showed the highest downscaling skill and summer the lowest. The rainfall indices that were indicative of rainfall occurrence were better modelled than those indicative of intensity. Models based on non‐linear artificial neural networks were found to be the best at modelling the inter‐annual variability of the indices; however, their strong negative biases implied a tendency to underestimate extremes. A novel approach used in one of the neural network models to output the rainfall probability and the gamma distribution scale and shape parameters for each day meant that resampling methods could be used to circumvent the underestimation of extremes. Six of the models were applied to the Hadley Centre global circulation model HadAM3P forced by emissions according to two SRES scenarios. This revealed that the inter‐model differences between the future changes in the downscaled precipitation indices were at least as large as the differences between the emission scenarios for a single model. This implies caution when interpreting the output from a single model or a single type of model (e.g. regional climate models) and the advantage of including as many different types of downscaling models, global models and emission scenarios as possible when developing climate‐change projections at the local scale. Copyright © 2006 Royal Meteorological Society

Identification of a complete methane monooxygenase operon from soil by combining stable isotope probing and metagenomic analysis - Marc G. Dumont; Stefan M. Radajewski; Carlos B. Miguez; Ian R. McDonald; J. Colin Murrell (Environmental Microbiology, 2006)
Summary Stable isotope probing (SIP) allows the isolation of nucleic acids from targeted metabolically active organisms in environmental samples. In previous studies, DNA‐SIP has been performed with the one‐carbon growth substrates methane and methanol to study methylotrophic organisms. The methylotrophs that incorporated the labelled substrate were identified with polymerase chain reaction and sequencing of 16S rRNA and ‘functional genes’ for methanotrophs ( mxaF , pmoA , mmoX ). In this study, a SIP experiment was performed using a forest soil sample incubated with 13 CH 4 , and the 13 C‐DNA was purified and cloned into a bacterial artificial chromosome (BAC) plasmid. A library of 2300 clones was generated and most of the clones contained inserts between 10 and 30 kb. The library was probed for key methylotrophy genes and a 15.2 kb clone containing a pmoCAB operon, encoding particulate methane monooxygenase, was identified and sequenced. Analysis of the pmoA sequence suggested that the clone was most similar to that of a Methylocystis sp. previously detected in this forest soil. Twelve other open reading frames were identified on the clone, including the gene encoding beta‐ribofuranosylaminobenzene 5′‐phosphate synthase, which is involved in the biosynthesis of the ‘archaeal’ C 1 ‐carrier, tetrahydromethanopterin, which is also found in methylotrophs. This study demonstrates that relatively large DNA fragments from uncultivated organisms can be readily isolated using DNA‐SIP, and cloned into a vector for metagenomic analysis.

Evolutionary Basis of Codon Usage and Nucleotide Composition Bias in Vertebrate DNA Viruses - Laura A. Shackelton; Colin R. Parrish; Edward C. Holmes (Journal of Molecular Evolution, 2006)

Residency and movement patterns of bonnethead sharks, Sphyrna tiburo, in a large Florida estuary - Michelle R. Heupel; Colin A. Simpfendorfer; Angela B. Collins; John P. Tyminski (Environmental Biology of Fishes, 2006)

Cocaine- and amphetamine-related transcript peptide and somatostatin in rat intracardiac ganglia - Robert J. Richardson; Ivica Grkovic; Colin R. Anderson (Cell and Tissue Research, 2006)

Nitrogen Dynamics in Cropping Systems in Southern Malawi Containing Gliricidia sepium, Pigeonpea and Maize - Paxie W. Chirwa; Colin R. Black; Chin K. Ong; Jumanne Maghembe (Agroforestry Systems, 2006)

Prediction of Parasite Infection Dynamics in Primate Metapopulations Based on Attributes of Forest Fragmentation - THOMAS R. GILLESPIE; COLIN A. CHAPMAN (Conservation Biology, 2006)
Although the effects of forest fragmentation on species and ecological processes have been the focus of considerable research in conservation biology, our capacity to predict how processes will be altered and which taxonomic or functional groups will be most affected by fragmentation is still poor. This problem is exacerbated by inherent temporal and spatial variability in fragment attributes. To improve our understanding of this interplay, we examined how various fragment attributes affect one potentially important ecological process, parasite infection dynamics, and considered how changes in this process affect host metapopulations. From August 1999 to July 2003 we surveyed red colobus ( Piliocolobus tephrosceles ) metapopulations inhabiting nine fragments (1.2 to 8.7 ha) in western Uganda to determine the prevalence and richness of strongyle and rhabditoid nematodes, a group of potentially pathogenic gastrointestinal parasites. We used noninvasive fecal flotation and sedimentation ( n = 536) to detect parasite eggs, cysts, and larvae in colobus fecal samples. To obtain an index of infection risk, we determined environmental contamination with Oesophagostomum sp., a representative strongyle nematode, in canopy ( n = 30) and ground vegetation plots ( n = 30). Concurrently, physical (i.e., size, location, and topography) and biological (i.e., tree diversity, tree density, stump density, and colobine density) attributes were quantified for each fragment. Interfragment comparisons of nine potential factors demonstrated that an index of degradation and human presence (tree stump density) strongly influenced the prevalence of parasitic nematodes. Infection risk was also higher in the fragment with the highest stump density than in the fragment with the lowest stump density. These results demonstrate that host‐parasite dynamics can be altered in complex ways by forest fragmentation and that intensity of extraction (e.g., stump density) best explains these changes.

Analysing the outer membrane subproteome of Methylococcus capsulatus (Bath) using proteomics and novel biocomputing tools - Frode S. Berven; Odd André Karlsen; Anne Hege Straume; Kristian Flikka; J. Colin Murrell; Anne Fjellbirkeland; Johan R. Lillehaug; Ingvar Eidhammer; Harald B. Jensen (Archives of Microbiology, 2006)

Expenditure freeze: the metabolic response of small mammals to cold environments - Murray M. Humphries; Stan Boutin; Donald W. Thomas; John D. Ryan; Colin Selman; Andrew G. McAdam; Dominique Berteaux; John R. Speakman (Ecology Letters, 2005)
There is renewed focus on the ecological determinants of animal metabolism and recent comparative analyses support the physiological expectation that the field metabolic rate (FMR) of homeotherms should increase with declining ambient temperature. However, sustained elevation of FMR during prolonged, seasonal cold could be prevented by intrinsic limits constraining FMR to some multiple of basal metabolic rate (BMR) or extrinsic limits on resource abundance. We analysed previous measures of mammalian FMR and BMR to establish the effect of ambient temperature on both traits and found no support for intrinsic limitation. We also measured the FMR of a northern population of red squirrels ( Tamiasciurus hudsonicus ) exposed to ambient temperatures much colder than all but one previous study of mammal FMR. These measurements revealed levels of energy expenditure that are, unexpectedly, among the lowest ever recorded in homeotherms and that actually decrease as it gets colder. Collectively, these results suggest the metabolic niche space of cold climate endotherms may be much larger than previously recognized.

Chloroplast and microsatellite DNA diversities reveal the introduction history of Brazilian peppertree ( Schinus terebinthifolius ) in Florida - DEAN A. WILLIAMS; WILLIAM A. OVERHOLT; JAMES P. CUDA; COLIN R. HUGHES (Molecular Ecology, 2005)
Brazilian peppertree ( Schinus terebinthifolius ) is a woody perennial that has invaded much of Florida. This native of northeastern Argentina, Paraguay, and Brazil was brought as an ornamental to both the west and east coasts of Florida at the end of the 19th century. It was recorded as an invader of natural areas in the 1950s, and has since extended its range to cover over 280 000 ha. Our goals were to understand the history of this invasion, as one step toward understanding why this exotic was so successful, and ultimately to improve development of biological control agents. We sampled plants from the native and exotic ranges, particularly Florida, and genotyped these individuals at nuclear and chloroplast loci. Nuclear microsatellite and cpDNA loci reveal strong genetic population structure consistent with limited dispersal in the introduced and native ranges. Bayesian clustering of microsatellite data separates the east and west coast plants in Florida into distinct populations. The two chloroplast haplotypes found in Florida are also concordant with this separation: one predominates on the east coast, the other on the west coast. Analysis of samples collected in South America shows that haplotypes as distinct as the two in Florida are unlikely to have come from a single source population. We conclude that the genetic evidence supports two introductions of Brazilian peppertree into Florida and extensive hybridization between them. The west coast genotype likely came from coastal Brazil at about 27° south, whereas the east coast genotype probably originated from another, as yet unidentified site. As a result of hybridization, the Florida population does not exhibit low genetic variation compared to populations in the native range, possibly increasing its ability to adapt to novel environments. Hybridization also has important consequences for the selection of biocontrol agents since it will not be possible to identify closely co‐adapted natural enemies in the native range, necessitating more extensive host testing.

Locus heterogeneity in autosomal recessive congenital cataracts: linkage to 9q and germline HSF4 mutations - Tim Forshew; Colin A. Johnson; Shagufta Khaliq; Shanaz Pasha; Catherine Willis; Rashida Abbasi; Louise Tee; Ursula Smith; Richard C. Trembath; Syed Qasim Mehdi; Anthony T. Moore; Eamonn R. Maher (Human Genetics, 2005)

Misidentification of cardiac vagal pre-ganglionic neurons after injections of retrograde tracer into the pericardial space in the rat - Ivica Grkovic; Kate Fernandez; Robin M. McAllen; Colin R. Anderson (Cell and Tissue Research, 2005)

Effects of small ponds on stream water quality and macroinvertebrate communities - John R. Maxted; Colin H. McCready; Mike R. Scarsbrook (New Zealand Journal of Marine and Freshwater Research, 2005)
Six small constructed ponds (surface area 500–7500 m 2 , catchment area 28–158 ha) in rural and native forest catchments in the Auckland region had poorer water quality than the streams they replaced. Temperature (24°C) and dissolved oxygen (DO) (4 mg/litre) criteria were exceeded for up to 46% and 84% of days, respectively, during a critical 40‐day summer period. The poor conditions found in ponds, even within undeveloped native forest catchments, indicated that the physical characteristics of ponds (e.g., lack of shade, organic sediments) affected water quality independently of other factors (e.g., land use, riparian protection). The frequency and severity of the exceedences were related to pond size, retention time, and catchment land use; the most degraded conditions were found in rural ponds with largest surface areas and longest retention times. Ponds affected water quality and macroinvertebrate communities downstream. Exceedences of temperature and DO criteria occurred more frequently and were more severe downstream than upstream of ponds. Ponds in rural catchments increased mean daily stream temperatures 3.1–6.6°C during the critical summer period, and temperature differences were three times higher than those in bush catchments (0.8–2.0°C). Elevated temperatures were observed for hundreds of metres downstream owing to the slow rate of cooling (1°C/ 100 m), expanding the extent of adverse effects well beyond the “footprint” of the pond. Macroinvertebrate community composition (sample area 1–3 m 2 ) and values of four commonly used metrics appeared to be significantly affected by ponds in rural and native forest catchments. These finding have important management implications that should lead to modifications (e.g., breaching dams) of the estimated 4500 existing ponds in the Auckland region, where possible, and restrictions on proposals for new “on‐line” ponds.

Use of DNA‐stable isotope probing and functional gene probes to investigate the diversity of methyl chloride‐utilizing bacteria in soil - Elena Borodina; Michael J. Cox; Ian R. McDonald; J. Colin Murrell (Environmental Microbiology, 2005)
Summary Enrichment and isolation of methyl chloride‐utilizing bacteria from various terrestrial environments, including woodland and forest soils, resulted in the identification of seven methyl chloride‐utilizing strains belonging to the genus Hyphomicrobium , an Aminobacter strain TW23 and strain WG1, which grouped closely with the genus Mesorhizobium . Methyl chloride enrichment cultures were dominated by Hyphomicrobium species, indicating that these bacteria were most suited to growth under the enrichment and isolation conditions used. However, the application of culture‐independent techniques such as DNA‐stable isotope probing and the use of a functional gene probe targeting cmuA , which encodes the methyltransferase catalysing the first step in bacterial methyl chloride metabolism, indicated a greater diversity of methyl chloride‐utilizing bacteria in the terrestrial environment, compared with the diversity of soil isolates obtained via the enrichment and isolation procedure. It also revealed the presence of as yet uncultured and potentially novel methyl chloride‐degrading bacteria in soil.

Evidence for the presence of a CmuA methyltransferase pathway in novel marine methyl halide‐oxidizing bacteria - Hendrik Schäfer; Ian R. McDonald; Phil D. Nightingale; J. Colin Murrell (Environmental Microbiology, 2005)
Summary Marine bacteria that oxidized methyl bromide and methyl chloride were enriched and isolated from seawater samples. Six methyl halide‐oxidizing enrichments were established from which 13 isolates that grew on methyl bromide and methyl chloride as sole sources of carbon and energy were isolated and maintained. All isolates belonged to three different clades in the Roseobacter group of the alpha subdivision of the Proteobacteria and were distinct from Leisingera methylohalidivorans , the only other identified marine bacterium that grows on methyl bromide as sole source of carbon and energy. Genes encoding the methyltransferase/corrinoid‐binding protein CmuA, which is responsible for the initial step of methyl chloride oxidation in terrestrial methyl halide‐oxidizing bacteria, were detected in enrichments and some of the novel marine strains. Gene clusters containing cmuA and other genes implicated in the metabolism of methyl halides were cloned from two of the isolates. Expression of CmuA during growth on methyl halides was demonstrated by analysis of polypeptides expressed during growth on methyl halides by SDS‐PAGE and mass spectrometry in two isolates representing two of the three clades. These findings indicate that certain marine methyl halide degrading bacteria from the Roseobacter group contain a methyltransferase pathway for oxidation of methyl bromide that may be similar to that responsible for methyl chloride oxidation in Methylobacterium chloromethanicum . This pathway therefore potentially contributes to cycling of methyl halides in both terrestrial and marine environments.

Bacterial diversity in the bacterioneuston (sea surface microlayer): the bacterioneuston through the looking glass - Mark P. Franklin; Ian R. McDonald; David G. Bourne; Nicholas J. P. Owens; Robert C. Upstill‐Goddard; J. Colin Murrell (Environmental Microbiology, 2005)
Summary The bacterioneuston is defined as the community of bacteria present within the neuston or sea surface microlayer. Bacteria within this layer were sampled using a membrane filter technique and bacterial diversity was compared with that in the underlying pelagic coastal seawater using molecular ecological techniques. 16S rRNA gene libraries of ≈ 500 clones were constructed from both bacterioneuston and the pelagic water samples and representative clones from each library were sequenced for comparison of bacterial diversity. The bacterioneuston was found to have a significantly lower bacterial diversity than the pelagic seawater, with only nine clone types (ecotaxa) as opposed to 46 ecotaxa in the pelagic seawater library. Surprisingly, the bacterioneuston clone library was dominated by 16S rRNA gene sequences affiliated to two groups of organisms, Vibrio spp. which accounted for over 68% of clones and Pseudoalteromonas spp. accounting for 21% of the library. The dominance of these two 16S rRNA gene sequence types within the bacterioneuston clone library was confirmed in a subsequent gene probing experiment. 16S rRNA gene probes specific for these groups of bacteria were designed and used to probe new libraries of 1000 clones from both the bacterioneuston and pelagic seawater DNA samples. This revealed that 57% of clones from the bacterioneuston library hybridized to a Vibrio sp.‐specific 16S rRNA gene probe and 32% hybridized to a Pseudoalteromonas sp.‐specific 16S rRNA gene probe. In contrast, the pelagic seawater library resulted in only 13% and 8% of 16S rRNA gene clones hybridizing to the Vibrio sp. and Pseudoalteromonas sp. probes respectively. Results from this study suggest that the bacterioneuston contains a distinct population of bacteria and warrants further detailed study at the molecular level.

A Novel, Lipid-Free Nanodispersion Formulation of Propofol and Its Characterization - Hongming Chen; Zhong Zhang; rn Almarsson; Jean-Francois Marier; Dina Berkovitz; Colin R. Gardner (Pharmaceutical Research, 2005)

Enhancement of antimicrobial effects by glucocorticoids - Jochen Trck; Claudia Oberdrfer; Tanja Vogel; Colin R. MacKenzie; Walter Dubener (Medical Microbiology and Immunology, 2005)

Cerebrospinal fluid from human immunodeficiency virus–infected individuals facilitates neurotoxicity by suppressing intracellular calcium recovery - Rick B Meeker; Jeramiah C Boles; Kevin R Robertson; Colin D Hall (Journal of NeuroVirology, 2005)

Injection experiments and thermal recovery in corehole OH-1, Lake City, California - Jason R. McKenna; Walter R. Benoit; Colin B. Goranson; David D. Blackwell (Natural Resources Research, 2004)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Impacts of riparian afforestation on stream biofilms: An exotic forest‐native grassland comparison - Ross M. Thompson; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 2004)
The nature of benthic biofilm was assessed in four streams in New Zealand, two flowing through native tussock grassland and two through exotic Pinus radiata forest. Components of the biofilm were described using epi‐fluorescent staining (DAPI) and scanning electron microscopy (SEM) of rock and wood substrata. DAPI and SEM analyses showed significantly more bacteria and fungi on rock and wood in tussock as opposed to pine streams. This emphasises the importance of the heterotrophic community even in systems which have abundant light available for primary production. The lack of a significant heterotrophic biofilm in pine streams was unexpected, and we speculate that chemical characteristics of the water may be responsible.

Familial aggregation of melanoma risks in a large population-based sample of melanoma cases - Colin B. Begg; Amanda Hummer; Urvi Mujumdar; Bruce K. Armstrong; Anne Kricker; Loraine D. Marrett; Robert C. Millikan; Stephen B. Gruber; Hoda Anton-Culver; Judith B. Klotz; Roberto Zanetti; Richard P. Gallagher; et al. (Cancer Causes & Control, 2004)

Familial aggregation of melanoma risks in a large population-based sample of melanoma cases - Colin B. Begg; Amanda Hummer; Urvi Mujumdar; Bruce K. Armstrong; Anne Kricker; Loraine D. Marrett; Robert C. Millikan; Stephen B. Gruber; Hoda Anton-Culver; Judith B. Klotz; Roberto Zanetti; Richard P. Gallagher; et al. (Cancer Causes & Control, 2004)

Biomonitoring of Element Deposition Using Mosses in the 2000 French Survey: Identifying Sources and Spatial Trends - S. Gombert; C. Rausch De Traubenberg; R. Losno; S. Leblond; J. L. Colin; D. Cossa (Journal of Atmospheric Chemistry, 2004)

Estimation of Shark Home Ranges using Passive Monitoring Techniques - Michelle R. Heupel; Colin A. Simpfendorfer; Robert E. Hueter (Environmental Biology of Fishes, 2004)

Molecular diversity of methanotrophs in Transbaikal soda lake sediments and identification of potentially active populations by stable isotope probing - Ju‐Ling Lin; Stefan Radajewski; Bulat T. Eshinimaev; Yuri A. Trotsenko; Ian R. McDonald; J Colin Murrell (Environmental Microbiology, 2004)
Summary Soda lakes are an environment with an unusually high pH and often high salinity. To identify the active methanotrophs in the Soda lake sediments, sediment slurries were incubated with a 10% (v/v) 13 CH 4 headspace and the 13 C‐labelled DNA was subsequently extracted from these sediments following CsCl density gradient centrifugation. This DNA was then used as a template for PCR amplification of 16S rRNA genes and genes encoding PmoA and MmoX of methane monooxygenase, key enzymes in the methane oxidation pathway. Phylogenetic analysis of 16S rRNA genes, PmoA and MmoX identified that strains of Methylomicrobium , Methylobacter , Methylomonas and ‘Methylothermus’ had assimilated the 13 CH 4 . Phylogenetic analysis of PmoA sequences amplified from DNA extracted from Soda lake sediments before Stable Isotope Probing (SIP) treatment showed that a much wider diversity of both type I and type II methanotroph sequences are present in this alkaline environment. The majority of methanotroph sequences detected in the 13 C‐DNA studies were from type I methanotrophs, with 50% of 16S rRNA clones and 100% of pmoA clones from both Lake Suduntuiskii Torom and Lake Gorbunka suggesting that the type I methanotrophs are probably responsible for the majority of methane oxidation in this environment.

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.

Pre-eruptive magma mixing in ash-flow deposits of the Tertiary Rum Igneous Centre, Scotland - Valentin R. Troll; Colin H. Donaldson; C. Henry. Emeleus (Contributions to Mineralogy and Petrology, 2004)

Iron inhibits neurotoxicity induced by trace copper and biological reductants - Anthony R. White; Kevin J. Barnham; Xudong Huang; Irene Voltakis; Konrad Beyreuther; Colin L. Masters; Robert A. Cherny; Ashley I. Bush; Roberto Cappai (JBIC Journal of Biological Inorganic Chemistry, 2004)

Changes in fulvic acid redox state through the oxycline of a permanently ice-covered Antarctic lake - Jennifer R. Fulton; Diane M. McKnight; Rose M. Cory; Colin Stedmon; Elisabeth Blunt; Christine M. Foreman (Aquatic Sciences, 2004)

Analysis of methanotrophic bacteria in Movile Cave by stable isotope probing - Elena Hutchens; Stefan Radajewski; Marc G. Dumont; Ian R. McDonald; J. Colin Murrell (Environmental Microbiology, 2004)
Summary Movile Cave is an unusual groundwater ecosystem that is supported by in situ chemoautotrophic production. The cave atmosphere contains 1–2% methane (CH 4 ), although much higher concentrations are found in gas bubbles that keep microbial mats afloat on the water surface. As previous analyses of stable carbon isotope ratios have suggested that methane oxidation occurs in this environment, we hypothesized that aerobic methane‐oxidizing bacteria (methanotrophs) are active in Movile Cave. To identify the active methanotrophs in the water and mat material from Movile Cave, a microcosm was incubated with a 10% 13 CH 4 headspace in a DNA‐based stable isotope probing (DNA‐SIP) experiment. Using improved centrifugation conditions, a 13 C‐labelled DNA fraction was collected and used as a template for polymerase chain reaction amplification. Analysis of genes encoding the small‐subunit rRNA and key enzymes in the methane oxidation pathway of methanotrophs identified that strains of Methylomonas , Methylococcus and Methylocystis/Methylosinus had assimilated the 13 CH 4 , and that these methanotrophs contain genes encoding both known types of methane monooxygenase (MMO). Sequences of non‐methanotrophic bacteria and an alga provided evidence for turnover of CH 4 due to possible cross‐feeding on 13 C‐labelled metabolites or biomass. Our results suggest that aerobic methanotrophs actively convert CH 4 into complex organic compounds in Movile Cave and thus help to sustain a diverse community of microorganisms in this closed ecosystem.

Assessment of the Diversity of African Primates - Peter Grubb; Thomas M. Butynski; John F. Oates; Simon K. Bearder; Todd R. Disotell; Colin P. Groves; Thomas T. Struhsaker (International Journal of Primatology, 2003)

Relationship between Droplet pH and Aerosol Dissolution Kinetics: Effect of Incorporated Aerosol Particles on Droplet pH during Cloud Processing - K. V. Desboeufs; R. Losno; J.L. Colin (Journal of Atmospheric Chemistry, 2003)

Habitat scale and biodiversity: influence of catchment, stream reach and bedform scales on local invertebrate diversity - Sebastien Brosse; Chris J. Arbuckle; Colin R. Townsend (Biodiversity and Conservation, 2003)

Mineral Resource Availability and Consumption by Colobus in Kibale National Park, Uganda - Karyn D. Rode; Colin A. Chapman; Lauren J. Chapman; Lee R. McDowell (International Journal of Primatology, 2003)

Headwater stream response to grassland agricultural development in New Zealand - Ralph H. Riley; Colin R. Townsend; Dev K. Niyogi; Chris A. Arbuckle; Kathi A. Peacock (New Zealand Journal of Marine and Freshwater Research, 2003)
Agricultural development of native grasslands may change stream physico‐chemistry in ways that provide both subsidies and stresses to the system. The aims of this study were to determine: (1) which physico‐chemical parameters respond most strongly to agricultural development; (2) how biodiversity, community composition, and food‐web structure responded to these changes; and (3) to determine the balance between negative and positive impacts of these subsidies and stresses based on the analysis of 18 headwater streams. Developed pasture streams had increased nutrient loading, alterations to streamside vegetation, increased fine sediment composition, and lower moss coverage of stream‐beds than undeveloped or lightly grazed native grassland catchments (which could not be distinguished from one another). These differences were associated with higher numbers of macroinvertebrate taxa and higher numbers of macroinvertebrates indicating that the net effects of these subsidies and stresses associated with agricultural development were positive within these headwater stream reaches.

Variation in the Nutritional Value of Primate Foods: Among Trees, Time Periods, and Areas - Colin A. Chapman; Lauren J. Chapman; Karyn D. Rode; Erin M. Hauck; Lee R. McDowell (International Journal of Primatology, 2003)

Low and homogeneous copy number of plasmid‐borne symbiont genes affecting host nutrition in Buchnera aphidicola of the aphid Uroleucon ambrosiae - Gordon R. Plague; Colin Dale; Nancy A. Moran (Molecular Ecology, 2003)
The bacterial endosymbiont of aphids, Buchnera aphidicola , often provides amino acids to its hosts. Plasmid amplification of leucine ( leuABCD ) and tryptophan ( trpEG ) biosynthesis genes may be a mechanism by which some Buchnera over‐produce these nutrients. We used quantitative polymerase chain reaction to assess the leuABCD / trpEG copy variability within Uroleucon ambrosiae , an aphid with a wide diet breadth and range. Both leuABCD and trpEG abundances are: (i) similar for aphids across 15 populations, and (ii) low compared to Buchnera from other aphid species (particularly trpEG ). Consequently, the plasmid location of trpEG combined with Buchnera 's chromosomal polyploidy may functionally limit, rather than increase, tryptophan production within Uroleucon ambrosiae .

Modulation of IP3-sensitive Ca2+ release by 2,3-butanedione monoxime - Matthew R. Turvey; Alex J. Laude; E. Oliver H. Ives; William H. Seager; Colin W. Taylor; Peter Thorn (Pflügers Archiv - European Journal of Physiology, 2003)

Individual, Population, Community, and Ecosystem Consequences of a Fish Invader in New Zealand Streams - Colin R. Townsend (Conservation Biology, 2003)
Knowledge of the population biology of invading species will often be necessary to develop effective management procedures and policies. But because invaders can have unexpected indirect effects in food webs, invasion ecologists need to integrate processes at the population level and other ecological levels. I describe a series of coordinated studies in New Zealand streams that address the effect of an exotic fish on individual behavior, population, community, and ecosystem patterns. Such case studies are important as an aid to the formulation of policy about invasions that are especially likely to become problematic. At the individual level, grazing invertebrates showed changes in behavior as a result of the introduction of brown trout ( Salmo trutta ), a predator that exerts a very different selection pressure than do native fish. At the population level, trout have replaced nonmigratory galaxiid fish in some streams but not others, and have affected the distributions of crayfish and other large invertebrates. At the community level, trout have suppressed grazing pressure from invertebrates and are thus responsible for enhancing algal biomass and changing algal species composition. Finally, at the ecosystem level, essentially all annual production of invertebrates is consumed by trout ( but not by galaxiids), and algal primary productivity is six times higher in a trout stream. This leads, in turn, to an increased flux of nutrients from the water to the benthic community. The trout invasion has led to strong top‐down control of community structure and ecosystem functioning via its effects on individual behavior and population distribution and abundance. Particular physiological, behavioral, and demographic traits of invaders can lead to profound ecosystem consequences that managers need to take into account.

Effects of alcohol consumption on the risk of colorectal cancer among men by anatomical subsite (Canada) - Colin R. Sharpe; Jack Siemiatycki; Bernard Rachet (Cancer Causes & Control, 2002)

Transformation of arachidonic acid to 19-hydroxy- and 20-hydroxy-eicosatetraenoic acids using Candida bombicola - Asmita Prabhune; Simon R. Fox; Colin Ratledge (Biotechnology Letters, 2002)

Inoculation of Chicks with Viable Non-Colonizing Strains of Campylobacter jejuni: Evaluation of Protection Against a Colonizing Strain - Richard L. Ziprin; Michael E. Hume; Colin R. Young; Roger B. Harvey (Current Microbiology, 2002)

Diet of the crayfish Paranephrops zealandicus in bush and pasture streams: Insights from stable isotopes and stomach analysis - John W. Hollows; Colin R. Townsend; Kevin J. Collier (New Zealand Journal of Marine and Freshwater Research, 2002)
Crayfish ( Paranephrops zealandicus White) stomachs from streams in both native bush (mainly tree leaves and dicotyledonous seeds) and exotic pasture settings (mainly grass stems and monocotyledonous seeds) were dominated by allochthonous material. More detritus occurred in stomachs in autumn‐winter than in spring‐summer, but quantities were similar in crayfish from native bush and pasture streams. The stomachs of larger crayfish contained a significantly greater proportion of detritus than smaller individuals. Aquatic invertebrates were the second most abundant dietary category by volume, with highest values in winter, but there were no significant differences between land uses or crayfish size classes. A wide range of invertebrates was eaten by crayfish, with mayfly nymphs, chironomid larvae, and snails predominating. The latter were numerically more prominent in crayfish from bush than pasture streams. Terrestrial invertebrates were recorded from 4% of stomachs, but there were no significant differences in relation to land use, season, or crayfish size class. Despite aquatic invertebrates making up 13 C and perhaps of microfloral origin, seems to be an important energy source for crayfish in both stream types.

Galectins in kidney development - R. Colin Hughes (Glycoconjugate Journal, 2002)

Cadmium Toxicity for Terrestrial Invertebrates: Taking Soil Parameters Affecting Bioavailability Into Account - Koen Lock; Colin R. Janssen (Ecotoxicology, 2001)

Genetic, physical, and phenotypic characterization of the Del(13)Svea36H mouse - Ruth M. Arkell; Matthew Cadman; Tracy Marsland; Anne Southwell; Caroline Thaung; Jennifer R. Davies; Toni Clay; Colin V. Beechey; Edward P. Evans; Mark A. Strivens; Steve D.M. Brown; Paul Denny (Mammalian Genome, 2001)

Compound heterozygosity and nonsense mutations in the α1-subunit of the inhibitory glycine receptor in hyperekplexia - Mark I. Rees; Trevor M. Lewis; Behnaz Vafa; Colin Ferrie; Peter Corry; Fransesco Muntoni; Heinz Jungbluth; John B. Stephenson; Mike Kerr; Russell G. Snell; Peter R. Schofield; Michael J. Owen (Human Genetics, 2001)

Case–control study of alcohol consumption and prostate cancer risk in Montréal, Canada - Colin R. Sharpe; Jack Siemiatycki (Cancer Causes & Control, 2001)

Molecular analysis of microbial community structure in an arsenite‐oxidizing acidic thermal spring - Colin R. Jackson; Heiko W. Langner; Jessica Donahoe‐Christiansen; William P. Inskeep; Timothy R. McDermott (Environmental Microbiology, 2001)
Electron microscopy (EM), denaturing gradient gel electrophoresis (DGGE) and 16S rDNA sequencing were used to examine the structure and diversity of microbial mats present in an acid‐sulphate–chloride (pH 3.1) thermal (58–62°C) spring in Norris Basin, Yellowstone National Park, WY, USA, exhibiting rapid rates of arsenite oxidation. Initial visual assessments, scanning EM and geochemical measurements revealed the presence of three distinct mat types. Analysis of 16S rDNA fragments with DGGE confirmed the presence of different bacterial and archaeal communities within these zones. Changes in the microbial community appeared to coincide with arsenite oxidation activity. Phylogenetic analysis of 1400 bp 16S rDNA sequences revealed that clone libraries prepared from both arsenic redox active and inactive bacterial communities were dominated by sequences phylogenetically related to Hydrogenobacter acidophilus and Desulphurella sp. The appearance of archaeal 16S rDNA sequences coincided with the start of arsenite oxidation, and sequences were obtained showing affiliation with both Crenarchaeota and Euryarchaeota . The majority of archaeal sequences were most similar to sequences obtained from marine hydrothermal vents and other acidic hot springs, although the level of similarity was typically just 90%. Arsenite oxidation in this system may result from the activities of these unknown archaeal taxa and/or the previously unreported arsenic redox activity of H. acidophilus ‐ or Desulphurella ‐like organisms. If the latter, arsenite oxidation must be inhibited in the initial high‐sulphide zone of the spring, where no change in the distribution of arsenite versus arsenate was observed.

Test Designs to Assess the Influence of Soil Characteristics on the Toxicity of Copper and Lead to the Oligochaete Enchytraeus albidus - Koen Lock; Colin R. Janssen (Ecotoxicology, 2001)

The detergent octylglucoside neutralizes lipopolysaccharide in a specific manner - Birgit Henrich; Raquel Guadarrama; Ulrich Zähringer; Colin R. MacKenzie (Medical Microbiology and Immunology, 2001)

Linkage of prostate cancer susceptibility loci to chromosome 1 - Jianfeng Xu; Siqun L. Zheng; Bao-li Chang; Jeffrey R. Smith; John D. Carpten; O. Colin Stine; Sarah D. Isaacs; Kathy E. Wiley; Lauren Henning; Charles Ewing; Piroska Bujnovszky; Eugene R. Bleeker; et al. (Human Genetics, 2001)

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

The measurement and modelling of the carbon dioxide exchange at a high Arctic site in Svalbard - Colin R. Lloyd (Global Change Biology, 2001)

Genomic Comparison of an Avirulent Strain of Orf Virus with that of a Virulent Wild Type Isolate Reveals that the Orf Virus G2L Gene is Non-Essential for Replication - Colin J. McInnes; Ann R. Wood; Peter F. Nettleton; Janice A. Gilray (Virus Genes, 2001)

Abundance, diversity, and structure of freshwater invertebrates and fish communities: An artificial neural network approach - Sebastien Brosse; Sovan Lek; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 2001)
Artificial neural networks (ANN) are models inspired by the structure and processes of biological cognition and learning. To illustrate the ecological applications of ANN, we present analyses of two complementary examples. ANN is first used to predict the diversity of macroinvertebrates, at the macrohabitat scale, in tributaries of a large river in New Zealand and, second, to predict the distribution and abundance of several fish species at the microhabitat scale in a French lake. The predictive abilities of the models were high, with correlation coefficients between observed and estimated values from 0.61 and 0.92. Moreover, the environmental variables found to be associated with invertebrate diversity and fish abundance were in accord with results of previous studies. The combination of ANN with a multivariate analysis offish community composition provided both for accurate prediction of fish assemblages and effective visualisation of their relationships with environmental variables. On the basis of these studies in different locations (New Zealand streams, French lake), involving various population and community attributes, we conclude that ANN is an appropriate tool for both prediction and explanation of ecological relationships at various spatial scales (microhabitat and macrohabitat), and for a range of aquatic ecosystems (lakes and rivers), organisms (invertebrates and fish), and ecological descriptors (abundance, Shannon diversity index, and community composition).

Smcy transgene does not rescue spermatogenesis in sex-reversed mice - Alexander I. Agulnik; Wilbur R. Harrison; Colin E. Bishop (Mammalian Genome, 2001)

Caldera formation in the Rum Central Igneous Complex, Scotland - Valentin R. Troll; C. Henry Emeleus; Colin H. Donaldson (Bulletin of Volcanology, 2000)

Polymorphic microsatellite loci of Oryzomys palustris , the marsh rice rat, in South Florida detected by silver staining - Yunqiu Wang; Colin R. Hughes; Edwin A. Gines‐Candelaria; Michael S. Gaines (Molecular Ecology, 2000)

Distribution of the New Zealand crayfish Paranephrops zealandicus in relation to stream physico‐chemistry, predatory fish, and invertebrate prey - Nisikawa Usio; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 2000)
Summer distributions of the crayfish Paranephrops zealandicus White, and of potential predators and prey, were investigated in 30 pools along a stream in Otago, New Zealand. Environmental variables were regarded as independent and invertebrates as dependent variables for young‐of‐the‐year (YOY) and adult crayfish. YOY and adults were negatively associated with trout presence and suspended solid concentrations, and positively with wood cover. Adults were further negatively associated with current velocity and positively with depth, leaf cover, and percentage sand. In contrast, YOY were positively associated with coarse substrates. The results are consistent with hypotheses that crayfish are vulnerable to sedimentation and trout predation. Furthermore, coarse substrate and cover may be important because they provide shelter from predation and cannibalism. Deep habitat, however, may act as a refuge from terrestrial predators and/or provide detritus storage for adult crayfish. Densities of adults were negatively associated with those of Megaleptoperla , Tanypodinae, and Scirtidae, but positively with Chironominae. The negative relationships are probably consequences of bioturbation and predation by crayfish. However, the positive relationship with Chironominae indicates that any pre‐dation/bioturbation effect may be outweighed by crayfish shredding leaves and enhancing food supply for these collector invertebrates. The effects of crayfish may propagate into lower trophic levels both directly and indirectly.

So what do your sugars do? - R Colin Hughes (Glycoconjugate Journal, 2000)

Salicylic acid is not a bacterial siderophore: a theoretical study - John R. Chipperfield; Colin Ratledge (BioMetals, 2000)

Molecular biology and regulation of methane monooxygenase - J. Colin Murrell; Bettina Gilbert; Ian R. McDonald (Archives of Microbiology, 2000)

Molecular analysis of an outer membrane protein, MopB, of Methylococcus capsulatus (Bath) and structural comparisons with proteins of the OmpA family - Anne Fjellbirkeland; Vahid Bemanian; Ian R. McDonald; J. Colin Murrell; Harald B. Jensen (Archives of Microbiology, 2000)

Characterization of microsatellite loci developed for the wattled curassow, Crax globulosa - Colin R. Hughes; Erik D. Larson (Molecular Ecology, 2000)

Assessment of the metabolic activity of Acremonium chrysogenum using Acridine Orange - Erzsébet Sándor; Levente Karaffa; Gopal C. Paul; István Pócsi; Colin R. Thomas; Attila Szentirmai (Biotechnology Letters, 2000)

Oxygenation and perfusion of rabbit tibialis anterior muscle subjected to different patterns of electrical stimulation - Adam R. Greenbaum; Jonathan C. Jarvis; Daniel O'Hare; Sanjiv Manek; Colin J. Green; John R. Pepper; C. Peter Winlove; Stanley Salmons (Journal of Muscle Research and Cell Motility, 2000)

Neotropical seasonally dry forests and Quaternary vegetation changes - R. Toby Pennington; Darién E. Prado; Colin A. Pendry (Journal of Biogeography, 2000)
Seasonally dry tropical forests have been largely ignored in discussions of vegetation changes during the Quaternary. We distinguish dry forests, which are essentially tree‐dominated ecosystems, from open savannas that have a xeromorphic fire‐tolerant, grass layer and grow on dystrophic, acid soils. Seasonally dry tropical forests grow on fertile soils, usually have a closed canopy, have woody floras dominated by the Leguminosae and Bignoniaceae and a sparse ground flora with few grasses. They occur in disjunct areas throughout the Neotropics. The Chaco forests of central South America experience regular annual frosts, and are considered a subtropical extension of temperate vegetation formations. At least 104 plant species from a wide range of families are each found in two or more of the isolated areas of seasonally dry tropical forest scattered across the Neotropics, and these repeated patterns of distribution suggest a more widespread expanse of this vegetation, presumably in drier and cooler periods of the Pleistocene. We propose a new vegetation model for some areas of the Ice‐Age Amazon: a type of seasonally dry tropical forest, with rain forest and montane taxa largely confined to gallery forest. This model is consistent with the distributions of contemporary seasonally dry tropical forest species in Amazonia and existing palynological data. The hypothesis of vicariance of a wider historical area of seasonally dry tropical forests could be tested using a cladistic biogeographic approach focusing on plant genera that have species showing high levels of endemicity in the different areas of these forests.

Long‐Term Effects of Logging on African Primate Communities: a 28‐Year Comparison From Kibale National Park, Uganda - Colin A. Chapman; Sophia R. Balcomb; Thomas R. Gillespie; Joseph P. Skorupa; Thomas T. Struhsaker (Conservation Biology, 2000)
If logging is to be compatible with primate conservation, primate populations must be expected to recover from the disturbance and eventually return to their former densities. Surveys conducted over 28 years were used to quantify the long‐term effects of both low‐ and high‐intensity selective logging on the density of the five common primates in Kibale National Park, Uganda. The most dramatic exception to the expectation that primate populations will recover following logging was that group densities of Cercopithecus mitis and C. ascanius in the heavily logged area continued to decline decades after logging. Procolobus tephrosceles populations were recovering in the heavily logged areas, but the rate of increase appeared to be slow (0.005 groups/km 2 per year). Colobus guereza appeared to do well in some disturbed habitats and were found at higher group densities in the logged areas than in the unlogged area. There was no evidence of an increase in Lophocebus albigena group density in the heavily logged area since the time of logging, and there was a tendency for its population to be lower in heavily logged areas than in lightly logged areas. In contrast to the findings from the heavily logged area, none of the species were found at a lower group density in the lightly logged area than in the unlogged area, and group densities in this area were not changing at a statistically significant rate. The results of our study suggest that, in this region, low‐intensity selective logging could be one component of conservation plans for primates; high‐intensity logging, however, which is typical of most logging operations throughout Africa, is incompatible with primate conservation.

CHARACTERIZATION OF CANCER CELL LINES ESTABLISHED FROM TWO HUMAN METASTATIC BREAST CANCERS - SHANKAR K. NAYAK; SURABHI KAKATI; SHASHI R. HARVEY; COLIN C. MALONE; ANDREW N. CORNFORTH; ROBERT O. DILLMAN (In Vitro Cellular & Developmental Biology - Animal, 2000)

Developing applications for lactococcal bacteriocins - R. Paul Ross; Mary Galvin; Olivia McAuliffe; Sheila M. Morgan; Maire P. Ryan; Denis P. Twomey; William J. Meaney; Colin Hill (Antonie van Leeuwenhoek, 1999)

The relationship between the rate of starch synthesis, the adenosine 5′-diphosphoglucose concentration and the amylose content of starch in developing pea embryos - Belinda R. Clarke; Kay Denyer; Colin F. Jenner; Alison M. Smith (Planta, 1999)

Evidence for the involvement of the fatty acid and peroxisomal β-oxidation pathways in the inhibition by dehydroepiandrosterone (DHEA) and induction by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and benz(a)anthracene (BA) of cytochrome P4501B1 (CYP1Bl) in mouse embryo fibroblasts (C3H10T1/2 cells) - Fidelis I. Ikegwuonu; Colin R. Jefcoate (Molecular and Cellular Biochemistry, 1999)

The synthesis and spectroscopic analysis of the neurotoxic prion peptide 106–126: Comparative use of manual Boc and Fmoc chemistry - Michael F. Jobling; Colin J. Barrow; Anthony R. White; Colin L. Masters; Steven J. Collins; Roberto Cappai (International Journal of Peptide Research and Therapeutics, 1999)

Kinetic measurements of binding of galectin 3 to a laminin substratum - Erminia A.M. Barboni; Sulemana Bawumia; R. Colin Hughes (Glycoconjugate Journal, 1999)

Patchy surface stone movement during disturbance in a New Zealand stream and its potential significance for the fauna - Christoph D. Matthaei; Kathi A. Peacock; Colin R. Townsend (Limnology and Oceanography, 1999)
A patchy movement of surface stones during disturbance in streams has been proposed from field observations, but few attempts have been made to quantify this phenomenon. If spates produce a mosaic of stable and disturbed areas, the former could serve as refugia for benthic invertebrates. We monitored the stability of surface stones at three geomorphically contrasting sites in a river with an unstable bed during three spates and one large flood. Stones were marked in situ by drilling holes in them or by scraping them with a chisel. For each stone, we determined visible surface area, embeddedness in the substratum, water depth, size of surrounding stones, and presence or absence of large stones upstream. During the first monitoring period, which covered one spate and the large flood, we marked 400 stones at each 20‐m‐long site in a systematic grid with 40 to 60 cm between stones. Stones were relocated after each disturbance, but each stone set was used to monitor both subsequent events. After the large flood, few marked stones were left. Therefore, additional sets of 200 stones were marked for a second monitoring period covering the remaining two spates; these stones were located at the same sites, but the distance between transects was doubled. Patchy bed movement occurred during all four disturbances, especially during the three smaller ones, which moved only 33 to 72% of marked stones. Stability of individual stones was mainly influenced by their size and embeddedness and sometimes by the water depth above the stone. Larger‐scale parameters (e.g., the position of the stone across the transect) were less important. Whole‐site stability differed little among sites. During the three smaller events, many stable surface stones were available as potential invertebrate refugia. In contrast, invertebrate refugia may have been restricted to the hyporheic zone and inundated flood‐plain gravels during the large flood. Because patchy stone movement was observed in a river with an unstable bed, it is likely to be a feature of most rivers. Therefore, small‐scale experiments may be able to simulate the effects of disturbance on the benthic community more effectively than previously thought.

Characterization of microsatellite loci for red‐necked grebes Podiceps grisegena - Joel L Sachs; Colin R Huges (Molecular Ecology, 1999)

Inducible anti-parasitic effector mechanisms in human uroepithelial cells: tryptophan degradation vs. NO production - W. Däubener; Vanessa Posdziech; Ulrich Hadding; Colin R. MacKenzie (Medical Microbiology and Immunology, 1999)

Spawning site selection by two galaxiid fishes, Galaxias anomalus and G. depressiceps , in tributaries of the Taieri River, South Island, New Zealand - Suzanne J. Moore; Richard M. Allibone; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 1999)
Recent studies have led to the recognition of Galaxias depressiceps and reinstatement of Galaxias anomalus . The two species maintain near allopatric distributions and it has been suggested that spawning habitat availability, at least partially, controls the distribution of these species. The spawning habitat of each species was determined and an assessment of the influence of spawning habitat availability on the distribution of the two species was carried out. Factors that may have influenced the onset of spawning were also examined. We found that G. depressiceps selected spawning sites with a high proportion of boulder substrata and nests were found on the underside of or between boulders. G. anomalus spawned within the streambed substrata, under boulders or cobbles, in shallow water and narrow channels relative to the available habitat. Suitable boulder spawning substratum for G. depressiceps in the G. anomalus sites was limited and this supports the hypothesis that spawning habitat availability influences G. depressiceps distribution. Conversely G. anomalus spawning habitat was available in G. depressiceps streams, indicating that spawning habitat limitations are not restricting G. anomalus . The onset of spawning, for both species, did not appear to be related to daylight, phase of the moon, or stream water level, but all species started spawning as water temperatures rose. The proximity of G. anomalus spawning sites to the stream edge and their occurrence in poorly consolidated substrata presents two management issues. Water abstraction may expose spawning sites if stream water levels are lowered, and these sites are vulnerable to trampling by stock.

Investigation and documentation of hybridization betweenParkinsonia aculeata andCercidium praecox (Leguminosae:Caesalpinioideae) - Julie A. Hawkins; Laura White Olascoaga; Colin E. Hughes; Jos-Luis R. Contreras Jimnez; Pedro Mercado Ruaro (Plant Systematics and Evolution, 1999)

Growth and dissemination of a newly-established murine B-cell lymphoma cell line is inhibited by multimeric YIGSR peptide - Toshimi Michigami; Motoyoshi Nomizu; Yoshihiko Yamada; Colin Dunstan; Paul J Williams; Gregory R Munday; Toshiyuki Yoneda (Clinical & Experimental Metastasis, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Orf Virus Encodes a Homolog of the Vaccinia Virus Interferon-Resistance Gene E3L - Colin J. McInnes; Ann R. Wood; Andrew A. Mercer (Virus Genes, 1998)

Comparative dietary analysis of a recently described fish species complex (Galaxiidae) in a New Zealand river - Richard M. Allibone; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 1998)
The diets of several populations of four recently described species of galaxiid with allopatric distributions were examined in the Taieri River, New Zealand. Comparisons of available prey items and prey consumed were carried out to examine whether the distributions of the galaxiid species might be influenced by food availability and preferences. Seventy‐three prey categories were identified. The availability of four of these (Deleatidium, Oligochaeta, Elmidae larvae and adults) differed among the streams occupied by different galaxiid species. Three differences in the frequency of prey consumption (Deleatidium, Oxyethira, and Elmidae larvae) were detected. Despite differences in diet it was concluded that all four fish species were generalist predators of invertebrates with similar diets that were influenced mainly by prey availability. Furthermore prey availability was not considered responsible for the allopatric distribution of the four species, rather, spawning habitat availability, physical nature of the streams, and prior geological history of the Taieri catchment are considered the controlling influences on galaxiid distribution.

Chloroplast DNA phylogeography of Alnus glutinosa (L.) Gaertn. - R. ANDREW KING; COLIN FERRIS (Molecular Ecology, 1998)
Traditionally, information on the postglacial history of plant species has been gained from the analysis of fossil pollen data. More recently, surveys of present patterns of genetic variation have given valuable insights into species phylogeography. The genus Alnus , based on fossil data, is known to have had at least four glacial refugia. A survey of chloroplast DNA (cpDNA) diversity in populations of black alder ( A. glutinosa ) was undertaken in order to gain more insight into its postglacial history. This revealed a high degree of structuring of 13 cpDNA haplotypes on a European scale which indicated that most of northern and central Europe was colonized from a refuge in the Carpathian Mountains. Based on the distribution of two common cpDNA haplotypes, colonization routes from this refuge can be determined. The locations of other previously identified refugia are confirmed and two formerly unconfirmed refugial areas for alder (southern Spain and Turkey) are proposed.

Population Characteristics of Howlers: Ecological Conditions or Group History - Colin A. Chapman; Sophia R. Balcomb (International Journal of Primatology, 1998)

CHARACTERIZATION OF POLYMORPHIC TRINUCLEOTIDE MICROSATILLITE LOCI IN THE GREAT‐TAILED GRACKLE - Colin. R. Hughes; Ryan. Kavlie; Kristine. Johnson (Molecular Ecology, 1998)

The use of biomarkers in Daphnia magna toxicity testing - Wim M. De Coen; Colin R. Janssen (Hydrobiologia, 1998)

A novel pink-pigmented facultative methylotroph, Methylobacterium thiocyanatum sp. nov., capable of growth on thiocyanate or cyanate as sole nitrogen sources - A. P. Wood; Donovan P. Kelly; I. R. McDonald; Sarah L. Jordan; Thomas D. Morgan; Sajdah Khan; J. Colin Murrell; Elena Borodina (Archives of Microbiology, 1998)

Viability and activity in readily culturable bacteria: a review and discussion of the practical issues - Douglas B. Kell; Arseny S. Kaprelyants; Dieter H. Weichart; Colin R. Harwood; Michael R. Barer (Antonie van Leeuwenhoek, 1998)

Autotrophic growth on carbon disulfide is a property of novel strains of Paracoccus denitrificans - Sarah L. Jordan; I. R. McDonald; Anna J. Kraczkiewicz-Dowjat; Donovan P. Kelly; Frederick A. Rainey; J. Colin Murrell; A. P. Wood (Archives of Microbiology, 1997)

Trinucleotide Microsatellite Loci and Increased Heterozygosity in Cross-Species Applications in the Social Wasp, Polistes - Joan E. Strassmann; John M. Peters; Karen Barefield; Carlos R. Solís; Colin R. Hughes; David C. Queller (Biochemical Genetics, 1997)

The intermediate disturbance hypothesis, refugia, and biodiversity in streams - Colin R. Townsend; Mike R. Scarsbrook; Sylvain Dolédec (Limnology and Oceanography, 1997)
The intermediate disturbance hypothesis has been influential in the development of ecological theory and has important practical implications for the maintenance of biodiversity but has received few rigorous tests. We tested the hypothesis that maximum taxon richness of macroinvertebrates will occur in communities subject to intermediate levels of disturbance at 54 stream sites that differed in the frequency and intensity of flood‐related episodes of bed movement. Our results support the intermediate disturbance hypothesis, with both highly mobile and relatively sedentary taxa conforming to the predicted bell‐shaped curve. Taxon richness was not related to habitat area (stream width), distance from the headwater, or the diversity of microhabitats (particle size categories) but was significantly and negatively related to the proportion of the substratum made up of small particles. Of all the factors measured, however, bed disturbance was by far the best at accounting for variation in taxonomic richness. We also quantified several kinds of potential refugia for invertebrates and found a positive relationship between richness and a refugia axis that combines amount of dead space with proportion of large substratum particles.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Cost-effectiveness of screening blood donors for hepatitis C and non-A, non-B, non-C hepatitis - C. Colin; P. Vergnon; A. M. Jullien; S. Excoffier; Y. Matillon; C. Trepo; J. P. Aymard; D. Bastit; M. L. Bidet; R. Breviere; F. Chenais; F. Hau; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Cysteine ligand vibrations are responsible for the complex resonance Raman spectrum of azurin - Colin R. Andrew; Jane Han; Tanneke den Blaauwen; Gertie van Pouderoyen; Erik Vijgenboom; Gerard W. Canters; Thomas M. Loehr; J. Sanders-Loehr (JBIC Journal of Biological Inorganic Chemistry, 1997)

Optimisation of 3-hydroxyeicosanoid biosynthesis by the yeast Dipodascopsis uninucleata - Simon R. Fox; Colin Ratledge; John Friend (Biotechnology Letters, 1997)

Macrophage surface glycoproteins binding to galectin-3 (Mac-2-antigen) - Sucai Dong; R Colin Hughes (Glycoconjugate Journal, 1997)

Taxonomic relationships of Thiobacillus halophilus , T. aquaesulis , and other species of Thiobacillus , as determined using 16S rDNA sequencing - I. R. McDonald; Donovan P. Kelly; J. Colin Murrell; A. P. Wood (Archives of Microbiology, 1997)

An endo-1,4-β-glucanase expressed at high levels in rapidly expanding tissues - David A. Brummell; Colin R. Bird; Wolfgang Schuch; Alan B. Bennett (Plant Molecular Biology, 1997)

Taxonomic relationships ofThiobacillus halophilus, T. aquaesulis, and other species ofThiobacillus, as determined using 16S rDNA sequencing - Ian R. McDonald; Donovan P. Kelly; J. Colin Murrell; Ann P. Wood (Archives of Microbiology, 1996)

Book review and notices - M. Beveridge; M. Jobling; Colin E. Adams; R. Williamson (Aquaculture International, 1996)

The potential for diazotrophy in iron-and sulfur-oxidizing acidophilic bacteria - Paul R. Norris; J. Colin Murrell; Deborah Hinson (Archives of Microbiology, 1995)

Aberrant individuals ofNeomysis integer and other Mysidacea: Intersexuality and variable telson morphology - Jan Mees; Nancy Fockedey; Ann Dewicke; Colin R. Janssen; Jean-Claude Sorbe (Aquatic Ecology, 1995)

DNA binding, adduct characterisation and metabolic activation of aflatoxin B1 catalysed by isolated rat liver parenchymal, Kupffer and endothelial cells - Birgit Schlemper; Joanne Harrison; R. Colin Garner; Franz Oesch; Pablo Steinberg (Archives of Toxicology, 1991)